L’impact des clauses d’arbitrage entre investisseurs étrangers et Etats sur la souveraineté : une analyse de l'équilibre entre protection des investisseurs étrangers et la souveraineté - Ahouyanganga Matondo, Dan Salomon (Université de Montréal, 2026)
Ce mémoire analyse l’impact des clauses d’arbitrage entre investisseurs étrangers et États sur la souveraineté étatique, en s’intéressant à l’équilibre entre protection des investisseurs et capacité réglementaire des États. Dans un contexte de mondialisation marqué par les crises sanitaires et les tensions géopolitiques, les États cherchent à attirer les investissements étrangers tout en préservant leur souveraineté économique. Le travail met en lumière le rôle du mécanisme RDIE, permettant aux investisseurs étrangers de contester les mesures étatiques devant des tribunaux arbitraux internationaux, contournant ainsi les juridictions nationales. Bien qu’il sécurise les flux d’investissements et renforce la confiance des investisseurs, le RDIE peut créer des déséquilibres, limitant la marge de manœuvre des États dans des domaines sensibles tels que la santé publique, l’environnement ou les droits sociaux. À travers l’analyse de cas emblématiques et des traités internationaux d’investissement, le mémoire propose des pistes pour concilier la protection juridique des investisseurs et le respect de la souveraineté étatique. Il conclut que le RDIE, tout en étant un outil essentiel de sécurisation des investissements, nécessite des réformes pour garantir un équilibre durable entre intérêts privés et intérêt général. This research study will analyze the impact of arbitration clauses between foreign investors and states on state sovereignty, focusing on the balance between investor protection and the regulatory capacity of states. In a globalized context marked by health crises and geopolitical tensions, states seek to attract foreign investment while preserving their economic sovereignty. The study highlights the role of the ISDS mechanism, which allows foreign investors to challenge state measures before international arbitration tribunals, thus bypassing national courts. Although it ensures investment flows and strengthens investor confidence, the ISDS system can create imbalances, limiting states' room for maneuver in sensitive areas such as public health, the environment, and social rights. Through analysis of historical cases and international investment treaties, the thesis proposes ways to reconcile legal protection for investors with respect for state sovereignty. It concludes that while ISDS remains an essential tool for securing investments, it requires reform to ensure a sustainable balance between private interests and the public good.
Keywords: Arbitration clauses; Clauses d’arbitrage; Foreign investors; ISDS; Investisseurs étrangers; Investment treaties; RDIE; Souveraineté; Sovereignty; States; Traités d’investissement; États

L'équilibre de la relation entre investisseur étranger et État hôte dans la jurisprudence arbitrale - Jorland, Maxime (Université Paris-Saclay, 2025)
Le droit des investissements internationaux s'est construit sous l'impulsion des tribunaux arbitraux qui, dans leur rôle d'interprétation du droit international coutumier et des traités d'investissement, ont contribué à enrichir le droit matériel des investissements. La multiplication des sentences rendues a constitué progressivement une véritable jurisprudence, visant à équilibrer la relation entre l'investisseur étranger et l'État hôte. Cependant, l'interprétation des traités par les tribunaux arbitraux s'est souvent faite dans un objectif de protection de l'investisseur face à la puissance publique de l'État, jusqu'à inverser parfois le rapport de force entre les deux opérateurs. De plus, l'absence de principe de précédent en arbitrage d'investissement a contribué à créer un flou notionnel, du fait des interprétations changeantes des dispositions des traités protégeant l'investisseur étranger. 2Cette étude vise donc à faire état du droit positif des investissements internationaux en déterminant un courant doctrinal commun aux sentences arbitrales. Une fois ce travail de compilation réalisé, l'objectif sera alors de déterminer l'état de l'équilibre des forces entre les deux opérateurs et proposer un rééquilibrage du droit des investissements. Ce rééquilibrage passe notamment par une redéfinition des critères jurisprudentiels imprécis ou changeants et une adaptation de la protection de l'investisseur étranger aux enjeux modernes du commerce international, tout en veillant à permettre à l'Etat hôte de conserver ses prérogatives de puissance publique. International investment law has largely been shaped by arbitral tribunals, whose interpretative function with regard to customary international law and investment treaties has contributed significantly to the development of substantive investment law. The proliferation of arbitral awards has progressively given rise to a de facto jurisprudence, aimed at striking a balance between the interests of foreign investors and the sovereign rights of host States. However, treaty interpretation by arbitral tribunals has often been guided by a protective logic in favour of the investor, at times to the extent of inverting the power dynamic between the two actors. Furthermore, the absence of a binding precedent doctrine in investment arbitration has fostered conceptual uncertainty, resulting from fluctuating interpretations of the treaty provisions safeguarding foreign investors.This study seeks to provide an overview of the current state of positive international investment law by identifying a coherent doctrinal trend emerging from arbitral case law. Based on this synthesis, the aim is to evaluate the prevailing balance of power between the investor and the host State, and to propose avenues for rebalancing investment law. Such rebalancing entails, in particular, a clarification of vague or inconsistent jurisprudential standards and an adaptation of investor protection to contemporary challenges of international trade, while ensuring that host States retain their sovereign regulatory authority.
Issue: 2025UPASH004
Keywords: Arbitrage; Arbitrage commercial international; Arbitration; CIRDI; Etat hôte; FDI; Host state; ICSID; International; Investissements; Investissements étrangers; Investisseur; Investments; Investor

Contribution à l’étude de la réservation des utilités des données numériques - Grave-Renaud, Gonzague (Université de Lille, 2025)
La dématérialisation et la numérisation croissantes de notre économie ont élevé les données au rang de matière première indispensable. La valeur des données réside dans leurs exploitations potentielles. C’est pourquoi leurs détenteurs cherchent à maximiser leurs revenus en limitant l’accès. Ce constat souligne les enjeux de gouvernance des données. La problématique de la réservation des données a alors émergé. Le constat est que la propriété intellectuelle ne parvient pas à appréhender pleinement la donnée. Néanmoins, l’analyse du droit positif révèle l’existence de mécanismes du droit commun permettant une réservation des utilités des données, tels que le contrat, la concurrence déloyale et parasitaire et le secret des affaires. Bien que ces mécanismes offrent une réservation, ils ne sont pas exempts de lacunes. Aussi, la question de la propriété des données a émergé et a suscité un vif débat. Cette interrogation a engendré un renouvellement des approches théoriques et pratiques du droit de propriété. Dans une approche prospective, un droit exclusif d’exploitation sur les données a été esquissé sous la forme d’un droit sui generis. Cet exercice de conceptualisation a mis en exergue les difficultés que pourrait entraîner une telle reconnaissance. Par ailleurs, il est impératif de trouver un juste équilibre entre la volonté d’appropriation des données et le droit d’accès des tiers à celles-ci afin d’instaurer un régime de protection à la fois efficace et équitable.
Keywords: Biens incorporels; Brevets d'invention; Contrats; Data; Données; Droit d'auteur; Droit des affaires; Droit d’accès; Intellectual property; Investissements; Investments; Propriedade intelectual; Propriété; Propriété intellectuelle; Protection de l'information (informatique) – Droit; Reservation; Responsabilité (droit); Right of access; Réservation; Secret; Systèmes d'information; Valeur; Value

Libérer le potentiel commercial de l'Afrique : Stimuler les marchés régionaux et réduire les risques - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Nations Unies, 2025)
Rapport sur le développement économique en Afrique 2024

International investment regime reform : integrating sustainable development into Uganda’s bilateral investment treaty system – a new model bit - Asiimwe, Esther Muchwa (University of Pretoria, 2025)
This thesis critically analyses Uganda’s bilateral investment treaty (BIT) system to determine its compatibility with sustainable development imperatives and proposes a new model BIT that aligns with Uganda’s evolving development priorities. Recognising the country’s reliance on foreign direct investment (FDI) for economic growth, this study interrogates the extent to which Uganda’s current BITs—many of which were concluded during earlier policymaking eras—expose the country to legal, economic, and regulatory risks. These include susceptibility to investor–state dispute settlement (ISDS) claims, constraints on the host state’s right to regulate, and a lack of provisions promoting environmental, social, and developmental objectives. Through doctrinal and comparative legal analysis, the study traces the historical evolution of international investment law (IIL), critiques the limitations of Uganda’s domestic and treaty-based FDI frameworks, and identifies substantive and structural weaknesses in Uganda’s in-force and model BITs. The analysis also considers international reform efforts and best practices from new-generation investment agreements, including the AfCFTA Protocol on Investment, the Investment Facilitation for Development (IFD) Agreement, and the SADC and EAC Model BITs. Particular attention is paid to the South African BIT reform experience as a comparator for Uganda’s reform journey. The study finds that Uganda’s BIT system is outdated, overly protective of investors, and poorly aligned with its sustainable development goals (SDGs). It recommends terminating unratified and problematic BITs, renegotiating existing ones, and adopting a new model BIT that balances investor protection with Uganda’s regulatory autonomy and sustainable development objectives. To this end, a draft model BIT is proposed as an annex to guide future treaty negotiations and reform Uganda’s investment regime in line with contemporary global standards and regional aspirations.
Keywords: Bilateral Investment Treaties (BITs); ISDS; Investissements; Investment law reform; Investments; Investor-State Dispute Settlement; Uganda

Expedited procedures in the Multilateral Investment Court: efficiency and consistency - Shouzab, Ali (Uppsala universitet, 2025)
The ongoing ISDS reform, under UNCITRAL Working Group III with a substantial input from the EU, has recently proposed for the establishment of a Multilateral Investment Court (MIC) with an appellate mechanism. Simultaneously, expedited arbitration procedures have gathered significant academic interest in the recent decades. While extensive literature exists on both the MIC development and expedited procedures, their intersection remains relatively unexplored. This dissertation bridges this research gap by analyzing how the best practices from different expedited procedures and EU treaties could be used to establish expedited MIC procedures. Adopting a doctrinal methodology, the research identifies the prominent models and trends in different expedited procedures, accesses their compatibility with the objectives of MIC, and finally proposes a suitable model to attain (cost and time) efficiency and consistency both for the first-tier and appellate proceedings in MIC. By doing so, the study contributes some recommendations for the development of expedited MIC procedures.
Keywords: Appellate Proceedings; Consistency; Efficiency; Expedited MIC Procedures; Expedited Procedures; First-Tier Proceedings; ISDS Reform; Multilateral Investment Court (MIC); UNCITRAL Working Group III

Unlocking Africa's trade potential: Boosting regional markets and reducing risks - United Nations Conference on Trade and Development (United Nations, 2025)
Economic Development in Africa Report 2024

From Divergent Paths to the Same Trap: The Legitimacy Crisis of the Investor-State Dispute Settlement System - Sönmez, Esma Yağmur (Middle East Technical University, 2024)
This thesis critically examines a much-debated issue in international law: the legitimacy of the Investor-State Dispute Settlement system (ISDS). The system was initially conceived to provide an alternate dispute resolution mechanism for the protection and promotion of foreign investment. In time, this objective has incited a discussion on the legitimacy of the system as the developed world has started to experience the role of host states. Since then, they have taken the lead in the reform process to achieve a balance between host state's and foreign investors' rights. To this effect, both the European Union (EU) and the Third Way Approaches to International Law (TWAIL) are for centralization of the system arguing its current problems emanate from its ad hoc and decentralized nature. Although both are aimed at system centralization, the paths they take to achieve it clearly differ. The EU seeks a permanent investment court by which ad hoc arbitration would give way to a more centralized framework. However, TWAIL advocates for a return to the pre-ISDS era, where national courts resolve investment disputes between foreign investors and states. The effectiveness of these two reform ideas in addressing the purported legitimacy concerns of the ISDS is critically examined in this thesis using Martti Koskenniemi's legal approach. Ultimately, it asserts that neither proposal is adequate to resolve the legitimacy issue of the system, as legitimacy can only be achieved by strengthening the principle of justice, which is feasible alone through a more decentralized structure.
Keywords: ADR; Alternative dispute resolution; Foreign investment; Foreign investors; ISDS; Investment Dispute; Investments; Investor-State Dispute Settlement

Diaspora as a Generator of Foreign Direct Investment - Dizdarević, Emina (IUS LAW Journal, 2024)
Focusing on Bosnia and Herzegovina, this study examines how diasporas contribute to the creation of foreign direct investment (FDI) in developing countries. It defines FDI as the acquirement over assets in a foreign nation and highlights how diaspora populations support investment flows. It also examines diaspora investment strategies, such as diaspora portfolio investment (DPI) and diaspora direct investment (DDI), and offers a historical overview of diaspora FDI patterns and how Bosnia and Herzegovina's policies are changing to engage its diaspora more.One case study illustrates the impact of diaspora-led FDI by highlighting the success of Senad Šantić, a Bosnian entrepreneur who returned to his home country to start a tech company. While these investments support development and economic growth, there are still issues, like the possibility of putting one's own interests ahead of the interests of the economy as a whole. Particularly in Bosnia and Herzegovina, where diaspora participation has historically been low, the implementation of effective policies and procedures is crucial, especially from a regulation perspective.The study also looks at the future of FDI, emphasizing the part that digital technology and new investment patterns will play. Opportunities for developing nations can be found in digital FDI, especially in industries like fintech and e-commerce, yet obstacles still exist in luring these investments. According to all the findings, developing nations can improve their chances for economic success by creating an atmosphere that encourages diaspora investment which will shift those nations into the global investment scene. Ultimately, FDI regulations and government programs are needed in order to fully utilize diaspora-led FDI for sustained growth.
Keywords: Bosnia and Herzegovina; Diaspora Engagement; Diaspora Investment; Economic Development; FDI; Foreign direct investment

Business Environment and its Impact on Attracting Foreign Direct Investment - Tanrıverdi, Elif Tanrıverdi (IUS LAW Journal, 2024)
This study provides an in-depth look at the complex relationship between business environments and foreign direct investment. The study examines this critical issue by focusing on emerging economies, such as Kosovo. In this research, analytical and empirical research methods have used to highlight the importance of FDI in promoting economic growth. FDI not only increases production capacity but also supports economic growth by increasing purchasing power and creating employment opportunities, especially in countries in transition. This analysis distinguishes between endogenous and exogenous variables to classify the various elements of the business environment. It is important to emphasize how a supportive business environment plays a vital role in attracting investment. The main factors affecting FDI include infrastructure quality, political stability, workforce skills, market potential and tax incentives. These initiatives are critical to creating a more favorable investment climate.As a result of the variables the study concludes by emphasizing the need for continuous reforms to strengthen the business environment. Such strategic efforts are crucial to optimize FDI flows and advance sustainable economic development. By strengthening regulatory frameworks and improving infrastructure, developing countries can be in better position itself to attract foreign investors. Furthermore, creating a strong business environment can also support the development of local entrepreneurs, increasing economic diversification. As a result, it not only facilitates the flow of capital, but also contributes to the long-term stability and growth of the national economy. Therefore, policymakers and governments need to prioritize these initiatives and develop comprehensive and sustainable strategies to improve the business environment.
Keywords: Business Environment; Economic growth; Foreign direct investment; Investment Incentives; Investments; Political Stability

Climate change and international investment law : lessons from Africa's investment treaty practice - Mogashoa, Lebogang Paul (University of Pretoria, 2024)
This dissertation critically analyses new generation continental, regional and bilateral investment treaties in Africa with the aim to explore enhancements that could be made thereto in order to enable African citizens to hold investors accountable for investment-related climate change issues in Africa. The main research question answered in the dissertation is: to what extent does African investment treaty practice incorporate climate change-related provisions and investor accountability for climate change. The dissertation analysed traditional investment treaties, particularly noting their silence on climate change and investor accountability, and their partiality to investor protection. Using the AfCFTA Investment Protocol as an anchor alongside other new generation continental, regional and bilateral investment treaties in Africa, it discusses a fundamental contemporary shift in African investment treaty practice towards ensuring sustainable investments and greater investor accountability for sustainability in Africa. It also explores the various limitations in these new generation investment treaties that still make investor accountability. In the end it proposes reforms to the Investor-State Dispute Settlement provisions of these investment treaties to recognise citizen-led arbitral claims against investors, utilising the Hague Rules on Business and Human Rights as the procedural infrastructure for handling arbitration of such claims.
Keywords: AfCFTA; African Continental Free Trade Area; Climate change; ISDS; Investment treaties; Investments; Investor-State Dispute Settlement

Anticipation of ratings during crises and investor behaviour: The case of MENA countries - Mahouachi, Noura; Henchiri, Jamel Eddine (African Journal of Economic and Business Research, 2024)
The study explores the reaction of stock markets to anticipated or unexpected rating announcements by the market in a crisis context by conducting an empirical study on the MENA (Middle East and North Africa) stock market over the period from December 2010 to August 2022. The results show that the crisis context support the anticipation of bad ratings and neutral ratings as opposed to good ratings. These results validate the asymmetry in investor reaction to announcements of anticipated rating downgrades compared with announcements of upgrades in times of crisis. This reaction highlights the irrational behave of investors in times of crisis. In fact, when investors detect a risk concerning the financial situation of a stock, they anticipate a downgrade and react quickly, even before the official announcement of the downgrade, by selling their shares on masse. This action will cause the share price to fall. Similarly, the market’s weak reaction to early good announcements is explained by the fact that this type of announcement does not provide them with any unknown information to guide their financial decisions.
Keywords: Abnormal returns; Anticipation; Event study; Expected rating; Stock markets; Unexpected rating

A Proposal for Reforming the Calculation of Damages in Investment Treaty Arbitration = Proposition pour le calcul des dommages-intérêts dans l’arbitrage au titre des traités d’investissement = Propuesta para Reformar el Cálculo de Daños en el Arbitraje de Los Tratados de Inversión - Jarrett, Martin (Investment Treaty News, 2024)

The impact of ISDS arbitration claims and adjudication on cross-border direct investment - Du, Julan; Zhang, Yifei (Transnational Corporations Review, 2024)
This study investigates the impact of the arbitration cases under the Investor-State Dispute Settlement (ISDS) scheme on cross-border direct investment in the form of merger and acquisition deals. The initiation of ISDS claims has significant and negative effects on direct investment from the claimant home country to the developing or weak-institution responding country. Indirect expropriation claims often have stronger effects than direct expropriation claims. The investor-win arbitration cases produce a significant substantiation effect by reducing merger flows, while the state-win cases produce an acquittal effect that encourages the subsequent capital inflow to the respondent state. Both effects are more striking in weak-institution or less developed target countries. We also detect some spillover effects of ISDS arbitration.
Keywords: Arbitration decisions; Cross-border merger deals; Direct and indirect expropriations; ISDS claims

Le traitement des investissements étrangers dans le Code des investissements de la RDC de 2002 - Nzohabonayo, Anaclet (Revue africaine de droit des affaires, 2024)
Cet article examine le traitement que le code des investissements de la République démocratique du Congo garantit aux investisseurs étrangers qui choisissent ce pays comme destination de leurs investissements. L’étude examine d’abord la portée dudit code en articulant son analyse sur sa philosophie afin de dégager les motivations du législateur et les objectifs que ce dernier lui a assignés. L’examen du champ d’application du code met l’accent sur sa portée ratione personae, ratione materiae et ratione loci. La réflexion explore ensuite les principaux mécanismes de traitement des investissements en démontrant que le code consacre un traitement non discriminatoire envers les investisseurs étrangers et qu’il adhère à l’orthodoxie des normes classiques de protection des investissements. L’étude analyse par ailleurs les incitatifs fiscaux et douaniers que le code concède aux investisseurs étrangers afin d’accroître la compétitivité de la destination congolaise parmi les investisseurs exportateurs de capitaux. Après analyse, l’étude conclut qu’en dépit de ses imperfections que nos analyses ont permis de mettre en lumière, le code des investissements de 2002 offre aux investisseurs étrangers un traitement globalement satisfaisant.
Keywords: Congo (République démocratique); Investissements; Investments

Fundamentos jurídicos para a atração de investimentos estrangeiros diretos - Botelho, Rodrigo Jacobina (Universidade de São Paulo, 2024)
A história moderna da humanidade vem demonstrando que jaz míope a visão de que determinado país e sua economia podem viver e sobreviver em estado de isolamento hermético ante a economia globalizada. Não é concebível que determinada sociedade possa se desenvolver sem interação com investidores estrangeiros. Mesmo em países que, por opção ideológica, há certo isolamento, vemos hoje a existência de investimentos estrangeiros, ainda que sejam originados em outros países com o mesmo viés ideológico. Desta forma, os países em desenvolvimento e, em especial para o trabalho que aqui se apresenta, o Brasil têm que compreender as possíveis estruturas jurídicas e econômicas, bem como de políticas públicas que expressam tais estruturas, para poder pretender se credenciar como atrativos destinos de investimentos estrangeiros, seja pela outorga de benefícios (diretos ou indiretos), seja pela segurança ao investidor. No Brasil, entretanto, essa atratividade deve ser sopesada com a preservação de valores fundantes de nossa Constituição, congruentes com o ordenamento jurídico nacional e, ainda, devem ser, depois de efetivado o investimento, acompanhado por um sistema que imponha transparência e solidez ao cumprimento das contrapartidas desejadas: notadamente a geração de emprego e renda e de contribuição para a criação da riqueza nacional. O ponto central do presente trabalho gira em torno dos fundamentos jurídicos para a atração e manutenção, bem como a construção de um possível sistema de aferição da solidez jurídica de políticas de incentivo ao capital estrangeiro.
Keywords: Acompanhamento; Attraction policy; Benefits; Benefícios; Convenience; Conveniência; FDI; Foreign direct investment; Foreign investment; Investimento estrangeiro; Investments; Monitoring; Política de atração

Comportement d’investissement des entreprises camerounaises : analyse en données de panel 2015-2022 - Metangmo, Janvier; Nankap Seujib, Alexis (Finance & Finance Internationale, 2024)
L’objectif de cette étude est de déterminer les facteurs influençant le comportement d’investissement des entreprises camerounaises par une approche microéconomique. En effet, malgré un taux de profit élevé (l’EBE représente environ 60% de la valeur ajoutée), le taux d'investissement privé au Cameroun demeure très faible (18% du PIB) et risque de compromettre l'atteinte du stade de pays émergent à l'horizon 2035. En se basant sur le modèle théorique accélérateur-profit, nous avons estimé un modèle de panel dynamique grâce aux données de 381 entreprises sur la période 2015-2022, par la méthode des moments généralisés (GMM). Les résultats obtenus identifient la demande sur le marché (effet accélérateur) comme principal facteur qui agit positivement et significativement sur l’investissement. A contrario, le profit, la dette ou les capitaux propres n’ont pas une influence significative sur le comportement d’investissement des entreprises camerounaises. En outre, même en cas de demande importante, le comportement d’investissement des entreprises camerounaises est influencé par leur statut juridique, leur taille, leur activité principale et l’état sécuritaire de la zone d’implantation. Cela illustre à souhait l’importance d’améliorer l’environnement des affaires et d’encourager les entreprises camerounaises à muter vers des modes d’organisation leur garantissant non seulement un développement rapide mais aussi une pérennisation. The aim of this study is to determine the factors influencing the investment behavior of Cameroonian companies, using a microeconomic approach. Indeed, despite a high profit rate (EBITDA represents around 60% of value added), the private investment rate remains very low (18% of GDP) and risks compromising the country's ability to reach the stage of an emerging country by 2035. The covid 19 crisis, the Boko Haram security crisis in the northern part of the country and the secessionist crisis in the English-speaking regions all add to an already unfavourable business climate. These observations lead us to reflect further on the factors that explain the investment behavior of Cameroonian companies. Based on the theoretical accelerator-profit model, we estimated a dynamic panel model using data from 381 companies over the period 2015-2022, using the generalized method of moments (GMM). The results obtained identify market demand (accelerator-effect) as the main factor acting positively and significantly on investment. Conversely, profit, debt or equity do not have a significant influence on the investment behavior of Cameroonian companies. Other variables such as the company's legal status, size and activity also have an effect on investment. The company's geographical location in a zone of insecurity, such as the northern and western regions of Cameroon, also has a negative effect on investment behavior, no doubt due to the uncertainty and irreversible nature of the investment.
Keywords: Accelerator-profit model; Cameroon; Cameroun; Effet de levier; Entreprises; Firms; GMM; Investissements; Investments; Modèle accélérateur-profit; Q de Tobin; Tobin's Q

La réforme des dommages dans le règlement des différends entre investisseurs et États et la question de la réparation intégrale - Marzal, Toni (Investment Treaty News, 2024)
Keywords: Dispute resolutions; Dispute settlement; Investissements; Investments; Règlement des différends

L’intérêt du développement dans les accords de promotion et de protection des investissements - Nyeck, Emmanuel Noé (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
La conclusion des accords de promotion et de protection des investissements a pour fonction d’augmenter significativement les investissements directs étrangers dans les pays en développement afin de les sortir du sous-développement. Ces accords sont donc envisagés comme la panacée contre le sous-développement en raison de l’échec des solutions traditionnelles de lutte contre le sous-développement. Cependant, fort est de constater que le développement auxquels ils renvoient ne peut être élevé au rang d’une véritable obligation juridique dans la mesure où la notion de développement est elle-même est ancré dans la soft law.
Keywords: Bilateral Investment Treaties (BITs); Contentieux de l’investissement; Droit international de l’investissement; Droit international du développement; Droits de l’homme; Human rights; International Investment Law; International development law; Investment litigation; Traités bilatéraux des investissements

Global Common: The Rights and Responsibilities of the State and the Investor in Renewable Energy Foreign Investment - Pang, Hui (UNSW Sydney, 2024)
States poured millions of dollars to attract foreign renewable energy investments for climate change mitigation, however, when it becomes too hefty for some states, they have modified regulations to reduce the level of support. These regulation changes have led to dozens of investors filing arbitrations against the host states, alleging breaches of investment treaty obligations. This thesis examines whether the current investor-state dispute settlement (‘ISDS’) regime adequately addresses environmental concerns when adjudicating renewable energy investment cases. While renewable energy investments can help protect a global common (the atmosphere) and mitigate climate change, the regulation changes also seek to protect a domestic public good (financial stability of the host state). Therefore, when the protection of a global common conflicts with a domestic public interest in renewable energy ISDS cases, what are the rights and obligations of the host state and the investor? Are the existing approaches of the ISDS regime toward environmental concerns and other public interests fair and adequate, and if not, what interventions can be made? This thesis explores these questions by conducting doctrinal analysis on more than 60 renewable energy cases and the arbitral jurisprudence regarding international environmental obligations. It uses the constitutionalisation of international law to break the self-contained regime of international investment law and argues that common values should be regarded as equally important as investment protection goals in ISDS. This thesis finds that the ISDS regime considers international environmental obligations to be insignificant in supporting the host state’s defences in non-compliance of bilateral investment treaties or the investor’s claims for investment protection. This thesis shows that the current approach furthers discrepancies between climate change mitigation and international investment law. Not only does this approach fail to acknowledge the environmental connections of renewable energy investment, but it also creates opportunities for fossil fuel investors to seek compensation against environmental regulation changes using the same arguments. As an intervention against the current approach, this thesis proposes to reconstrue the concept of legitimate expectations to place common values on equal grounds with investment protection incentives. This thesis makes two significant contributions to knowledge. Firstly, it extends existing analyses of the conflicts and synergies between international investment law and environmental protection and contributes to the growing body of scholarship on this topic. Research on this topic has mainly focused on how the state safeguards environmental interests against investor protection claims. While this narrative comprises many cases, it does not capture the full picture and overlooks the possible contributions of private parties in protecting global commons. Instead, this thesis examines whether international environmental obligations can serve as a ‘shield’ for the state’s non-compliance in investment protection, or as a ‘sword’ for investors to compel the state to fulfil its international obligations. Secondly, this thesis makes an intervention to reconstrue ‘legitimate expectations’, where common values are reinforced and not only the interests of investors are protected but also the ‘legitimate expectations of a responsible investor’ from the state and local communities are taken into account.

A comparative evaluation of the South African income tax regime for investments using trusts - Herbst, Hendri (Stellenbosch University, 2023)
This study evaluates the South African income tax regime for investments using trusts. It considers whether reforms are required, and if so, how can this be done to create a tax framework that will encourage investment, limit tax avoidance and curb capital outflows, while considering South Africa’s unique context and challenges.
Keywords: Income tax; Investments; Taxation; Trusts and trustees

Standing in international investment and trade disputes - Ossa, Ralph; Staiger, Robert W.; Sykes, Alan O. (Journal of International Economics, 2023)
International investment agreements employ dispute settlement procedures that differ markedly from their counterparts in trade agreements. A prominent and controversial difference arises with respect to the issue of “standing”: Who has the right to complain to adjudicators about a violation of the agreement? While trade agreements limit standing to the member governments (state-to-state dispute settlement), investment agreements routinely extend standing to private investors as well (investor-state dispute settlement). We develop parallel models of trade and investment agreements and employ them to study this difference. We find that the difference in standing between trade and investment agreements can be understood as deriving from the fundamentally different problems that these agreements are designed to solve. Our analysis also identifies some important qualifications to the case for including investor-state dispute settlement provisions in investment agreements, thereby offering a potential explanation for the strong political controversy associated with these provisions.
Keywords: Bilateral investment agreements; Investments; Investor-State Dispute Settlement; State-to-state dispute settlement; Trade agreements; Trade dispute

Vulnerability Theory as a Paradigm Shift in International Investment Law: Reimagining the Role of the State - Küçüksu, Aysel; Ünüvar, Günes (Business and Human Rights Journal, 2023)
This article argues for a fundamental raison d'être reconceptualization of international investment law (IIL) through Martha Fineman's 'vulnerability theory'. The theory helps identify the structural sources of IIL's shortcomings, whilst philosophically challenging the one-sided view that foreign investors are entitled to protections, but are free from obligations vis-à-vis the communities affected by their undertakings. Emphasizing the productive power of the state to take positive action that acknowledges ordinary citizens' embeddedness within, and dependence upon, surrounding structures, the vulnerability theory challenges the hegemonic perception of the state as a source of danger - a view which has hitherto undermined both the potency and the enforceability of investor obligations. Used as a heuristic device in studying both IIL's existing structures and the potential avenues for reimagining it, Fineman's theory not only shines a novel light on the foundational premises of IIL, but also grants theoretical traction to existing ideas about improving the system.

Congolese Land Rights Put to the Test by the Private Real Estate Investment Revolution - Milenge, Christian Mwenyemali (Open Journal of Social Sciences, 2023)
Private investors’ land rights vary from country to country, depending on the legal system in place. The degree of openness of land laws determines the degree to which both domestic and foreign investors are attracted, as the latter aims to invest in countries with legal systems offering the most secure and sustainable interests. How can Congolese land laws be made more attractive to private investors in the real estate sector? Using exegetical and comparative methods, we will test our hypothesis that reform to increase the rights of private national and foreign investors to access land would be an asset. By comparing Congolese land law with other legal systems, and with current social and economic realities, we have concluded that accommodating land rights is a prerequisite for increasing both domestic and foreign private investment in real estate and an essential step towards boosting and modernizing real estate investment in the DRC.
Number: 9
Keywords: Agricultural Investment; Congolese Land Ownership Law; Investments; Land Rights; Private Investment; Real Estate Law

Les chaînes d’approvisionnement mondiales à forte intensité technologique : le potentiel de l’Afrique - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Nations Unies, 2023)
Rapport sur le développement économique en Afrique 2023

La transformation du Système de résolution des conflits entre État hôte et investisseur étranger : la conciliation des intérêts d’acteurs d’un système adaptatif complexe - Deligny Malchair, Marion (Université de Lorraine, 2023)
Les conflits entre État hôtes et investisseurs étrangers occupent, depuis une dizaine d’année le devant de la scène géopolitique. Le questionnement se porte aujourd’hui de façon globale sur l’articulation des méthodes de règlement de conflits particulièrement complexes en raison de leurs implications institutionnelles, juridiques et économiques. Cette thèse se consacre à appréhender le cadre de règlement des conflits d’investissements selon le modèle du système afin de déterminer les conditions nécessaires à la transformation profonde du Système de résolution des différends entre États-hôtes et investisseurs.L’analyse du Système de résolution des différends entre États-hôtes et investisseurs suppose d’abord d’en restituer le contexte historique et d’examiner les bases institutionnelles posées par le système CIRDI, celui-ci étant le fruit d’une idée, la substitution du droit à la force pour la résolution des différends d’investissement : « le paradigme juridictionnel ». Or, si des bases institutionnelles avaient été posées, celles relationnelles ne l’étaient pas. Il s’en suit un usage des mécanismes du Système de résolution des différends entre États-hôtes et investisseurs dans une logique défensive et adversariale. Cependant, la complexification croissante du monde et incidemment du système des investissements, conduit les acteurs de l’investissement à passer d’une logique adversariale à une logique de collaboration et de co-construction pour résoudre les inévitables problématiques auxquelles ils font face : « le paradigme consensuel ».Nous nous interrogeons alors sur les conditions nécessaires à la mise en œuvre de ce nouveau paradigme comme fondement du Système afin d’en provoquer la transformation profonde. L’application de concepts issus du champ d’étude de la complexité et des systèmes adaptatifs complexes permet de conclure que le consensualisme est tout à la fois le résultat et le moyen à mettre en œuvre pour faciliter cette transformation. Seule une démarche holistique, incluant l’ensemble des acteurs dans leur diversité, peut permettre de faire émerger des solutions innovantes à la hauteur des enjeux. Notre proposition est d’utiliser les outils et méthodes du Design Thinking appliqués au droit – le Legal Design- dont la démarche place les parties prenantes, et donc les éléments de culture et de contexte, au cœur du processus de conception de solutions, et susceptible de provoquer un changement dans la dynamique relationnelle des acteurs vers une logique de collaboration. Cette conclusion s’applique aux deux échelles retenues : celle de la transformation globale du Système de résolution des différends entre États-hôtes et investisseurs, et celle des projets d’investissement, dont une gouvernance participative doit être encouragée afin d’en permettre le succès et de permettre de réaliser une des vocations premières du système des investissements qu’est le développement des États d’accueil au bénéfice de leurs communautés. Conflicts between host states and foreign investors have been at the forefront of the geopolitical scene for the past ten years. Now the question is being raised on a global scale concerning the articulation of particularly complex conflict resolution methods because of their institutional, legal and economic implications. This thesis focuses on understanding the framework for resolving investment disputes based on the system model in order to determine which conditions are necessary for the profound transformation of the Dispute Resolution System between host states and investors.Before any analysis of the Dispute Resolution System between host states and investors can be undertaken, it is necessary to provide an insight into the historical context and to examine the institutional foundations of the ICSID system. These are the result of an idea, substituting international law to the use of force for the resolution of investment disputes: “the jurisdictional paradigm”. If institutional foundations were laid, relational ones were not. This resulted in the use of the Dispute Resolution System mechanisms between host states and investors in a defensive and adversarial logic. However, the increasing complexity of the world and, incidentally, of the investment system, has led investment players to move from an adversarial logic to one of collaboration and co-construction in order to resolve the inevitable problems they face: “the consensual paradigm”.We then question the conditions required for the implementation of this new paradigm as the foundation of the System in order to bring about its profound transformation. Applying concepts from the fields of study into complexity and complex adaptive systems leads to the conclusion that consensus constitutes both the outcome and the means to facilitate this transformation. Only a holistic approach, including all the actors involved and their diverse contexts, can make it possible to develop innovative solutions that meet these challenges. Our proposal is to apply Design Thinking tools and methods in a legal context – Legal Design. This approach places stakeholders, and therefore the elements of culture and context, at the heart of the process of designing solutions, and is therefore well suited to bringing about a change in the relational dynamics of the actors towards a logic of collaboration. This conclusion applies to both scales: that of the overall transformation of the Dispute Resolution System between host states and investors and that of investment projects, whose participative governance structure must be recognized as a crucial success factor and a means to support one of the primary purposes of the investment system, which is the development of host states for the benefit of their communities.
Keywords: Arbitrage; Arbitrage commercial international; Arbitragem; Arbitration; Complex Adaptive System; Dispute System Design; Droit international; Foreign investment; Investissements étrangers; Investment Conflits Resolution; Investment Mediation; Legal Design; MARD; Mediación; Mediation; Mediação; Médiation; Médiation d'investissement; Règlement de conflits; Résolution des conflits d'investissement; Système adaptatif complexe

Legal Framework on Protection of Environmental and Foreign Direct Investment Rights in Nigeria: A Reflection on the Oil and Gas Industry - Osaro, Ebiemere (African Journal of International Energy & Environmental Law, 2023)
It is trite that environmental challenges remain one of the major global concerns and no doubt of great impact on human existence and wellbeing. This impact is a result of human activities on the natural ecosystem. This article examines the legal framework by the Nigerian state in regulating the activities of the multinational investors in the oil and gas industry in the Niger Delta region of the country. It discusses the international, regional, and national legal framework in the protection of environment and environmental rights of the host community and foreign direct investment rights. The author demonstrates the imbalance in the protection of environmental and foreign direct investment rights from which suggestions are made towards correcting this injustice as caused by the existing legal framework.
Keywords: Community; Direct; Environment; Foreign investment; Niger Delta; Oil and Gas Industry; Protection; Rights

Addressing the Legitimacy Crisis of Investment Arbitration Through its Harmonization with World Trade Organization Law - Seifi, Seyed Jamal; Veis Karami, Mahdi (Public Law Researsh, 2023)
International investment law is facing a legitimacy crisis, in which to tackle, substantial efforts are being made in structural and procedural areas. The first step to overcoming this crisis is identifying the roots of it. The lack of a dynamic balance between public and private interests is one of the main factors creating this legitimacy crisis in this legal system.[1] This paper focuses on the changes in the investment arbitration jurisprudence to create this balance. The findings of this paper can explain one of the convergence points of international trade and investment law. Such a claim is based on the evolution of international trade law in facing a similar legitimacy issue and the structural-procedural approach of this legal system in balancing public and private interests as an ultimate solution to the crisis.[2] From this perspective, one of the major factors in creating a legitimacy crisis in both legal systems is the dominance of the paradigm for preference of private interests; and one of the convergence points of international trade and investment law has been to replace it by accepting the paradigm of creating a dynamic balance between competing goals.[3] This paper examines this convergence in arbitral jurisprudence.IntroductionIn recent years, the legitimacy crisis of the regime of international investment law and, as a result, the investor-state dispute settlement system has been one of the most important and controversial topics in the academic environment and the practice of states consequently, serious efforts in various fields to tackle this crisis have begun. According to this paper, choosing an arbitration mechanism modeled on international commercial arbitration to resolve disputes between host states and foreign investors can be evaluated as a wrong and hasty action that, regardless of its factors and contexts, has changed the nature and function of this system over time.[4] It should be noted that the main factor in such consequences is how this dispute resolution system is used which, contrary to the accepted model, always puts the host states in a "respondent" position in possible future disputes and, as a result, disrupts the balance expected in any international dispute settlement system. On this basis, the confrontation of the host state's sovereign competence in ensuring public interests with the foreign investors’ ability to challenge this competence is brought into the spotlight: currently, within the regime of international investment law, host states have only responsibilities and obligations in contrast to extensive and exclusive rights and privileges recognized for foreign investors, and this can be considered as the most important factor disturbing the said balance. The main issue in this field is to analyze the role of the investment arbitral tribunals in creating such a balance. In this regard, the authors, by focusing on the nature of investment treaties, and the relations between the parties in investment disputes and with emphasis on the general legal regime governing international investment, consider creating a dynamic balance between public and private interests to be the key to solving the crisis. They emphasize that; As long as the rights and obligations of the parties to the dispute are based on imbalanced grounds, the change in nature of the disputes and the function of the system -as the main roots of this legitimacy crisis - will remain. In this remark, it is very important to focus on the two-sided nature (public-private) of the relationships established in the framework of investment treaties. The relationship between the host state and the foreign investor is created within the framework of investment treaties and in light of fundamental differences from purely private relationships in international commercial arbitration.[5] Note that any dispute arising from this relationship is affected by its inherently public nature governed by public international law.[6] Thus, a purely private attitude towards these relations does not seem viable. As Ian Brownlie has stated in the case of SME v. the Czech Republic, it can lead to ignoring some of the basic elements of the relevant investment treaty.[7] In other words, the right and duty of the host state in protecting and promoting public interests is a fundamental part of this relationship, and any indulgence of it leads to a serious disruption of the mentioned balance through which the system's legitimacy will be the first victim.It is clear that the main task of any dispute resolution system is to create such a balance, and on this basis, and compared to the WTO dispute resolution system, the role of the investment tribunals in this process is discussed. This jurisprudential convergence is in line with the goal of strengthening the legitimacy of the international investment law system as a whole.Based on the above, the first part of this paper focuses on the process of establishing the ISDS in international investment law and its characteristics, the factors of the crisis of legitimacy are analyzed with an analytical approach, while also explaining the nature of investment treaties and explaining the general legal regime governing international investment. Furthermore, the lack of a dynamic balance between public and private interests is emphasized as the main cause of the crisis. In the second part, while comparing the two legal systems of international trade and investment with a similar crisis of legitimacy, we will examine the interaction of investment arbitration with the WTO's jurisprudence in facing this crisis through a case study of several investment arbitral awards. [1]. David Gaukrodger, “The Balance between Investor Protection and the Right to Regulate in Investment Treaties: A Scooping Paperˮ, OECD Working Paper on International Investment 2017/02, at 4.[2]. Nicholas DiMascio & Joost Pauwelyn, “Non-Discrimination in Trade and Investment Treaties: Worlds apart or Two Sides of the Same Coin?”, AJIL, Vol. 102, No.1, (2008), at 89.[3]. Jurgen Kurtz and Sungioon Cho, “Convergence and Divergence in International Economic Law and Politics”, EJIL, Vol. 20, No. 1, (2018), at 187.[4]. Benedict Kingsbury & Stephan W. Schill, “Public Law Concepts to Balance Investor's Rights with State Regulatory Actions in the Public Interest - The Concept of Proportionalityˮ, In Schill Stephan W., International Investment Law and Comparative Public Law (UK: Oxford University Press, 2010) at 76. [5]. Crina Baltag, “Reforming The ISDS System: In Search of a Balanced Approach?ˮ, Contemporary Asia Arbitration Journal, Vol. 22, No. 2, (2019), at 285.[6]. Ibid.[7]. Andreas Kulick, “Sneaking Through Backdoor – Reflections on Public Interest in International Investment Arbitrationˮ, Arbitration International, Vol. 29, No. 3, (2013), at 438.
Keywords: Crisis of Legitimacy; International Investment Law; Investor-State Dispute Settlement; WTO; World Trade Organization

La place contestée de l'arbitrage international en droit de l'investissement - El Issa, Rayyan (Université Paris-Saclay, 2023)
La place de l'arbitrage en droit de l'investissement est discutée. Les réfutations à son encontre grandissent. De nombreuses problématiques édulcorent la définition même de la notion d'investissement. Les controverses doctrinales restent toujours nombreuses et débattues à ce sujet. De même, des doctrines s'affrontent sur la question de savoir s'il faut ou non élaborer un corps de règles cohérentes pour des sentences arbitrales homogènes. L'opposition à l'arbitrage dans le droit de l'investissement se retrouve aussi dans les problématiques liées à l'exequatur des sentences arbitrales liées à l'arbitrage d'investissement dans l'Union européenne. Un manque de soutien apparent au développement de l'arbitrage dans l'Union européenne s'est installé, comme le démontre le récent traité CETA conclu entre l'Union européenne et le Canada. L'arbitrage d'investissement ferait courir le risque d'un recul de la souveraineté. En effet, du fait l'arbitrage d'investissement, les Etats seraient moins incités à légiférer sur des matières pouvant avoir un impact sur l'activité d'une entreprise étrangère, par crainte d'une procédure arbitrale. Un lien délicat apparait alors, entre souveraineté et arbitrage d'investissement. Plusieurs doctrines se sont longtemps affrontées, notamment celle élaborée par Calvo et Drago en Amérique Latine entre 1870 et 1900, proposant de réduire les droits des investisseurs étrangers, face à une doctrine opposée, celle militant pour un standard minimum international de protection des investisseurs étrangers. Or, une renaissance de ces débats apparaît aujourd'hui, avec une problématique liée à la souveraineté de plus en plus ancrée dans les débats liés à l'arbitrage d'investissement. Pourtant, l'arbitrage d'investissement doit être perçu comme une méthode permettant à des investisseurs de bénéficier d'un arbitre indépendant et permettant de « dépolitiser » les contentieux. Mais des Etats admettent de moins en moins que leurs lois établies démocratiquement pour l'intérêt général puissent être contestées par des investisseurs étrangers devant un tribunal arbitral. Des auteurs parlent de « chilling effect », par lequel des Etats n'osent plus légiférer, par crainte de contentieux ultérieurs. De plus en plus d'Etats refusent que leur droit soit remis en cause par des juges privés. Plusieurs questions se posent. Est-il toujours concevable de protéger davantage un investisseur étranger qu'un investisseur national ? Est-il légitime de privilégier des juges privés, plutôt que des juges nationaux pour trancher les litiges en matière d'investissement ? L'utilité de l'arbitrage peut être comprise, dans des pays où la justice étatique est dite « corrompue » ou « biaisée ». En pareille situation, un investisseur étranger est légitime à vouloir saisir un arbitre neutre et indépendant. Mais la légitimité d'avoir recours à l'arbitrage dans des pays développés bénéficiant d'une justice étatique indépendante pose plus de difficultés. Dès lors, faudrait-il limiter l'arbitrage d'investissement aux pays souffrant d'un déficit d'indépendance de justice étatique ? Et donc d'exclure ce mode de règlement des litiges en la matière dans l'Union européenne ? La « politisation » du débat est en pleine renaissance. L'arbitrage d'investissement est un domaine relativement jeune et il convient de se demander s'il s'agit là d'un mode de règlement des litiges adéquat et d'un mode adapté au commerce international en général ? Assistera-t-on prochainement ou assiste-t-on déjà à ce que des auteurs qualifient de « fin de cycle » ? Il s'agit de questions ancrées dans l'actualité, que ce soit en France ou ailleurs dans le monde. The place of arbitration in investment law is discussed. The rebuttals are growing. Many issues water down the very definition of the notion of investment. The doctrinal controversies are still numerous and debated on this subject. Similarly, doctrines clash on the question of whether or not it is necessary to develop a body of coherent rules for homogeneous arbitral awards. The opposition to arbitration in investment law is also found in issues related to the exequatur of arbitral awards related to investment arbitration in the European Union. An apparent lack of support for the development of arbitration in the European Union has set in, as demonstrated by the recent CETA treaty concluded between the European Union and Canada. Investment arbitration would run the risk of a decline in sovereignty. Indeed, because of investment arbitration, States would be less encouraged to legislate on matters that could have an impact on the activity of a foreign company, because of the fear of arbitration proceedings. A delicate link then appears between sovereignty and investment arbitration. Several doctrines have long clashed, in particular the one developed by Calvo and Drago in Latin America between 1870 and 1900, proposing to reduce the rights of foreign investors, in front of an opposing doctrine, that campaigning for a minimum international standard of protection for foreign investors. A revival of these debates is appearing today, with an issue linked to sovereignty increasingly rooted in the debates linked to investment arbitration. However, investment arbitration must be seen as a method allowing investors to benefit from an independent arbitrator and allowing disputes to be “depoliticised”. But states admit less and less that their laws democratically established for the general interest can be challenged by foreign investors before an arbitration tribunal. Authors talk about the “chilling effect”, by which States no longer dare to legislate, because of the fear of subsequent litigation. More and more States refuse to have their rights challenged by private judges. Several questions arise. Is it always conceivable to protect a foreign investor more than a national investor ? Is it legitimate to favor private judges, rather than national judges, to settle investment disputes ? The usefulness of arbitration can be understood in countries where state justice is said to be “corrupt” or “biased”. In such a situation, a foreign investor is legitimate in wanting to seize a neutral and independent arbitrator. But the legitimacy of having recourse to arbitration in developed countries benefiting from independent state justice arouses more difficulties. Therefore, should investment arbitration be limited to countries suffering from a lack of independence of state justice ? And therefore to exclude this method of settling disputes in this area in the European Union ? The “politicization” of the debate is in full revival. Investment arbitration is a relatively young field and it is worth asking whether it is an adequate mode of dispute resolution and a mode suitable for international trade in general ? Will we soon witness or are we already witnessing what some authors describe as the “end of the cycle” ? These are issues rooted in the news, whether in France or elsewhere in the world.
Keywords: Arbitrage; Arbitragem; Arbitration; Contentieux; Contentieux de la concurrence; Droit de l'investissement; Droit et État; Investment Law; Investments; Litigation; Souveraineté; Sovereignty

The Pros and Cons of Third Party Funding in the International Investment Arbitration Regime - Mirveisi, Alireza; Zakerian Amiri, Mehdi; Abdollah Zadeh, Mohammad Ali (Public Law Researsh, 2023)
There is a growing stream of critics who see investment arbitration in favor of foreign investors and as a negative force as opposed to sustainable development. The phenomenon of third-party funding and its use in investment arbitration has increased such concerns. Third-party funding is basically the payment of all or a part of the arbitration costs of one of the parties of dispute by a third party funder which in return, the funder receives a percentage of the output of the award if successful. The purpose of this article is to explain and analyze the theoretical differences between pros and cons of third-party funding regarding the access to justice, screening mechanism for the claims, and the financial consequences on the host state. In this article, the advocates see third-party funding as a means of access to justice for aggrieved investors in investment claims, while the adversaries refering on the profitability of third-party funding, see this method in arbitration a form of wealth transfer from public sector to private corporations and also refer to the asymmetric structure of the investment arbitration regime as well as the risks arising from the transfer of management and control of arbitration process to the third party funders. یک جریان رو به رشدی از منتقدان وجود دارد که داوری سرمایه‌گذاری را به نفع سرمایه‌گذاران خارجی و بعنوان یک نیروی منفی در تضاد با توسعه پایدار می‌داند. پدیده تأمین مالی ثالث و بکارگیری آن در داوری سرمایه‌گذاری به این نگرانی‌ها افزوده است. تأمین مالی ثالث اساساً پرداخت تمام یا بخشی از هزینه‌های داوری یکی از طرفین دعوی توسط تأمین کننده شخص ثالث است که در ازای آن، تأمین کننده مالی درصدی از رأی صادره را در صورت پیروزی دریافت می‌نماید. هدف مقاله، تشریح و تحلیل اختلافات نظری موافقان و مخالفان تأمین مالی ثالث در خصوص دستیابی به عدالت، غربالگری دعاوی و تبعات مالی آن بر دولت است. در این مقاله موافقان، تأمین مالی ثالث را ابزاری جهت دستیابی به عدالت برای سرمایه‌گذاران زیان‌دیده در دعاوی سرمایه‌گذاری در نظر می‌گیرند در حالی که مخالفان با اتکا به اهداف سودآوری تأمین مالی ثالث، این روش را در داوری نوعی انتقال ثروت از بخش عمومی به بخش خصوصی می‌دانند و به ساختار نامتقارن رژیم داوری سرمایه‌گذاری و خطرات ناشی از انتقال مدیریت و کنترل فرایند داوری به تأمین کنندگان شخص ثالث نیز اشاره می‌نمایند.
Keywords: ACCESS TO JUSTICE; Arbitrage; Arbitragem; Arbitration; Investment Arbitration Regime; Investments; Screening Mechanism for Claims; Third Party Funding; تأمین مالی ثالث; دستیابی به عدالت; رژیم داوری سرمایه‌گذاری; غربالگری دعاوی

Investissements directs étrangers et croissance économique : une analyse empirique des données de l’Afrique des Grands Lacs - Selenge, Bienvenu Mulunda; Kasongo, Maxime Mukwamba (Repères et Perspectives Economiques, 2022)
L’objectif de cet article est d’identifier, dans le cas spécifique des pays de l’Afrique des Grands Lacs, les canaux de transmission par lesquels les flux entrants d’investissements directs étrangers (IDE) peuvent avoir une influence positive sur la croissance économique. Nous employons à la fois la méthode des moindres carrés généralisés simple (MCG) et la méthode des moindres carrés généralisés réalisables (MCGR) pour vérifier l’évidence empirique de cette relation, entre les IDE et la croissance, sur les données de la période 1970-2019. Les résultats montrent que les IDE ont un impact positif sur la croissance économique, mais qui dépend fortement de la stabilité macroéconomique. D’autre part, nous ne trouvons pas l’incidence des facteurs tels que le développement financier, l’ouverture commerciale et le capital humain comme canaux de transmission de l’effet positif des IDE sur la croissance.
Keywords: Afrique des Grands Lacs; Croissance économique; FDI; Foreign direct investment; Investissements directs étrangers; Stabilité macroéconomique

The Right to Water in Investment Treaty Arbitration and Its Impact on Jurisdiction and Applicable Law - Geravand, Farshad (Public Law Researsh, 2022)
The right to water in investment arbitration has been one of the most contentious issues before investment arbitration tribunals in recent decades. The privatization of public services, including water and sanitation, and assigning them to foreign investors has caused the right to water as a vital benefit being repeatedly raised in investment arbitrations. However, due to tribunals’ narrow interpretation of jurisdiction and applicable law, this fundamental human right has been considered irrelevant and ignored, and this has fueled the legitimacy crises in investment arbitration. This research seeks to indicate the potentiality of more protection of the right to water through balancing the states international obligations in the two areas of investment law and human rights law. Proposed methods for integrating human rights with investment law include the correct interpretation of jurisdictional clauses and the applicable law based on the treaties interpretation principles, systematic integration and the inclusion of new clauses in investment agreements. طرح حق بر آب در داوری سرمایه‌گذاری یکی از مناقشه‌انگیزترین مباحث پیش روی دیوان‌های داوری در چند دهه اخیر بوده است. خصوصی‌سازی خدمات عمومی از جمله آب و فاضلاب و سپردن آنها به سرمایه‌گذاران خارجی موجب شده تا حق بر آب بعنوان یک منفعت عمومی و حیاتی بارها در داوری‌های سرمایه‌گذاری مطرح شود. با تفسیر مضیق محاکم از شروط صلاحیتی و قانون حاکم، این حق بنیادین بشری در برخی موارد نامربوط و نادیده تلقی شده و این امر به بحران مشروعیت در داوری سرمایه‌گذاری دامن زده است. این جستار می‌کوشد تا امکان حمایت بیشتر از حق بر آب را از طریق برقراری تعادل بین تعهدات بین‌المللی دولت‌ها در دو عرصه حقوق سرمایه‌گذاری و حقوق بشر نشان دهد و در پایان روش‌هایی را برای ادغام این دو از جمله تفسیر درست شروط صلاحیتی و قانون حاکم با تکیه بر اصول تفسیر معاهدات، تلفیق سیستمیک و گنجاندن بندهای جدید در موافقتنامه‌های سرمایه‌گذاری پیشنهاد کند.
Keywords: Applicable law; International Investment Arbitration; Jurisdiction; Right to Water; Systemic Integration; تلفیق سیستمیک; حق بر آب; داوری سرمایه‌گذاری بین‌المللی; شروط صلاحیتی; قانون حاکم

La réforme du droit OHADA des investissements : une éradication des pratiques contractuelles déloyales par l’introduction d’un Acte uniforme relatif aux investissements - Dzama, Pollyana Marguerita Milaine Awé (Université de Montréal, 2022)
Cette ébauche est une contribution au développement économique des Etats d’Afrique subsaharienne, en particulier ceux membres de l’OHADA. Elle répond à une problématique qui nuit au développement économique de ces États par la voie de l’investissement : celle de la mise en place d’un système juridique africain permettant d’asseoir des règles juridiques pertinentes, fondamentales à l’encadrement du champ des investissements en Afrique. Quoiqu’il existe déjà au niveau national et communautaire africain, des législations applicables en la matière, cette étude démontre l’insuffisance de ces règles, trop promotrices des investissements, et peu protectrices de leurs enjeux, à régir comme il se doit le domaine des investissements. Cette étude est de ce fait révélatrice d’une nécessité, d’une opportunité : celle de la réforme du système juridique africain des investissements par l’instauration d’un Acte uniforme OHADA relatif aux investissements (AUI). Le dispositif normatif de cet Acte uniforme se voudra à la fois préventif et curatif des irrégularités pouvant être commises par les acteurs publics africains et leurs partenaires occidentaux dans les phases de négociation des conventions d’investissement, d’admission de l’investissement, d’exécution et d’extinction de l’activité d’investissement mais aussi protecteur des enjeux sociaux et environnementaux liés à l’exécution des projets d’investissement en Afrique. Cette réforme est également le lieu de veiller aux intérêts économiques des États africains lors des partenariats économiques conclus avec les États occidentaux et entreprises occidentales, au respect par leurs partenaires du droit interne et communautaire africain objet de la réforme mais également de protéger les investisseurs étrangers face aux actes préjudiciables émanant des acteurs publics africains. L’effectivité de telles mesures n’est possible que par l’institution d’un organe communautaire africain (la CARICI : Cour Africaine de Répression des Infractions Commises en matière d’Investissement) qui aura pour mission le suivi de l’exécution des projets d’investissements conformément aux programmes ou plans d’investissements agréés et aux dispositions juridiques qui seront établies par ledit Acte uniforme relatif aux investissements. Telles sont les suggestions émises lors de la rédaction de ce travail de recherche, qui nous l’espérons concourras à une grande avancée du droit des investissements africains et par voie de conséquence à une croissance économique fulgurante de ce continent. This study is a contribution to the economic development of sub-Saharan African states, in particular those that are members of OHADA. It responds to a problem that is detrimental to the economic development of these States through investment: that of the establishment of an African legal system making it possible to establish relevant legal rules, fundamental to the supervision of the field of investment in Africa. Although legislation already exists at the national and community level in Africa, this study shows the inadequacy of these rules, which are too promotive of investments and offer little protection to those at stake, to govern the field of investments as they should. This study is therefore indicative of a need and an opportunity: that of reforming the African legal system for investments through the introduction of an OHADA Uniform Act on Investments (UAI). The normative mechanism of this Uniform Act is intended to be both preventive and curative of irregularities that may be committed by African public actors and their Western partners in the phases of negotiation of investment agreements, admission of the investment, execution and termination of the investment activity; but also protective of the social and environmental issues related to the execution of investment projects in Africa. This reform is also the place to watch over the economic interests of African States during economic partnerships concluded with Western States and Western companies, the respect by their partners of African domestic and community law which is the subject of the reform, but also to protect foreign investors against prejudicial acts emanating from African public actors. The effectiveness of such measures is only possible through the institution of an African community body (the ACRIO: African Court of Repression of Investment Offences) which will have as its mission the monitoring of the execution of investment projects in accordance with the approved investment programmes or plans and the legal provisions which will be established by the said Uniform Act on Investments. These are the suggestions made during the drafting of this research work, which we hope will contribute to a great advance in African investment law and consequently to a dazzling economic growth of this continent.
Keywords: Acte uniforme relatif aux investissements; Droit OHADA des investissements; Investissements; Investments; Law enforcement; OHADA investment law; Pratiques contractuelles déloyales; Unfair contractual practices; Uniform Act on Investment

La mise en question de l’arbitrage d’investissement et la réforme du règlement des différends entre investisseurs et États - Sucharitkul, Vanina (Université Paris 2, 2022)
Au cours des dernières décennies, le régime de règlement des différends entre investisseurs et États (« RDIE »), par le biais de l’arbitrage ad hoc, a été l’objet d’un examen approfondi et de critiques croissantes. Au fur et à mesure que les États défendeurs de diverses régions ont perdu des affaires d’arbitrage d’investissement, ils ont été comme désenchantés par ce type de mécanisme de résolution des litiges, dans ce qui est désormais connu comme le contrecoup de l’arbitrage d’investissement. Plus récemment, ces critiques se sont intensifiées au point que l’Union Européen a remplacé le RDIE contemporain par une cour permanente d’investissement pour régler ces différends. Une approche intermédiaire de la réforme du système par l’établissement d’un organe d’appel visant à donner de la cohérence aux nombreuses sentences arbitrales ad hoc est également envisagée. Cette thèse analyse les principales critiques du système du RDIE actuel afin d’examiner sa pertinence et effectue une comparaison entre les options de réforme, la manière dont elles sont censées résoudre les défauts du système, ainsi que les implications découlant de certaines des solutions les plus débattues. L’objectif de la thèse est de faire valoir qu’une refonte radicale ou révolutionnaire du système d’arbitrage des investissements ne fera que générer des incertitudes, susciter des problèmes juridiques et pratiques très complexes, et ne n’apportera finalement pas de meilleurs résultats. L’accent devrait plutôt être mis sur une indispensable évolution ou réforme substantielle au niveau des traités, afin de tirer les leçons des cas passés et de s’assurer que la rédaction des traités répond mieux aux défis actuels. = The dispute settlement regime between investors and States through ad hoc arbitration has come under heavy scrutiny and mounting criticism in the past few decades. As respondent States in various regions have lost investment arbitration cases, those States have become disenchanted with this form of dispute resolution mechanism in what has become known as the backlash against investment arbitration. More recently, these critiques have escalated to the extent that the European Union has replaced it with a completely new scheme that includes dismantling the investment arbitration system by replacing it with a permanent investment court to settle such disputes in its trade agreement. An intermediate approach to reforming the system, the establishment of an appellate body aimed at providing consistency to the numerous ad hoc arbitration awards, is also being considered. This thesis analyses the main criticisms of the current investor-State dispute settlement (“ISDS”) system to determine its validity and carries out a comparison between the policy reform options, how they are intended to solve the system’s purported flaws, as well as the implications arising from some of the hotly debated options. The aim of the thesis is to argue that drastic overhaul or revolutionary reform to the investment arbitration system will only lead to uncertainties, more complex legal and practical problems and would not yield better results. Instead, the focus should be on the evolution of substantive reform at the treaty level, to address the lessons learned from past cases and ensure that treaty drafting responds to current day challenges.
https://assasrecherche.u-paris2.fr/ori-oai-search/notice/view/2022ASSA0095
Keywords: Appellate Mechanism; Arbitrage; Arbitrage international; Arbitragem; Arbitration; Convention CIRDI; Cour Multilatérale d’Investissement; Droit et État; Groupe de travail III de la CNUDCI; ICSID Convention; INVESTMENTS; ISDS; ISDS Reform; Incohérence de sentences arbitrales; Inconsistent Arbitral Awards; Investissements étrangers (droit international); Investisseurs et État; Investment Court System; Investor-State Dispute Settlement; Multilateral Investment Court; Mécanisme d’appel; RDIE; Règlement des différends; Règles de transparence; Réforme du RDIE; Système de Cour d’Investissement; Transparency Rules; UNCITRAL Working Group III

La négociation dans le règlement des litiges internationaux d'investissement - Paredes Balladares, Francisco Xavier (Université Paris 1, 2022)
La négociation est une institution fascinante du droit de l’investissement, polyvalente et multifonctionnelle. L’étude systématisée de la négociation dans le droit de l’investissement fait ressortir que cette institution est plus qu’un simple moyen permettant de parvenir à des accords. En réalité, la négociation est partout dans le droit de l’investissement. Il s’agit de la seule institution véritablement transversale au droit des investissements, qui intervient de nombreuses manières dans les rapports entre les investisseurs et les États d’accueil. Nous pouvons attester de l’existence des négociations avec la négociation des accords internationaux d’investissement ou de contrats d’investissement entre l’État d’accueil et l’investisseur. De surcroît, la négociation est un instrument au service de l’instance juridictionnelle qui sert aux arbitres dans l’interprétation des accords ainsi que pour la détermination de la responsabilité des parties. Si les divers rôles de la négociation dans le droit de l’investissement ont fortement contribué à l’évolution du droit international, la négociation reste une institution peu connue. Sa nature, sa portée, et son contenu juridique restent peu étudiés et non systématisés dans le droit de l’investissement. De ce fait, cette recherche offre une analyse approfondie de la négociation afin de trouver sa place dans l’ordre juridique de l’investissement (en général) et dans le règlement des litiges (en particulier). Nous examinerons dans cette recherche les nombreux apports de la négociation au droit de l’investissement permettant d’affirmer que la négociation constitue le mécanisme essentiel dans la conclusion des accords ; qu’elle impose aux parties des comportements précis ; qu’elle est un instrument qui permet aux tribunaux internationaux de déterminer la responsabilité des parties en fonction de leurs actions et inactions ; enfin, qu'elle constitue un instrument qui aide la justice arbitrale à interpréter les accords ponctuels. Ainsi, cette recherche a pour ambition de comprendre la nature, la portée et les fonctionnalités de la négociation dans le règlement des litiges transnationaux d’investissement. Negotiation is a fascinating instrument of Investment Law, versatile and rich in legal content. The systematic study of negotiation in Investment Law reveals that this institution is much more than just an instrument for reaching agreements. In fact, negotiation is everywhere. It is the only institution of Investment Law that is truly transversal, intervening in many layers of the relationship between investors and Host States. We can recognize the existence of negotiations from the very beginning of an investment process (the negotiation of a contract between the investor and the Host State), as well as negotiations over the course of the life and operation of an investment, and negotiations at the termination of a transnational investment project. Moreover, negotiation is an instrument that serves arbitral tribunal as element for the interpretation of the agreements, and the determination of the parties’ liability. The various roles of negotiation in Investment Law have certainly contributed to the evolution of international law. Nevertheless, negotiation remains an unknown institution to lawyers, regarding its nature, scope, uses and legal content. Investment law requires a thorough analysis of this institution and a structure that adapts to the transnational legal order. In this research, we will examine numerous contributions of negotiation to Investment Law: as a necessary mechanism for the conclusion of agreements that impact Investment Law; as a mandatory rule that it imposes specific behaviors on the parties in respect to the principle of good faith; as an instrument that serves international tribunals to determine the parties’ liability for their actions taken over the course of negotiations, and as an instrument to assist the justice system to construe contracts. Thus, the ambition of this research is to comprehend the nature, scope, and the features of negotiation in International Investment Law. La negociación es un instrumento fascinante de Derecho de las inversiones, a la vez versátil y rico en contenido legal. El estudio sistematizado de la negociación en el Derecho de las inversiones revela que esta institución es mucho más que un instrumento para alcanzar acuerdos. En realidad, la negociación está en todas partes en el derecho de las inversiones. Es laúnica institución verdaderamente transversal al Derecho de las inversiones, que interviene de varias formas en la relación entre inversionistas y los Estados receptores de inversión. Podemos constatar la existencia de las negociaciones desde el inicio de un proceso de inversión (en la negociación de un tratado bilateral deinversión, o de un contrato entre el inversionista y el Estado anfitrión), negociaciones durante la vida y la operación de una inversión y negociaciones encaminadas a la terminación o liquidación de la inversión transnacional. Resalta, además, que la negociación es un instrumento al servicio de la instancia jurisdiccional, que sirve a los árbitros en su tarea de interpretación de acuerdos, y a la determinación de la responsabilidad de las partes. Los diversos roles que presenta la negociación en el Derecho de las inversiones ciertamente han contribuido a la evolución del Derecho internacional. Sin embargo, la negociación sigue siendo una institución poco conocida por los juristas, especialmente en lo tocante a su naturaleza, alcance, usos y contenido legal. ElDerecho de las inversiones requiere de un análisis exhaustivo de esta institución, acompañado de una estructura que se adapte al orden legal transnacional.En esta investigación examinaremos las diversas contribuciones que hace la negociación al Derecho de las inversiones, a saber: se muestra como un mecanismoinevitable para concluir acuerdos que terminan contribuir en la evolución del Derecho de las inversiones; impone a las partes comportamientos específicos enrespeto del principio de la buena fe; es un instrumento para que los tribunales internacionales determinen la responsabilidad de las partes en razón de sus accionesdurante la fase de negociación y se constituye en un instrumento que asiste al sistema de justicia en la tarea de interpretar los acuerdos. La ambición de esta investigación no es otra cosa que comprehender la naturaleza, el alcance y la funcionalidad de la negociación en el Derecho internacional de las inversiones.
Keywords: Accord; Arbitrage; Arbitrage d'investissement; Arbitration; Bonne foi; Buena fe; Contenido jurídico; Contract interpretation; Contrahendo; Contrato; Derecho Internacional Público; Derecho de las Inversiones; Droit de l’investissement; Droit international; Duty to negotiate; Estoppel; Good faith; Interpretación de acuerdos; Interprétation de l’accord; Investissements étrangers; Investment Law; Investments; Justicia; Negociación; Negotiando; Negotiation; Negotiation agreement; Négociation; Négociations; Obligación de negociar; Obligation de négocier; Pacto de negociación; Pactum; Período de negociación; Public International Law; Transnacional; Transnational

Investment Law and its Others - Schneiderman, David (Temple International Law Journal, 2022)
Accepted: 2024-06-06T13:17:31Z

The Idea of Economic Constitution in Europe: Genealogy and Overview - Grégoire, Guillaume; Miny, Xavier (Brill, 2022)
Derrière les controverses qui jalonnent l’histoire de l’idée de Constitution économique émerge la question éminemment politique de la marge de manœuvre laissée aux autorités publiques dans la sphère économique. La notion cristallise ainsi une tension fondamentale : entre démocratie et État de droit, quel doit être modèle d’organisation et d’ordonnancement juridique de l’économie? Des physiocrates aux néolibéraux, de la République de Weimar à l’intégration européenne, des constitutions nationales à la Global Governance, cet ouvrage collectif nous invite dès lors à explorer la généalogie du concept polémique de Constitution économique. Les auteurs ouvrent alors, à travers un dialogue interdisciplinaire constant, une réflexion globale autour des enjeux juridiques et politiques du processus actuel de constitutionnalisation de l’ordre de marché en Europe.
Keywords: Constitutional Law; Economic History; History; International Law; Legal History

La mise en concurrence des systèmes juridiques nationaux et l’idée de Constitution économique - Salah, M. Mahmoud Mohamed (The Idea of Economic Constitution in Europe, 2022)
Conséquence de la compétition que les États se livrent pour attirer le maximum d’investisseurs, la mise en concurrence des systèmes juridiques nationaux s’est traduite par une libéralisation continue du droit qui a eu un effet direct sur l’idée de Constitution économique. Celle-ci a non seulement vu son épaisseur normative se renforcer du fait de la neutralisation des dispositifs juridiques dirigistes mais elle s’est également universalisée en raison de la conversion de la quasi-totalité des pays au dogme de « l’attractivité ». Toutefois, ce mouvement généralisé vers le tout libéral commence à être remis en cause sous l’effet de facteurs divers qui se traduisent par une demande sociale et politique pour plus de régulation étatique. Il en résulte à la fois un regain de l’unilatéralisme qui affecte la force des principes qui sous-tendent l’idée de constitution économique et une prise en compte plus affirmée des valeurs et intérêts collectifs qui altère la substance de ces principes.
Section: The Idea of Economic Constitution in Europe
Keywords: Constitutional Law; Economic History; History; International Law; Legal History

Role of Abuse of Rights Doctrine and Investment Arbitration Ratione Temporis in Limiting Nationality Planning - Saeedi, Niloofar; Askary, Pouria (Public Law Researsh, 2022)
Sometimes foreign investors after the dispute have arisen or when it is predictable and with the intention of bringing the dispute to arbitration, change their nationality or acquire new nationality. The phenomenon called Nationality Planning eases foreign investors’ access to a desirable treaty and increases the chance of bringing disputes against host states.So host states try to avoid these disputes by raising objections to Ratione Temporis or claiming abuse of rights. Arbitration tribunals’ approach towards their Ratione Temporis and abuse of rights is material in host states’ success in limiting Nationality Planning. So the question to be answered is that what requirements are considered by arbitrations in determining Ratione Temporis and abuse of rights and how these two are different. Arbitral precedent shows that these tribunals make distinction between cases of nationality planning contrary to their Ratione Temporis and cases that are considered as abuse of rights. However, in practice their strict approach results in limited acceptation of objections to Ratione Temporis or abuse of rights claims. گاه سرمایه‌گذار خارجی پس از بروز اختلاف یا زمانی که اختلاف قابل پیش‌بینی است و به قصد طرح دعوی در مرجع داوری، اقدام به تغییر تابعیت یا کسب تابعیت جدید می‌نماید. این اقدام که برنامه‌ریزی تابعیت نام دارد، دسترسی سرمایه‌گذار خارجی به یک معاهده سرمایه‌گذاری مطلوب را تسهیل کرده و احتمال طرح دعوی علیه دولت میزبان را افزایش می‌دهد. از این‌رو دولت‌های میزبان تلاش می‌کنند با طرح ایراد به صلاحیت زمانی یا سوء استفاده از حق، مانع پذیرش چنین دعوایی شوند. رویکرد مراجع داوری در احراز صلاحیت زمانی خود و تشخیص موارد سوء استفاده از حق، در موفقیت یا عدم موفقیت دولت میزبان در مقابله با برنامه‌ریزی تابعیت تعیین‌کننده است. بنابراین باید به این پرسش پرداخته شود که مراجع داوری چه شرایطی را برای احراز صلاحیت زمانی و سوء استفاده از حق در نظر می‌گیرند و چگونه میان این دو تمایز قائل می‌شوند. رویه مراجع داوری حاکی از آن است که این مراجع میان مواردی از برنامه‌ریزی تابعیت که مانع صلاحیت زمانی آن‌هاست و مواردی که سوء استفاده از حق تلقی می‌گردد، تمایز قائل می‌شوند. هرچند رویکرد سخت‌گیرانه آنها در عمل موجب می‌شود تنها در موارد محدودی ایراد به صلاحیت زمانی یا ادعای سوء استفاده از حق مورد پذیرش واقع شود.
Keywords: Abuse of rights; Bilateral Investment Treaty; Foreign Investment Arbitration; Nationality Planning; Ratione Temporis; برنامه‌ریزی تابعیت; داوری سرمایه‌گذاری خارجی; سوء استفاده از حق; صلاحیت زمانی; معاهده دوجانبه سرمایه‌گذاری

Scope of Obligation of the Host State for Protection of Foreign Investor in Armed Conflicts - Shahbazian, Abolghasem; Salimi, Sadegh (Public Law Researsh, 2022)
Measures taken by governments during armed conflict to safeguard their essential interests sometimes cause damages to foreign investors. The investors thus affected seek remedies in the arbitration tribunals invoking breach of host government obligations to protect investments. The host government also usually attempts to assert as defense non-precluded measures to prove its irresponsibility, or if it proves responsible, justify it by resorting to circumstances precluding wrongfulness in the customary international law. But since different courts do not consider the same requirements to invoke these rules, there is no certainty that the parties to the lawsuit will be able to invoke them and, as a result, the scope of government's obligations to protect the foreign investor during the armed conflict is obscure. To clarify the scope of the host government's obligations to protect the foreign investor during armed conflicts and balance the interests of the investor and the host government during the investment disputes arising from the armed conflict, this article explores the possibility and requirements of invoking circumstances precluding wrongfulness and non-precluded measures and the relationship between them. اقداماتی که دولت‌ها در زمان مخاصمات مسلحانه در جهت حفظ منافع اساسی خود انجام می‌دهند گاه موجب ورود خسارت به سرمایه‌گذاران خارجی می‌گردد. سرمایه‌گذاران آسیب‌دیده در محاکم داوری با استناد به نقض تعهدات حمایتی توسط دولت میزبان، خسارات وارده به خود را طلب می‌نمایند. دولت میزبان نیز معمولاً برای اثبات عدم مسئولیت خود به شرط اقدامات منع نشده مندرج در معاهده سرمایه‌گذاری استناد می‌کند و یا در صورت اثبات مسئولیت، به منظور توجیه آن به معاذیر رافع وصف متخلفانه در حقوق بین‌الملل عرفی متوسل می‌شود. اما از آنجا که محاکم مختلف، شرایط یکسانی را جهت استناد کشور میزبان به شرط اقدامات منع نشده و معاذیر رافع وصف متخلفانه در نظر نمی‌گیرند، قطعیتی در امکان استناد به آن‌ها وجود ندارد. در نتیجه، قلمرو تعهد دولت به حمایت از سرمایه‌گذار خارجی در زمان مخاصمات مسلحانه در هاله‌ای از ابهام فرو رفته است. این مقاله با هدف روشن ساختن قلمرو تعهد دولت میزبان به حفاظت از سرمایه‌گذار خارجی در هنگام مخاصمات مسلحانه و به منظور توازن منافع سرمایه‌گذار و دولت میزبان در دعاوی سرمایه‌گذاری ناشی از مخاصمات مسلحانه، امکان و الزامات استناد کشور میزبان به معاذیر عرفی رافع وصف متخلفانه و شرط اقدامات منع نشده و ارتباط میان آنها را مشخص می‌نماید
Keywords: Armed Conflicts; Customary International Law; Foreign investment; Interests of the Host State; Non-Precluded Measures; اقدامات منع نشده; حقوق بین‌الملل عرفی; سرمایه‌گذاری خارجی; مخاصمات مسلحانه; منافع دولت میزبان

Contract Interpretation in Investment Treaty Arbitration: A Theory of the Incidental Issue - Chernykh, Yuliya (Brill, 2022)
For the first time, a monograph provides a systematic, in-depth account of contract interpretation in investment treaty arbitration and offers a conceptual paradigm that would enhance the quality of the tribunals’ reasoning.; Readership: The monograph is of relevance for legal scholars, practitioners and policymakers in the field of investment treaty arbitration. The book will also be of additional value to postgraduate and doctoral students.
Accepted: 2022-04-07T09:15:30Z
Keywords: Arbitrage; Arbitragem; Arbitration; Contract interpretation; International law; Investment arbitration; Investments

Bank Bail-ins in International Investment Law - Duque-Cordero, Luciano (Universität Wien, 2022)
The global financial crisis led to the introduction of special resolution regimes for financial institutions. The most prominent innovation of these resolution regimes is the so-called bail-in tool, which allows regulators to recapitalise financial institutions by expropriating shareholders and creditors. This thesis analyses the conditions under which a hypothetical bail-in of a financial institution would constitute a compensable breach of international investment law. It identifies the issues that are most likely to be relevant if a bail-in were to be litigated before an investment arbitration tribunal. The thesis first addresses jurisdictional issues, in particular the question of whether bail-inable instruments can even be considered an investment in procedural terms. The analysis then continues to substantive standards of protection. It deals comprehensively with the question of expropriation and related issues such as compensation, the right to regulate, and causation. It concludes with possible violations of the fair and equitable treatment standard.
https://phaidra.univie.ac.at/detail/o:1417287
Keywords: Bail-in; Bank resolution; Expropriation; International Investment Law; Investments

Paradigm Shift in Investment Treaty Arbitration: Toward Stricter Control over the Qualifications and Conduct of Arbitrators - Kamalinejad, Hassan (University of Victoria, 2022)
There is a growing concern over the qualifications and social interactions of investment treaty arbitrators. The characteristics of this class of international adjudicators have significantly evolved over the past few decades. The contemporary arbitration panelist interacts within a broad and complex network of arbitration participants. Their patterns of social behavior both within the community of panelists and within the broader network of actors in arbitration proceedings have fundamentally reshaped the composition, dynamics and culture of the arbitration community. These new forms of relationships and patterns of conduct are new in the context of public international law. These have created unprecedented challenges to the investment treaty arbitration system. New manifestations of attributes and social behavior of panelists demonstrate inadequacies of the existing standards, rules and procedures that govern panelists. This study surveys problematic patterns of social behavior of investment treaty adjudicators and shows how certain instances of social behavior inevitably or potentially jeopardize the very foundations of the system. This research empirically examines the voting behavior of two distinct groups of party-appointed panelists, and the results reveal a relationship between appointments and the decision-making attitude of adjudicators. It further methodically maps the pool of ICSID panelists and answers the question ‘who are ICSID panelists?’ It reviews the evolution of the attributes of ICSID adjudicators, assesses the composition of the ICSID pool, and evaluates the social interactions of this group of investment treaty adjudicators. To address the challenges that investment treaty arbitration faces, a radical and multidimensional shift is occurring in the system. This transformation is directed towards greater control over the qualifications and conduct of adjudicators. These developments reconstruct the composition of the pool of adjudicators and influence how they interact with other actors in investment treaty arbitration proceedings. The ongoing reform progress indicates that the attributes and behavior of future investment treaty adjudicators would likely be different from the characteristics and conduct of the contemporary generation of panelists.
URI: http://hdl.handle.net/1828/14772
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Code of conduct; ICSID; Impartiality; Investment treaties; Investment treaty arbitration; Investments; Permanent court system; Qualifications; State practice

L'équilibre des intérêts en droit international des investissements : principe général de droit applicable aux rapports entre investissement et environnement - Mekpo, Cosme Gosshé (Université Laval, 2022)
Avec la résurgence des problèmes environnementaux, le droit international des investissements se retrouve aujourd'hui face à l'urgence de sa propre réadaptation. Et, comme réponse unique à un impératif catégorique, l'équilibre des intérêts émerge en tant qu'un principe général de droit (PGD), de nature souple et autonome, à qui ses diverses fonctions (logique, axiologique, unificatrice et correctrice) confèrent une utilité opérationnelle au sein de l'ordre juridique international, et dont la mise en œuvre en droit international des investissements est l'expression de la dimension évolutive. En tant que principe référentiel, il est consubstantiel au droit international des investissements et vise à faire prévaloir un idéal normatif (le droit de l'équilibre) sur un autre (le droit de la protection). Toutefois, l'aporie de l'équilibre des intérêts est d'être, à la fois, une affirmation du principe de la souveraineté réglementaire et une limitation de celui-ci. Dans un premier temps, sa mise en œuvre se traduit par la prise en compte de l'intérêt général dans le balancier état-investisseur et, dans un second temps, cette exigence ne se concrétise qu'au bout d'un double test de la proportionnalité et du raisonnable. Alors que sa source de régénération par rapport au reste du système est la protection internationale des valeurs fondamentales et socio-environnementales, sa structure de base demeure le couple droit-obligation et s'apparente à une transversalité normative qui combine à la fois la lex lata et la lex ferenda d'une part, la soft law et la hard law d'autre part. Malgré sa fécondité croissante, il est possible de le décrire comme étant la source d'un droit poly-normatif et « open-textured » qui possède à la fois un noyau d'applicabilité, une teneur variable et une juridicité foisonnante. Le profil abrégé de cette construction normative pourrait alors se matérialiser en droit international des investissements par: la prise en compte de l'intérêt général, la responsabilité sociale des entreprises multinationales, la réciprocité par équivalence des droits et obligations des parties, la flexibilité réglementaire et la compatibilité d'avec les autres normes de protection internationales.
Keywords: Dommages à l'environnement; Investissements; Investissements étrangers (environnement); Investments; Responsabilité Sociale de l'Entreprise

Articulating clearer fair and equitable treatment clauses within Tanzania’s international investment agreements: correcting the disparity between host state and international investor interests - Ntangeki, Joanitha (Canterbury Christ Church University, 2022)
International Investment Agreements seek to promote foreign investment whilst protecting foreign investors. Despite the goal of International Investment Agreements being to secure parity between the interests of the host State and the foreign investor, there has been consequential disparity in the protection of the interests of both parties. Notably, the host State is susceptible to disadvantage. This research examines the extent to which International Investment Agreements in Tanzania have facilitated this disparity. In particular, the research evaluates the inclusion of fair and equitable treatment provisions in Tanzania’s International Investment Agreements and the extent to which fair and equitable treatment provisions have in some way facilitated this disparity. The research examines systematically the fair and equitable treatment provisions contained in twenty IIAs signed by Tanzania between 1965 and 2013 (eleven of which are still in force). The research takes a comparative approach in evaluating and contrasting the Tanzanian provisions with other fair and equitable treatment clauses in IIAs signed by India, Morocco and the Netherland. The Tanzanian provisions are vague and non-uniform in comparison. The research is situated in the broader context of national sovereignty and the relationship between Tanzania and its foreign investors under international law. The substance of the analysis centres on foreign investors in the mining sector in Tanzania and the extent to which these investors have sought to take advantage of the fair and equitable treatment clauses in the IIAs in order to pursue their activities to the detriment of local populations. The research evidences the negative impact of their claims that changes in government policy (often aimed at benefiting citizens) amount to unfair treatment of the foreign investor. This has a significant impact on the ability of the government to develop its policies around sustainable development, environmental protection and the guarantee of human rights of the citizens of the host State. The research demonstrates that a clearer and fuller articulation of fair and equitable treatment clauses within Tanzania’s IIAs can act as a corrective to the disparity between the host State and the international investor. This requires that IIAs are drafted to include an exhaustive and full list of the State’s obligations towards the foreign investor so as to limit foreign investor claims against the host State. The impact of not doing so has grave implications for the rights of the citizens of Tanzania and unnecessarily tips the balance of power in favour of the foreign investor and away from the host State. This undermines the ability of the host State to assert its sovereignty within its own borders.
Permalink: https://repository.canterbury.ac.uk/item/9714v/articulating-clearer-fair-and-equitable-treatment-clauses-within-tanzania-s-international-investment-agreements-correcting-the-disparity-between-host-state-and-international-investor-interests
Keywords: Foreign investment; International investment; Investor interest; Tanzania

Investissement et propriété intellectuelle - Dépinoy, Anaïs (Université de Lille, 2021)
La thèse porte sur les rapports entre l’investissement dans la conception d’objets immatériels et la propriété intellectuelle. Elle interroge la vocation du droit de la propriété intellectuelle à la protection d’un tel investissement. À l’examen du droit positif, il n’est pas aisé d’identifier une réponse claire à cette question.L’existence de la protection est incertaine, alors même que la technique employée est adéquate. Discutée, elle mérite d’être repensée. Son avenir dépend par ailleurs de son caractère souhaitable, et donc de sa légitimité. Aussi, pour être effective, la protection doit faire l’objet d’un choix politique de société. Proposantune lecture de la propriété intellectuelle sous l’angle de sa finalité de protection de l’investissement, l’étude est menée à l’appui de la construction d’un concept juridique d’investissements immatériels. Celle-ci permet de présenter le sujet et ses problématiques de façon renouvelée, afin de dépasser les difficultés. Le résultat de l’exercice de conceptualisation, conjugué à un exercice de classification juridique de la réalité, sert de base à un essai de reconstruction prospective du système juridique de la propriété intellectuelle. Les catégories, qualifications et régimes de ce dernier sont réaménagés, pour le faire évoluer en équilibre et cohérence, vers une fonction assumée de protection de l’investissement. L’enjeu est d’aboutir à un système de protection légitime, sécurisant et fidèle à la réalité et ses attentes.
Keywords: Capital immatériel; Concept; Droit subjectif; Economic efficiency; Efficacité économique; Industrial property; Intellectual property; Investissements; Investissements immatériels; Investments; Literary and artistic property; Profitability; Propriedade intelectual; Propriété industrielle; Propriété intellectuelle; Propriété intellectuelle (droit international); Propriété littéraire et artistique; Qualification; Rentabilité; Reservation; Risk; Risque; Régime; Réservation; Social values; Subjective right; Valeurs sociales

Legal Guide on Agricultural Land Investment Contracts - UNIDROIT; IFAD (UNIDROIT/IFAD, 2021)

Compensation for Regulatory Expropriation in International Investment Law - Khachvani, David (Université de Genève, 2021)
The States, international organizations and interest groups are increasingly concerned with treaty claims of foreign investors, who sometimes seek compensation for the States' legitimate regulatory measures, such as tobacco plain packaging, nuclear energy phase out and environmental regulations. International investment law has yet to develop a comprehensive and predictable framework addressing some of the basis questions related to compensability of legitimate regulatory measures. The thesis carries out a comparative legal analysis to identify the key features of the prohibition of uncompensated expropriation as a general principle of law, and explores the rationale of that principle in political philosophy. Equipped with the results of this analysis, it proceeds to propose an analytical approach addressing practical questions related to the compensatory protection of foreign investments.
Keywords: Climate Change; Compensation; Expropriation; Investments; Police Powers; Regulatory Powers

Legal Protection of Foreign Direct Investment in the OHADA Area - Ngoya, Dominique (Social Science Research Network, 2021)
This paper analyzes the protection of Foreign Direct Investments in the OHADA area, specifically, its regulation by the Treaty of Organization and Harmonization in Africa of Business Law (OHADA Treaty). It is to restore legal and judicial security within their scope that OHADA member countries have undertaken to harmonize and unify their economic sector legislation to attract foreign investment as a factor in economic development. Several national and international legal instruments are responsible for the protection of foreign direct investment in OHADA countries. Indeed, the volume of foreign direct investment (FDI) to developing countries increased considerably during the 1990s; As Africa is now one of the favorite destinations for Western and even African investors, it is becoming a very profitable continent for investors. However, the issue of regulating or securing foreign investment in African countries is still flawed. The establishment of OHADA, in a way, is in the same direction; if we stick to the purpose of the organization prescribed in paragraph 5 of the preamble to the OHADA Treaty, which states that the purpose of the OHADA law is to "promote the growth of economic activity and encourage investment." Unfortunately, this objective remains only an announcement of the preamble to the Treaty, because of the definition of business law given by Article 2 of that treaty. However, the list of subjects is not exhaustive, investment remains absent. Thus, foreign investment is not regulated by the OHADA Treaty, so even investment-related activities are held by other subjects (corporate law, commercial law, and security law). The omission of FDI in the scope of the OHADA Treaty leads us to raise the question of its regulation.This work proposes a reflection that the OHADA Treaty should be modernized through reform including investment and many other issues to deal effectively with the issue of foreign investment given the ineffectiveness of national and sub-regional instruments in this area.
Keywords: Foreign direct investment; Investment Law; Investment Protection; OHADA

The Relationship between International and Domestic Law in the Field of Attribution of Responsibility to a State in International Investment Disputes - Amidimehr, Elham; Seifi, Jamal (Public Law Researsh, 2021)
The attributability of actions to states within the context of investment treaty disputes and to focus on the roles played by international and domestic laws in such attributions have caught the attention of jurists in recent years. The ILC Draft Articles on Responsibility of States for Internationally Wrongful Acts, and particularly, article 3 points to the main outcome of this debate, where it does not consider domestic law irrelevant in internationally wrongful acts and stipulates that the issue is subject to international law and it will take into account the relevance of domestic law. Thus, although the characterization of an act of a State as internationally wrongful is an independent function of international law and such characterization is not affected by the characterization of the same act as lawful by domestic law, it does not mean that domestic law is irrelevant to such description; on the contrary, it may be related in various ways. The present article attempts to examine the challenging junction of domestic and international law with regard to the attributability of actions taken within the framework of investment treaties, specifically by state-owned and para-statal entities that exercise elements of state authority. قابلیت انتساب عمل به دولت در چارچوب اختلافات معاهده‌ سرمایه‌گذاری و تمرکز بر نقش‌هایی که حقوق بین‌الملل و حقوق داخلی در چنین انتسابی ایفا ‌می‌نمایند در زمره‌ مباحثی است که در سال‌های اخیر بسیار مورد ‌توجه حقوقدانان بوده و ماده 3 مواد کمیسیون حقوق بین‌الملل در ارتباط با مسئولیت دولت‌ها نیز بیانگر پیامد اصلی این بحث است که فی‌الواقع، حقوق داخلی را با مسأله متخلفانه بودن اعمال از حیث بین‌المللی بی‌ارتباط تلقی ‌ننموده، بلکه مقرر ‌می‌دارد مسئله مورد بحث، تابع حقوق بین‌الملل است لیکن حقوق بین‌الملل نیز خود تا حدِ ارتباط، حقوق داخلی را در نظر خواهد گرفت. بنابراین اگرچه توصیف خصوصیات یک عمل به عنوان عملی غیرقانونی از عملکردهای مستقل حقوق بین‌الملل است که تحت ‌تأثیر توصیف خصوصیات این عمل بموجب حقوق داخلی قرار نمی‌گیرد لیکن این گفته بدین معنی نیست که حقوق داخلی با توصیف عمل متخلفانه‌ بین‌المللی بی‌ارتباط ‌است؛ بالعکس، ممکن ‌است به طرق مختلفی به آن مرتبط‌ باشد. در این مقاله سعی بر‌ آن است که تلاقی چالش‌برانگیز حقوق داخلی و حقوق بین‌الملل در بحث قابلیت انتساب اعمال ‌صورت ‌گرفته در چارچوب معاهدات سرمایه‌گذاری توسط ارگان‌های دولتی و نهادهای نیمه‌دولتی که عناصر اختیارات دولتی را اعمال می‌نمایند مورد واکاوی قرار‌ گیرد.
Keywords: Attribution; Domestic Law; International Arbitration; International Investment Treaties; International Law; حقوق بین‌الملل; حقوق داخلی; داوری بین‌المللی; معاهدات سرمایه‌گذاری بین‌المللی; کلیدواژگان انتساب مسئولیت

A Reflection on the Invalidation of Patents in the Light of Constituent Elements of Indirect Expropriation under Foreign Investment Law - Rahbari, Ebrahim; Shahabi, Mahdi; Falahati, Soroosh (Public Law Researsh, 2021)
Patents are considered as investments protected under the International Investment Law. Although, these properties are protected under the principle of territoriality, similar to other investments, they can be expropriated as a result of host states’ regulatory measures inconsistent with protection standards stemming from foreign investment protection regulations and treaties including fair and equitable treatment and legitimate expectations of foreign investors. Considering the fact that few arbitration awards have been issued by arbitration panels in this regard, it is yet difficult to claim there is a strong precedent in International Investment Law. Nevertheless, reflecting the provisions of international regulations, the stance of the domestic law and the most important relevant case, this article provides the most significant elements of indirect expropriation as well as existing doctrines in this respect and further investigates whether invalidation of patents can amount to indirect expropriation. It will also be mentioned that despite the fact that according to several foreign investment protection treaties, invalidation of patents shall not be subject to regulations regarding indirect or creeping expropriation, the final determination lies with the arbitration panel. یکی از مصادیق سرمایه‌گذاری خارجی مورد حمایت در حقوق بین‌الملل سرمایه‌گذاری، اختراعات است. این دسته از دارایی‌ها علی‌رغم به رسمیت شناخته شدن در پرتو اصل سرزمینی بودن حمایت، همانند سایر سرمایه‌گذاری‌ها می‌توانند تحت تدابیر حاکمیتی دول میزبان که مغایر با استانداردهای حمایتی نشأت گرفته از قوانین و معاهدات بین‌المللی حمایت از سرمایه‌گذاری خارجی همچون شرط رفتار عادلانه و منصفانه و صیانت از انتظارات مشروع و معقول سرمایه‌گذار می‌باشند، با خطراتی همچون سلب مالکیت مواجه شوند. نظر به صدور آرای معدود مراجع بین‌المللی در این خصوص، سخن گفتن از شکل‌گیری رویه‌ای متقن در این راستا دشوار می‌باشد. با این حال، در این نوشتار ضمن بررسی مهمترین عناصر متشکله سلب مالکیت غیرمستقیم و دکترین‌های موجود در این زمینه، به بررسی قابلیت تطبیق ابطال گواهی ثبت اختراع با سلب مالکیت غیرمستقیم پرداخته و با تشریح مقررات برخی اسناد بین‌المللی، موضع حقوق داخلی و مهم‌ترین پرونده مربوط به این موضوع در حقوق سرمایه‌گذاری خارجی در ابعاد گوناگون آن مداقه نموده و در نهایت به این نتیجه خواهیم رسید که حتی در صورت مستثنی نمودن ابطال گواهی ثبت اختراع از مقررات مربوط به سلب مالکیت در معاهدات حمایت از سرمایه‌گذاری خارجی، تشخیص نهایی تحقق سلب مالکیت با دیوان داوری است.
Keywords: Elements of indirect expropriation; Foreign investment; Indirect expropriation; Intellectual property; Invalidation of patents; ابطال گواهی ثبت اختراع; حقوق مالکیت فکری; سرمایه‌گذاری خارجی; سلب مالکیت غیرمستقیم; عناصر سلب مالکیت غیرمستقیم

El principio de proporcionalidad en el derecho international económico - Reyes Sarmiento, Lina (Université Paris 10, 2021)
Le principe de proportionnalité a été récemment reconnu dans les traités et les accords internationaux du commerce et des investissements avec l’État. Cependant, peu d'études se concentrent sur la nature juridique, le contenu, la portée et les fonctions de ce principe dans le droit économique international. Cette thèse présente une analyse actuelle et détaillée sur ces questions.
Cotutelle avec : Université Autonome de Barcelone
Keywords: Arbitrage international; Arbitraje internacional; Dispute resolution; Droit international économique; International Arbitration; Inversiones; Investissements; Investments; OMC; Principes; Principios; Principles; Proporcionalidad; Proportionality; Proportionnalité; Proportionnalité (droit); Règlement des différends; Solucion de diferencias; WTO

Vers la mise en place d’une zone d’investissement commune au sein de la Zone de libre-échange continentale africaine : uniformiser les conditions régissant les investissements intra-africains - Commission Économique Pour l'Afrique (Nations Unies, 2021)
Le présent rapport prône l’adoption de mesures de lutte contre la COVID concernant tout particulièrement la politique d’investissement soutenue par l’Accord portant création de la Zone de libre-échange continentale africaine afin de préserver les acquis du marché commun pour les entreprises et les citoyens africains et d’accroître les avantages en découlant. La Zone de libre-échange continentale africaine (ZLECAf) contribuera à générer les ressources financières nécessaires au développement économique de l’Afrique. Elle a pour objet de mettre en place un marché africain intégré où les biens, les personnes, les services et les capitaux circulent librement, complétant les efforts d’intégration régionale au profit des 1,3 milliard d’habitants du continent. Le produit intérieur brut combiné du marché de la ZLECAf est de 2 500 milliards de dollars. Elle a officiellement vu le jour le 21 mars 2018 à Kigali, date à laquelle 44 États membres de l’Union africaine ont signé l’Accord portant création de la Zone de libre-échange continentale africaine. L’Accord est entré en vigueur le 30 mai 2019 après le dépôt de l’instrument de ratification par le 22ème État membre de l’UA. La ZLECAf est entrée dans sa phase opérationnelle en juillet 2019. Les échanges régis par les règles de la ZLECAf ont débuté le 1er janvier 2021.

The conflict of jurisdiction between intra-EU BITs and European law: proposal for an EU investment court - Lewis, Krystle (Canterbury Christ Church University, 2021)
This work aims to find a practical solution to the problem that exists between intra-EU Bilateral Investment Treaties (BITs) and European Union (EU) law over conflict of jurisdiction issues. Currently, there is a problem as the EU Commission has rendered intra-EU BITs incompatible with EU law. This work argues that the current conflict of jurisdictional problems within investment agreements can be overcome by the creation of an EU investment court. The reliance on this court for the resolution of this conflict, as opposed to private law mechanisms, is important as it is the way forward in handling the conflict of jurisdiction issue at its best. This work argues that an EU investment court will be a panacea to the current problems concerning the conflict of jurisdiction. These problems will be presented through a positivist method where the law is analysed in its current form, highlighting its current weaknesses and resolving these weaknesses by proposing recommendations for such a court through a comparative examination of other international courts that fulfil a similar dispute resolution function, namely the Organisation for the Harmonisation of Business Law in Africa (OHADA) and the Unified Patent Court (UPC) and the World Trade Organisation (WTO). The purpose of this work is manifold. The work will provide an analytical examination of the relationship between EU law and international obligations within intra-EU BITs. It will further explore and assess the viability of a range of alternative solutions to intra EU BITs enforcement within the EU. It will additionally examine the operation of the OHADA, the UPC and the WTO to inform the proposal of an EU investment court. This is important as the outcome of these examinations will support the argument made in this thesis. It will also impact dispute resolution beyond academia by providing a practical solution to alleviate the current challenges with intra-EU BITs. The recommendations thus can inform changes for lex ferenda.
Permalink: https://repository.canterbury.ac.uk/item/94574/the-conflict-of-jurisdiction-between-intra-eu-bits-and-european-law-proposal-for-an-eu-investment-cour
Keywords: Bilateral Investment Treaties (BITs); Investissements; Investments

Challenges for Responsible Investment in the retirement benefits sector of Kenya - Mathenge, Elizabeth (Victoria University of Wellington, 2021)
Responsible investment (RI) is the investment strategy that incorporates environmental, social and governance (ESG) factors into the investment decision-making process (Hebb, Hawley, Hoepner, Neher, & Wood, 2015). RI has shifted from what was considered a niche market to become one of the fastest-growing areas of finance in many parts of the world (PRI, 2019b). However, a closer look at the development of RI and adoption rates in countries and regions reveals that RI is not commonly practised in sub-Sahara Africa (except for South Africa). This study explores the critical challenges for RI development in the retirement benefits sector of Kenya and, by engaging with a variety of key stakeholders, proposes how to overcome the identified challenges. It contributes to the literature on challenges for RI in a developing country by offering an in-depth case study of the retirement benefits sector.My study employs qualitative methods to collect and analyse data collected from semi-structured interviews with 22 participants (asset managers, regulators and capital market experts, and a council member of the Association of Retirement Benefits Schemes of Kenya) as well as a collection of published documents by government agencies in Kenya. Also, I analysed 10 annual reports to assess the kind of ESG information that is disclosed by listed companies. My study explores, in particular, how actors in the retirement benefits sector conceptualise RI. It identifies the leading ESG factors in Kenya and draws on the business-case approach to RI to explore whether the participants consider those factors as material risk factors that present both risks and opportunities to the investment decision-making process. Further, my study identifies the specific barriers for RI development and proposes how to overcome them. The findings show that participants define RI using several terminologies. This is consistent with the existing literature. My study finds that all participants consider corporate governance as a material risk factor that can impact the financial returns of a portfolio. However, most of the asset managers do not think that the environmental and social factors can present material risk factors to their investment decision-making process. Although over a third of the asset managers recognise that the environmental and social issues in Kenya present business opportunities to retirement benefits schemes, there is a shortage of well-structured assets in those areas. Further, this study identifies five specific barriers for RI development: diversification challenges; a lack of ESG data; a lack of demand/incentives; short-termism; and the demand for high financial returns and a lack of awareness and expert knowledge of RI practices. My study recommends that the National Treasury of Kenya develops RI policy for the entire finance sector. In addition, the findings support a recommendation for the Capital Markets Authority and the Retirement Benefits Authority to embark on capacity building programmes to educate the actors in the finance sector on RI strategies and to create awareness of the impact of ESG on financial returns in the long run.
Keywords: Investment and Risk Management; Kenya; Responsible investment; Retirement benefits schemes

OHADA bölgesinde yabancı yatırımlara ilişkin hukuki sorunlar « Türk hukuku ile karşılaştırmalı olarak » - Useni, Ahmed Emedi (İstanbul Ticaret Üniversitesi, 2021)
OHADA bölgesindeki yabancı yatırımların yasal korunması bahassederken yasal mekanizmaların varlığı fikrine atıfta bulunur. Yabancı yatırımlarının korunmasının sağlanması Bu Örgüte üye olmayan ülkelerin vatandaşları. Mukayese arama sürecinde Türk hukuku ile anlayışlı olmalıdır. Bu yatırımlar için optimal yasal güvenlik modeli olmalidir çünkü OHADA yasa nispeten yeni ve yapım aşamasındadır. Talking about the legal protection of foreign investments in the OHADA zone inevitably refers to the idea of the existence of legal mechanisms capable of ensuring the protection of investments of economic operators who are nationals of non-member countries of this Organization. The comparison with Turkish law must to be understanding in the process of seeking the model of optimal legal security for these investments, because the OHADA law remains relatively new and under construction.
https://tez.yok.gov.tr/UlusalTezMerkezi/TezGoster?key=tqUiYt63sTQLTpozMJ92QppmfBTCxeWntSm8WuGV7UbfQesqsfYTJBeuQ5wKcBdH
Keywords: Company law; Comparative law; Foreign capital investments; Hukuksal korunma; Investissement étranger; Investments; Karşılaştırmalı hukuk; Legal protection; Organization for the Harmonization of African Business Law; Ticaret Kanunu Uyum Örgütü; Turkish law; Türk hukuku; Yabancı sermaye yatırımları; Şirketler hukuku

Improving international investment law’s treatment of (anti-)corruption: Towards a more balanced approach - Yan, Yueming (McGill University, 2021)
In recent years, investment arbitration tribunals are increasingly confronted with allegations of corruption, mostly invoked by host States as a defense to investors’ claims. After an affirmative finding of an alleged corrupt act between the investor and a public official of the host State in the establishment or conduct of the investment, tribunals have adopted a binary approach to the issue – if they uphold allegations of corruption, they completely dismiss the investor’s submissions. This binary approach has resulted in an asymmetry of liability for the two parties to a corrupt act (i.e., investors and host States/host State officials), failing to take into account the inherent bilateralism of corruption and the fact that domestic laws and international norms have outlawed both the act of offering and of accepting bribes. In particular, public officials’ free participation in a corrupt act to advance investments is attributable to the host State and requires State responsibility under international law. Moreover, the increasingly prevalent practice of inserting anti-corruption provisions in investment treaties has reinforced this lop-sided feature, as well as offering only weak effectiveness in terms of deterring corruption. After a careful examination of the treatment of corruption issues in investment arbitration and investment treaties, this thesis proposes a paradigm shift from the current asymmetric approach to a more balanced approach. It calls on investment tribunals to take a dual-track approach that investigates both corruption and investors’ claims, and ensures that each party assumes responsibility for its own misconduct. It also proposes that treaty drafters include anti-corruption provisions that impose strong obligations of anti-corruption on both sides of corruption (i.e., investors and host States) rather than merely on a single party to it
https://escholarship.mcgill.ca/concern/theses/5q47rt984
Keywords: Anti-Corruption Law; Investment arbitration; Investment treaty; Investments

Legalization through adjudication: The case of investor-state dispute settlement - Yu, Chen (McGill University, 2021)
The reform of the Investor-State Dispute Settlement (ISDS) mechanism has provoked much debate among legal scholars and practitioners. The critiques of ISDS mainly arise from concerns regarding the legitimacy of the mechanism such as the perceived tolerance for the lack of impartiality and consistency. To allay these concerns, there have been proposals to reform ISDS by establishing investment courts with tenured judges and appellate tribunals. However, international adjudication systems like ISDS cannot be fully analogized to domestic courts in common law countries: ISDS falls into a broader international regime where there are neither hierarchical/centralized decision-making and enforcement authorities nor a multilateral investment treaty, and the rules and principles on foreign investment protection are fragmented in around three thousand Bilateral Investment Treaties (BITs). Against this backdrop, this thesis argues that, although there is a general agreement among the international community to further legalize international investment law, the process of legalization via the specific avenue of reforming the adjudication mechanism (i.e. ISDS) is subject to (1) the institutional constraint of international investment law, especially the lack of shared understanding among the international community regarding the treatment of foreign investments, and (2) the internal constraints of adjudication as a mode of social ordering. It further cautions that pursuing predictability while disregarding the low level of shared understandings regarding investment protection may cause more legitimacy problems than it solves
https://escholarship.mcgill.ca/concern/theses/2j62s986g
Keywords: Bilateral Investment Treaties (BITs); ISDS Reform; International Investment Law; Investments; Investor-State Dispute Settlement

Le régime d'investissements étrangers en Algérie : aspects juridiques - Benhama, Abderrahmane (Université Paris 1, 2020)
L’investissement national et étranger, privé et public, représente indubitablement l’un des axes les plus importants dans les politiques économiques des États développés et ceux en voie de développement. Le régime juridique de l’investissement étranger en Algérie n’a cessé d’être au centre des débats. D’essence économique, c’est pourquoi le législateur algérien a légiféré en masse sur le sujet notamment, à partir des années 1990, à l’occasion de l’adoption de la loi n° 90-10 du 14 avril 1990 relative à la monnaie et au crédit. Cette dernière était en effet le début d’un long processus de transition et d’orientation économique vers l’économie de marché. Actuellement le régime juridique de l’investissement étranger en Algérie est régi principalement par la loi 16-09 relative à la promotion de l’investissement, accompagné d’un ensemble de décrets d’application. Cette récente réforme du droit des investissements est une avancée importante dans la gestion, l’accueil et le traitement des investissements étrangers en Algérie, et ce au regard de tous les avantages qui sont consentis au profit des investisseurs, ainsi que l’assouplissement des procédures d’installations d’entreprises étrangères sur le territoire national.
Keywords: African Union; Algérie; Conseil National d'Investissement; European Union; Fonds Monétaire International; Fonds d'Appui à l'Investissement; Foreign direct investment; Foreign investment; International Monetary Fund; Investissement Direct Etranger; Investissements étrangers; Organisation Mondiale du Commerce; Taxe sur la Valeur Ajoutée; Union Africaine; Union européenne; Value-added tax; World Trade Organization

Foreign Investments in Disputed Maritime Zones: Maritime Disputes as Events of Force Majeure in International Law and International Investment Contracts - Kassem, Hazem (BAU Journal - Journal of Legal Studies, 2020)
Sovereign rights in Exclusive economic zones and Continental shelves are functionally limited to the economic exploitation of these zones. Moreover, in the case of disputed maritime zones these sovereign rights are neither exclusive nor necessarily constant. Nevertheless, states are still expected to provide the investments established in these zones the same treatment they should provide in their territories where they exercise full and constant sovereignty. If a host state agrees to the establishment of an investment in a maritime zone that become later contested, do the occurrence of the contestation and the hazards arising from such contestation relief the host state from its contractual and treaty obligations toward the investment by virtue of the force majeure concept. This paper argues that a traditional interpretation of the force majeure concept in respect of investment agreements and contracts, hampers states ability to de-escalate their maritime disputes, diminishes its capacity to conclude delimitation agreements and reduces the promotion of the UNCLOS III as well as its mechanisms for disputes settlement. It proposes a contextualist interpretation of the force majeure concept that is adapted to the exploitation of disputed maritime zones and states obligations under the international law of the sea. First, it examines the concept of force majeure as a doc-trinal hypothesis and its applications in international contracts and international in-vestment agreements. Second, it analyzes the legal act of maritime contestation as a force majeure event according to the possible interpretations of the concept of “force majeure”. Finally, it examines the recurrent legal implications susceptible of arising out of a contestation; provisional orders and unfavorable delimitation and their qualifica-tion as a force majeure event in the realm of investment agreements and contract.
Keywords: BIT; Disputed maritime zones; Force majeure; Foreign investment; Investment contracts; Maritime contestation; Maritime delimitation; Provisional measures

Développement des investissements immatériels dans les entreprises des pays en voie de développement : quelle place pour le conseil d’administration ? - Gonne, Jérôme; Bello, Pascal; Feudjo, Jules Roger (Revue de Recherches en Economie et en Management Africain, 2020)
L’objectif de cet article est d’analyser l’apport des compétences spécifiques des membres du conseil d’administration (CA) au développement des investissements immatériels dans un contexte de marché boursier embryonnaire. Pour conduire cette étude, nous avons utilisé la méthode hypothético-déductive. Ainsi, à partir de la revue de la littérature, nous avons pu formuler trois (03) hypothèses qui ont été testées par la suite. Les données de l’étude ont été collectées auprès d’un échantillon de 78 Sociétés Anonymes opérant au Cameroun. Les résultats obtenus mettent en exergue deux (02) dimensions des compétences des administrateurs qui permettent particulièrement de garantir une information comptable et financière de qualité sur la composante immatérielle et d’améliorer le niveau des investissements immatériels dans ces entreprises.
Keywords: Accounting information; Board of directors; Compétences des administrateurs; Conseil d'administration; Directors' skills; Financial information; Information comptable; Information financière; Intangible investments; Investissement immatériel; Public limited companies; Sociétés Anonymes

Direito de recesso e valor justo como proteção do investidor: a reforma necessária - Ponczek, Daniel Kalansky (Universidade de São Paulo, 2020)
Este trabalho parte da seguinte indagação: qual seria o melhor critério de avaliação para calcular o reembolso para fins de recesso do acionista minoritário dissidente de uma sociedade por ações? A análise partiu da constatação de que a atual Lei das Sociedades por Ações (Lei nº 6.404 de 1976), conforme entendimento majoritário, fixa como método de cálculo o patrimônio líquido contábil, quando o estatuto social não determina que outro seja aplicado. Contudo o método nem sempre reflete o valor justo da companhia, o que faz com que ao acionista seja ofertado um valor irrisório. Para estudar esse tema, começou-se por analisar a origem e os propósitos para os quais o recesso foi criado. Em seguida, analisaram-se os métodos de cálculo disponíveis para avaliar uma companhia. Estudou-se, também, a maneira como o reembolso é calculado nos Estados Unidos da América e na Itália. Com esse arcabouço teórico, analisou-se o direito brasileiro e, ao final, delineou-se como seria o valor de reembolso ideal. Concluímos pela necessidade de uma reforma legislativa de forma a prever que o valor do recesso deve dar-se obrigatoriamente pelo valor justo e, assim, oferecer proteção ao acionista minoritário e fomentar o mercado de capitais.
Keywords: Acionista minoritário; Appraisal remedy; Appraisal right; Corporate law; Direito de recesso; Essential right of the shareholder; Fair value; Investisseur (protection); Investments; Investor protection; Protection for the minority shareholders; Reembolso; Reimbursement; Right to dissent; Rétractation; Sociedade por ações; Valuation methods

The intersection of Public Procurement Law and Policy, and International Investment Law - Dagbanja, Dominic Npoanlari (Transnational Corporations Journal, 2020)
There is substantial scholarship on the limitations that international investment agreements (IIAs) place on States’ authority to regulate in the public interest. An area of fundamental importance that has not received scholarly attention in connection with IIAs is public procurement regulation. Given that public procurement is about the needs of States and their citizens, States would want to retain their authority within municipal public procurement laws to decide with whom to contract to meet those needs, and to pursue socioeconomic and industrial policies through procurement. However, most States are parties to IIAs, which impose obligations on them with respect to the protection of foreign investment. This article explores this seminal issue of whether IIAs stand to limit the authority of States in the implementation of procurement legislation and policies. Based on textual analysis and arbitral case study, it argues that treaty-based standards of investment protection can limit States’ authority on the implementation of methods of procurement (such as national competitive tendering or restricted tendering) and socioeconomic policies in procurement. A question that needs fuller engagement is the extent of conflict between specific IIAs and public procurement laws and policies, either regionally or globally, and how to reconcile conflicting obligations to promote foreign investment and sustainable development. This article provides the foundation for such future research.
http://hdl.handle.net/10019.1/124422
Keywords: Foreign (International law); Investments; Methods of procurement; Socioeconomic policies; Sustainable development

L’entrepreneuriat dans le Secteur [In]Formel au Sud-Kivu, en R.D. Congo - Mihigo, Isidore Murhi; Dady, Cool Mangole; Ibale, Douglas Amuli; Elie, Lunanga; Mukulu, Joseph Bahati (Revue de l’Entrepreneuriat et de l’Innovation, 2020)
Since the crises of 1970 and 1980, there has been a remarkable growth in the creation of enterprises in both formal and informal economies. This study attempts to highlight the determinants of the probability of entering the formal sector through an econometric analysis. The data used are based on surveys of 210 SMEs in the in[formal] sector in the city of Bukavu in DR Congo. We find that the probability of entering the formal sector is explained by the entrepreneur’s characteristics (gender and occupied status of employee) and the firm’s characteristics (capital, turnover, and the size of the workforce]. The capital of the company remains the most important constraint that entrepreneurs face to undertake in the formal sector.
Keywords: Bukavu; entrepreneur; formal; informal and sector

Protection de l'intérêt général et investissements directs étrangers dans le secteur minier malien: contribution aux réformes du droit OHADA - Kanta, Korotoumou (Université de Montréal, 2020)
Dans la présente étude, la protection des droits de l’homme et la promotion du développement durable sont considérées comme des préoccupations d’intérêt général. Partant de l’hypothèse d’une surprotection par le droit international de l’investissement de l’investisseur étranger, l’auteur tente de démontrer que le rééquilibrage des droits et des obligations entre investisseurs étrangers et États hôtes de l’investissement, amorcé dans les pays développés n’est pas perceptible dans les pays du sud. En effet, l’analyse faite des politiques et cadres juridiques relatifs aux investissements étrangers des pays de l’Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) semble conforter la thèse selon laquelle les mécanismes de prise en compte des préoccupations d’intérêt général sont relativement inadéquats, ou à tout le moins, insuffisamment efficaces. Les politiques de promotion et de protection de l’investissement direct étranger (IDE) y sont privilégiées, laissant peu ou pas de place aux politiques de protection axées sur les enjeux d’intérêt général. Il en résulte donc un déséquilibre marqué entre les mécanismes de promotion mis en œuvre dans ces pays et la nécessaire prise en compte des préoccupations liées au développement durable et à la protection des droits de l’homme. En nous appuyant sur le cas des investissements miniers au Mali, la présente étude permet de mettre en lumière ce déséquilibre tout en insistant sur les faiblesses systémiques et les conditions asymétriques dans lesquelles les instruments de régulation des investissements miniers sont produit et mis en œuvre. Les pistes de réflexion suggérées privilégient des approches fondées sur la convergence, à l’échelle des pays membres de l’OHADA, des mécanismes de production et de mise en œuvre des instruments juridiques entourant les investissements étrangers. Dans cette nouvelle configuration, le pouvoir d’uniformisation et d’harmonisation de l’OHADA est fortement sollicité. The protection of both human rights and sustainable development are viewed as real concerns of general interest in this thesis. These constitute a real challenge in international law of investments that often overprotects the foreign investor. The need to consider the general interest has been manifested in some case law before gaining the traditional way. This positive trend, consisting in including concerns of general interest remains exceptional, particularly in the investment policies and legislation in developing countries. On one hand, the legal regime of foreign direct investment (FDI) shows some disproportions of negotiating power to sign bilateral investment treaties negotiated with developed countries. On the other hand, government contracts present the same failures. Furthermore, FDI promotion and protection policies have become priorities on issues of general interest. The imbalance of the legal regime of FDI is reflected in the national investment laws in developing countries. Mining in Mali is a perfect example of the challenge of protecting the public interest in the legal framework of FDI. Avenues to find the way out have therefore been suggested in the context of the Organization for the Harmonization of Business Law in Africa (OHADA). The main goal is to promote a better protection of the general interest in Mali as well as in its other State members. These lines of thought have favored standardization of FDI in OHADA's body of law by focusing on the admission phase and the negotiation of investment treaties on behalf of the State members.
Keywords: FDI; Foreign direct investment; General interest; Intérêt général; Investissements; Investissements directs étrangers; Investments; Mines; OHADA; Responsabilité Sociétale de l'Entreprise; Social responsibilities of corporations responsibility

Investissement direct étranger et croissance économique en zone CEMAC : Le rôle du capital humain. - Ekodo, Raymond (Revue Marocaine d'Economie, 2020)
Résumé : L’objectif de ce papier est d’évaluer l’effet du capital humain dans la relation qui existe entre l’investissement direct étranger (IDE) et la croissance économique dans les pays de la Communauté Economique et Monétaire de l’Afrique Centrale (CEMAC). Pour y arriver, des estimations économétriques ont été faîtes en utilisant la Méthode des Moments Généralisés (MMG) en panel dynamique des six pays de la zone sur la période allant de 1996 à 2016. Les résultats obtenus montrent que le capital humain n’exerce aucune influence sur la relation entre l’IDE et la croissance économique dans le cas des pays de la CEMAC, et que la quasi-totalité de ces pays font plutôt face à un problème de la qualité du capital humain. Au regard de ces résultats, des recommandations ont été faites pour une amélioration de la capacité d’absorption des technologies avancées issues des flux entrants d’IDE par les pays hôtes à travers un capital humain au potentiel optimal pour la promotion d’une croissance économique de long-terme dans la zone Mots clés : Capital humain, Investissement Direct Etranger, croissance économique, CEMAC, MMG. The objective of this paper is to assess the effect of human capital in the relationship that exist between foreign direct investment (FDI) and economic growth in the Economic and Monetary Community of Central Africa (EMCCA) countries. To achieve this objective, econometric analyses of the panel data of the six countries for the period 1996 to 2016 have been carried out using the Generalized Methods of Moment (GMM). The result obtained from the analyses show that human capital has no influence on the relationship between FDI and economic growth in the case EMCCA countries, and that instead they face the problem of the quality of human resources. Based on the findings recommendations were made on how to improve the absorptive capacity of advanced technology deriving from FDI by hosts’ countries through human capital of optimal potential for the promotion of long-term economic growth in the zone.Keys words: human capital, foreign direct investment, economic growth, CEMAC, GMM
Keywords: CEMAC; Capital humain; Croissance économique; Economic growth; Foreign direct investment; GMM; Human capital; Investissement Direct Etranger; Investissements; Investments; MMG

Approche analytique de la ventilation des investissements directs étrangers marocains en Afrique: Trifurcation stratégique - Iraqi, Ahmed (Revue Marocaine d'Economie, 2020)
Depuis 2016, le Maroc est devenu le premier investisseur intra-africain. Une telle amplification de ses IDE envers l’Afrique reflète des motivations stratégiques outre-économiques que ne cesse de rappeler les plus hautes instances dirigeantes du royaume. Concomitamment à cela, la diplomatie africaine du Maroc a été remarquablement entreprenante et ce depuis 2013, et plus particulièrement dans le cadre de sa demande de réintégration réussie à l’union africaine, suivie par une seconde demande d’admission au sein de la CEDEAO qui s’est soldée également par un accord de principe favorable. À cet effet, nous nous sommes penchés sur des considérations d’ordre stratégique en mettant au diapason les caractéristiques inhérentes des investissements marocains en Afrique par rapport à une multitude d’enjeux. Dit autrement, nous avons délimité la ventilation stratégique des investissements marocains à la base d’une considération tridimensionnelle, se basant en l’occurrence sur le motif d’ordre économique, l’intérêt géopolitique outre la motivation tendancielle relativement à la prédation économique mondiale dont est victime le continent.
Keywords: Afrique; Banques; FDI; Foreign direct investment; Géopolitique; Investissements; Investissements directs étrangers; Investments; Maroc; Stratégie

International Investment Law in African Courts - Mbengue, Makane Moïse; Schacherer, Stefanie (International Investment Law: An Analysis of Major Decisions, 2020)
This chapter identifies major categories of situations, events and institutions in which or through which questions of international investment law have been dealt with before African courts. The chapter is selective in nature and aims at showing tendencies instead of exhaustivity. A noteworthy tendency that becomes apparent through the chapter’s analysis is that the prevailing narrative of bypassing African courts and tribunals seems declining in importance as an increasing number of national investment law instruments foresee African judicial and arbitral institutions for the settlement of investment disputes.
Keywords: African national courts; Apartheid; EAC; ECOWAS; Investment arbitration; Land reform; National investment law; OHADA

The Effect of EU State Aid Law on the Future of EU Investment Policy - Finckenberg-Broman, Pamela (Griffith University, 2020)
On 1 July 2017, the Commission of the European Union (Commission) announced that investor state dispute settlement (ISDS) was dead. Apart from the fundamental public distrust of ISDS, its rejection by the European Union (EU) is a symptom of several underlying causes, the foremost of which is the need to protect the autonomy of the EU legal order and its right to regulate public policy objectives, as well as to avoid jurisdictional conflicts. With this backdrop EU state aid law, which enjoys public policy status, has emerged as a major example of the conflict between investor protection and the right to regulate. As state aid law imposes measures on the EU Member States that conflict with these states’ international obligations to foreign investors under bilateral investment treaties (BITs), they have become subject to claims and substantial liabilities. This dilemma can arise in any setting that involves the EU or one or more of its Member States. It also includes relations with non-EU countries, as the web of international investment agreements (IIAs) operates, in different forms, on an international scale. Therefore, this dilemma and the EU’s responses to it is analysed through the different forms in which EU state aid law appears, dependent on the EU investment policy aspect utilised as a platform for analysis. Utilising a doctrinal analysis by studying, discussing and analysing the impact of EU state aid law on the EU Member States’ BITs and EU Trade Agreements, this dissertation provides an insight into the function and logic behind international treaties involving the EU’s competition and investment policy. This is done by utilising the research question: How does the European Union (EU) state aid law affect the future of EU investment policy in a global context? Further, this thesis puts forward three arguments in which EU state aid law is affecting the future of EU investment policy in a global context. First, state aid law applies in the EU’s incorporation of clauses promoting fair competition and state aid policy in international trade agreements. Second, state aid law and policy has contributed to recent EU internal development, which led the EU Member States to terminate their bilateral agreements with each other (intra-EU BITs) by the end of 2019. Third, the EU has been working towards replacing the existing BITs between the EU’s Member States and third countries (extra-EU BITs) with the EU’s own trade agreements, which are aligned with EU legislation. Essentially, this thesis golden thread is a debate on who gets to decide on the scope of state aid law now and in the future. In other words, is it the EU that sets the borders and the status of state aid law and policy law regarding investment protection or the international investment tribunals by their legal practice? Hence, this thesis offers a glimpse of a conceivable future of EU investment policy in a global context. An analysis of the relevant literature, and observation of recent policy changes on its subject matter, as reflected in the Commission’s policy documents, the EU’s international agreements and declarations by the Member States, leads to the findings of this dissertation. A conflict situation that originated from legal conflicts within the EU, the EU experience of investment protection and state aid regarding intra-EU BITs, provided some lessons to learn for the EU organs. These lessons learned have found expression on a global scale. By incorporating fair competition and state aid policy in international trade the EU is reasserting that it is the EU that decides on state aid law and policy law regarding investment protection. Indeed, the EU is attempting to tame investment protection in such a way that fair competition and investment protection can peacefully coexist in international trade. Ultimately, the interplay of state aid and the EU’s investment policy within the internal market reflects on the external trade relations of both the Member States and the EU through this practice. Thus, state aid law affects and will continue to affect the future of EU investment policy in a global context.
Keywords: EU; European Union; Investment protection; Investments; Policy Law; State aid law

Chinese Investment in Ethiopia: Contribution, Challenges, Opportunities and Policy Recommendations - Gebrehiwot, Berihu Assefa; Gebreeyesus, Mulu; Weldesilassie, Alebel Bayrau (PSI Research Report, 2020)
Recognizing the immense potential for greater Chinese investment promotion and its contribution to Ethiopia’s industrialization and acknowledging the gaps, this paper aims to conduct a rigorous research through analysis of secondary sources and qualitative survey of Chinese enterprise doing business in Ethiopia in various sectors. In this regard, the key policy questions that this study tries to answer are ‘the involvement in and the contribution to Ethiopia’s industrialization and the challenges and opportunities they face. Hence, the overall objective of this research will be to (i) assess the trends in Chinese enterprises involvement in Ethiopia’s industrialization for the last decade, (ii) inform both the Chinese government and Ethiopian government on key business barriers and market failures that are constraining Chinese business entry and growth in Ethiopia; (iii) investigate the immense untapped investment potential from China that can be attracted and opportunities that Ethiopia could offer to Chinese investors; and (iv) propose policy options on how to address the challenges and thereby maximize the opportunities to enhance Chinese investment towards Ethiopia’s industrialization.

Investor-state arbitration and African states: a proposal for a Pan-African investment court - Ama, Obiajunwa (Canterbury Christ Church University, 2020)
This thesis proposed for the reform of Africa’s Investor-State Dispute Settlement (ISDS) landscape through the establishment of a Pan-African Investment Court (PAIC) as a mechanism for the resolution of Investor-State Disputes. This proposal is influenced by the findings of my investigation on the functioning of Investor-State Dispute Settlement (ISDS) through the deployment of Investor-State Arbitration to resolve Investor-State Disputes between African states and foreign investors. This research is motivated by the criticisms of the Arbitration mechanism by a broad spectrum of constituencies within international investment law. These criticisms are primarily anchored on the legitimacy crises of ISDS, a dissatisfactory notion that denounces the deployment of the private mechanism and privity of contract ingrained investment arbitration framework to resolve publicly-inclined investor-state disputes. Ancillary to this critical holy grail are further dissatisfactions on the practical functionality of investment arbitration in aspects of high volume of cases against developing states, lack of diversity in the appointment of arbitrators and curtailment of sovereignty of host states through the intrusion of provisions of International Investment Agreements on legitimate internal decision-making powers. Consequently, this thesis investigated the practical functioning of ISDS in African states. After the study of the experiences of Egypt, South Africa and Tanzania; it was found that the legitimacy crises of ISDS also impacts on African states, and does not support their socio-economic and sustainable developmental aspirations. As a remedy, I proposed for a reform to an Investment Court System (ICS) through the establishment of a Pan-African Investment Court (PAIC). An evaluation of this recommendation was conducted that evidenced potential challenges that may mitigate its feasibility, thus leading to the advancement of two secondary reform alternatives vis the reform and retention of the current investor-state arbitration framework and engagement in innovative treaty-making practices by African states. To the best of my knowledge, this thesis has not been previously submitted in any higher institution or published by another person. The contents of this thesis are my ideas. Where the materials of others were used, due acknowledgement and reference was provided. Acknowledgements
Permalink: https://repository.canterbury.ac.uk/item/90873/investor-state-arbitration-and-african-states-a-proposal-for-a-pan-african-investment-court
Keywords: Arbitration; Investment Court System; Investments; Investor-State Dispute Settlement; Investor-state arbitration

Zukunftsfähiger internationaler Rechtsrahmen für Investitionen in Afrika - Gramlich, Ludwig (Recht in Afrika, 2020)
The future of sustainable development in Africa and for its growing population will depend on investments which might come mostly from abroad attracted by a favourable investment climate (or ecosystem). It is rather doubtful that the actual ('old') international legal framework for investment-related and investment-specific measures which does hardly create an adequate balance between the interests of all important public as well as private stakeholders would meet the requirement of today and tomorrow. But any alterations or improvements must start from the present state of things. So, this study looks at the different levels and various instruments dealing with traditional standards of investment and investor protection, e.g. BITs und TIPs, and at the activities of global, regional and sub-regional organizations (in particular EU and OHADA). Moreover, new developments at global and regional levels are discussed including trends showing a somewhat specific African approach to investment issues ('Africanization'). Finally, a very important topic, i.e. the relation between investment protection and human rights (of investors and of other people negatively affected by relevant activities), is described and assessed in more detail. A second part of the analysis will turn to elaborating on dispute settlement and enforcement issues since till today, there seems to be a sharp distinction between Investor-State- Dispute Settlement (ISDS) by way of mediation, conciliation and arbitration on the one hand and judicial redress by national courts (of home, host or third States) on the other.

An Empirical Analysis of Private Equity Investment Affecting Enterprise Value - Li, Jianhong (Université de Genève, 2020)
The lack of long-term and stable financial support for SMEs is the fundamental reason why enterprises cannot develop for a long time. At present, the situation of financing difficulties for SMEs is becoming more and more serious. Private equity (PE) investment has emerged as an important financing method. Private equity investment, while broadening the financing channels of SME capital markets, brings advanced management experience to enterprises, which helps enterprises to develop rapidly and effectively. According to the statistics of the Zero2IPO Research Center, the active investment institutions in China's equity market have grown from more than 200 in 2000 to more than 14,000 in 2018, with a total asset under management over RMB 9 trillion. Great progress has been realized in the scale and development of the industry. In addition, with the launch of the GEM in 2009, PE investment industry met new opportunities of development and became popular. At present, the development of China's PE investment business is still at an early stage. Neither relevant policies, laws and regulations nor supporting mechanisms are mature enough. Therefore, researches on China's PE investment business needs to be carried out. In this context, more and more scholars are beginning to focus on the field of PE investment. This paper focuses on whether PE investments can fundamentally increase the enterprise value. The basic theory is sorted out to serve as the theoretical basis for this study. Through a systematic analysis, this paper draws out 4paths of PE investment affecting enterprises, which are the influence on technological innovation, corporate governance activities, dividend distribution decision and earnings management, respectively. And through empirical analysis, it finds the empirical basis of the impact of PE investment on enterprise value, and investigates how PE investments affect enterprise value based on the difference in investment characteristics such as investment duration and whether the investment is joint or not. This paper conducts an empirical test by selecting the listed companies of the Shenzhen Stock Exchange GEM in 2015-2018 as sample. The results show that the investment of PE firm will significantly increase the value of the target enterprise. This paper makes a detailed analysis of sample data. The conclusion of the study is that private equity investment will have a significant impact on the value of target enterprises. Private equity investment plays an important role in the modern governance structure of small and medium-sized enterprises in China This paper enriches the existing literature and provides constructive suggestions for the health development of the PE investment market. 中小企业缺乏长期稳定的资金来源是企业无法长久发展的根本性原因，目前 中小企业融资难的形势越来越严峻，私募股权投资作为一种重要的融资手段应运 而生。私募股权投资在拓宽中小企业资本市场融资渠道的同时，给企业带来先进的 管理经验，有助于企业快速并有效的发展。据清科研究中心的统计数据显示，中国 股权市场活跃的投资机构已由 2000 年的 200 多家发展到 2018 年的 1.4 万多家，管 理资本量超过 9 万亿人民币，行业规模和发展实现了质的飞跃。此外，随着 2009 年创业板的推出，私募股权投资行业的发展业迎来了新的希望和契机，私募股权投 资业务开始盛行。目前，我国私募股权投资业务的发展还处于早期阶段，无论是从 政策还是法律法规再到配套机制，都还不够健全。因此，对我国私募股权投资业务 的研究亟需开展，在此背景下，越来越多的学者开始关注私募股权投资这一领域。 本文研究的重点是私募股权投资是否能够根本上提升企业价值。本文首先对 基础理论进行了梳理，以此作为研究的理论依据，而后论述了私募股权投资对被投 资企业价值影响的理论分析，。本文通过系统的理论分析得出了私募股权投资影响 企业的路径，并通过实证分析，得到私募股权投资对企业价值的影响的实证依据， 并且从投资期限和是否联合投资等投资特征的差异性，深入研究私募股权投资对 企业价值的影响方式。本文通过选取深圳证券交易所创业板 2015-2018 年的上市企 业作为样本，进行了实证检验，并得出以下研究结论:私募股权投资的参与会显著 提升目标企业的价值，同时，私募股权投资的期限越长、联合投资机构的数量越多， 目标企业的价值也会越高。 本文基于理论又结合实际，对样本数据进行了分析，研究的结论是私募股权投 资会对被投资企业的价值产生显著影响。私募股权投资对于我国中小企业的现代 化治理结构起到了完善作用。本文的研究结果丰富了现有文献，对私募股权投资市 场健康发展提出了建设性的建议。
Keywords: Enterprise Value; Investment Term; PE Investment

The Effect of IFRS Adoption on Foreign Direct Investment in Africa - Musah, Alhassan; Adjei, Eunice; Ahmed, Ibrahim Anyass (Journal of Applied Accounting and Taxation, 2020)
Adoption of International Financial Reporting Standards (IFRS) is supposed to help enhance comparability of financial statement, improve the quality of financial reporting and accounting information of businesses in a country. This is expected to help improve Foreign Direct Investment (FDI) in the adopting countries. This study examined the effect of IFRS adoption on FDI inflows in Africa. Unlike previous studies that sample both adopting and non-adopting countries, this study sampled only Africa countries that have adopted IFRS to determine whether the adoption has improved FDI inflows. To achieve this objective, 20 African countries that have adopted IFRS were sampled covering a period 1980 to 2015. Data was sourced from The World Bank financial and Economic Data. Control variables such as GDP growth, openness of the economy, government debt and population growth were included in the model. The correlation and regression analysis showed that IFRS adoption has a positive and significant influence on FDI inflows in Africa. On the other hand, open economy, government debt and population growth had a positive and significant association with FDI. Overall, the results show that African countries that want to improve FDI inflows must improve the quality of their reporting environment by adopting IFRS.
Keywords: Africa; FDI; Foreign direct investment; IFRS; IFRS adoption; Investments; Macroeconomic variables

What drives individual decision-making of Foreign Direct Investments (FDI) to Sub-Saharan Africa - Yusuf, Mukhtar Abubakar (Case Western Reserve University, 2020)
This dissertation examines a multiplicity of factors that influence at the microeconomic level the level of Foreign Direct Investment (FDI). The main objective of the dissertation is to empirically explore and validate the effect of a select set of individual-level perceptual factors on FDI decisions. Given the paucity of research on the topic in comparison to macroeconomic studies of investment inflows between regions and countries, we conduct the study as a mixed-method study. The study consists of three interconnected empirical studies. The first seeks to identify the presence of factors that shape an individual’s decisions on FDI inflows. The two following ones seek to validate the effects of these factors on the individual decision maker's propensity to invest in a specific country. The first study belongs to a qualitative strand and answers the following research question: What are the investor’s critical perceptual factors and experiences that influence their FDI decisions? The study participants consisted of 30 foreign investors, the government’s Ministries, Departments, and Agencies (MDAs), and the Nigerian investors in the diaspora. The paper finds that on the supply side, several key FDI perception factors influence decision-making. On the demand side, there are four attractors and four repellents that influence potential investors' decisions. In the quantitative strand of the study, we offer the following questions: (1) To what extent do investment decision perception impact foreign direct investment (FDI) inflows? And (2) To what extent do the investors from Europe and North America and investors from Asia and Africa (the West and the East) influence what factors matter in foreign direct investment (FDI) decisions? The samples consist of 269 individuals from the private sector, both in Nigeria and in the diaspora that participated in the survey. I use structural equation modeling to find that Return on Investment (ROI), Security/Personal Safety, and Investment Facilitation Services have a significant direct effect on the FDI decisions. A post hoc exploratory analysis indicates positive relationships between Ease of Doing Business and Investment Promotion and FDI are significant for investors from the investors from Europe and North America as well as the negative impact of Corruption. In contrast, the positive relationship between Return-On-Investment and FDI is more substantial for investors from East Asia and Africa. The next part of the quantitative strand investigates (1) to what extent investment promotion services and Investment Facilitation effects in the receiving country shape positive investment decision outcomes, and (2) to what extent investment perceptions and related decisions vary across industry groups facing different investment horizons and risk levels. The analysis indicates that the Investment Promotion services significantly mediate Corruption Perceptions and Investment Facilitation services. And Investment Facilitation does moderate the effect of Investment Promotion. The exploratory industry-level analysis reveals that the effects of Return On Investment to FDI decisions and Security to FDI decisions significantly differ across Infrastructure-Mining/Services, Services/Agriculture-Manufacturing, and Agriculture-Manufacturing/Infrastructure-Mining industries suggesting significant Industry-level effects. Generally, these findings reveal much more refined and complex dynamics of FDI inflows and how individual investor’s perceptions shape them. Specifically, the results provide deeper insights into the investor’s risk perceptions that arise in a particular country. This depends on holistic perceptions of the country’s economic, political, and social environment, and also the investor’s time horizon and risk preferences signaling significant individual and situational differences in how decision-makers approach FDI.
Keywords: Corruption; Ease-of-doing-business; FDI; FDI attractors; Foreign direct investment; Investment decision-making; Investments; Nigerian Investment Promotion Commission; Perception; ROI; Return on investment; Security

Les mécanismes d'incitations fiscales à l'investissement des entreprises étrangères en France et au Gabon - Engone, Kénaelle Cyndie (Université de Limoges, 2019)
L’attractivité territoriale des Etats se trouve au centre des préoccupations tant au niveau national qu’international. Les mesures fiscales dérogatoires destinées à attirer des investissements étrangers s’avèrent nombreuses et complexes, en raison non seulement de l’influence internationale, mais également des hésitations et de l’accumulation des règles nationales. Au Gabon et en France, les incitations fiscales d’attraction territoriale ont été instruites dans des domaines d’activités clés de l’économie. Elles participent ainsi à l’industrialisation de ces pays. Cependant, au-delà de l’industrialisation, ces mesures dérogatoires visent à développer certaines zones du territoire, et surtout à lutter contre le chômage. Néanmoins, loin de toujours parvenir aux résultats escomptés, ces mesures finissent parfois, au fil des années et des modifications successives à se complexifier, les rendant illisibles. The territorial attractiveness of states is at the center of national and international. Derogatory tax measures designed to attract foreign investments are numerous and complex, not only because international influence, but also hesitations and the accumulation of national rules. In Gabon and France, territorial attraction tax incentives have been educated in key activity areas of the economy. They thus participate industrialization of these countries.However, beyond industrialization, these derogations aim to develop certain areas of the territory, and especially to combat unemployment. Nevertheless, far from always achieving the expected results, these measures end up sometimes, over the years and successive modifications to become more complex, making them unreadable.
Keywords: Aides d’Etat; Attractivité (géographie); Competitiveness; Compétitivité; Emploi; Employment; Fiscalité; Gabon; Impôt; Incitations fiscales; Industrialisation; Investissements; Investments; State aids; Tax incentives; Taxe

Essays on Economics of Litigation : an Application to Investor-State Disputes - Vu, Duy (Université Côte d'Azur, 2019)
International investment treaties often allow the foreign investor to sue the host country before international arbitration in case of breaches of treaty provisions. The number of investor-state disputes is growing so rapidly that some countries expressed their discomfort with the current international investment law regime. The first chapter gives readers a comprehensive view on the effectiveness and spillover effect of international investment arbitration. Based on a vast interdisciplinary literature, we reexamine recent criticisms and identify the root of the crisis faced by international arbitration. We conclude that it is possible for countries to adapt the current regime of international law to new situations without wholesale exit. The second chapter investigates the early settlement of investor-state disputes. Drawing on the rich economic literature and a new dataset related to treaty-based disputes, we find that the host state's experience, the case prospect, the nature of the regulatory measures, the identity of investors and Dutch investment treaties have significant impacts on the probability of early settlement. The third chapter focuses on an institutional dimension of arbitration: the effectiveness of ICSID in solving disputes. The time to resolution and the quality of the final judgment which is measured by the requirement of follow-on proceedings are used as performance indicators. We highlight how arbitrators' biographical and professional characteristics can impact the ICSID effectiveness. Les traités internationaux d'investissement permettent souvent à l'investisseur étranger de poursuivre le pays d'accueil devant un tribunal d’arbitrage international en cas de violation des dispositions du traité. Le nombre de différends entre investisseurs et États augmente si rapidement que certains pays expriment leur malaise à l'égard du régime actuel du droit international de l'investissement. Le premier chapitre donne aux lecteurs une vue générale sur l'efficacité et les effets de spillover de l'arbitrage international en matière d'investissement. En se basant sur une vaste littérature interdisciplinaire, nous réexaminons les critiques récentes et identifions la cause sous-jacente de la crise relative à l'arbitrage international. Nous concluons qu'il est possible pour les pays d'adapter le régime actuel du droit international à de nouvelles situations plutôt que de le quitter. Le deuxième chapitre étudie le règlement amiable des différends entre investisseurs et États. En nous fondant sur la riche littérature économique et sur une nouvelle base de données de différends relatifs à la violation des traités, nous constatons que l'expérience de l'État hôte, les perspectives du différend, la nature des mesures réglementaires, l'identité des investisseurs et les traités d'investissement néerlandais influencent significativement la probabilité d'un règlement rapide du différend. Le troisième chapitre se concentre sur une dimension institutionnelle de l'arbitrage : l'efficacité du CIRDI dans la résolution des différends. Le délai de résolution et la qualité du jugement final, représentée par la probabilité d'avoir des recours post-sentence, sont utilisés comme indicateurs de l'efficacité. Nous soulignons comment les caractéristiques biographiques et professionnelles des arbitres affectent l'efficacité du CIRDI.
Essais en économie du litige : une application aux différends entre investisseurs et Etats
Keywords: Analyse économique; Arbitrage international; Arbitrage international d'investissement; Centre international pour le réglement des différends relatifs aux investissements; Différends investisseur-Etat; Economic analysis; International Investment Arbitration; Investissements étrangers; Investor-state disputes; Médiation internationale

La sécurité alimentaire à l'épreuve du droit international des investissements - Madeleine, Emily (Université Côte d'Azur, 2019)
Si les investissements internationaux contribuent à la réalisation de la sécurité alimentaire, ils peuvent aussi constituer une menace et une voie d’aggravation. L’étude des interactions entre la sécurité alimentaire et les investissements internationaux révèle l’existence de conflits de normes porteurs de risques alimentaires et met en lumière des déséquilibres normatifs dans le droit international des investissements. Ainsi, la mise en œuvre des droits des investisseurs est susceptible de conduire à l’exclusion de la sécurité alimentaire. A l’inverse, l’affirmation de cette dernière peut générer une altération ou une négation des droits des investisseurs. De sorte que, dans cette situation conflictuelle, les obligations alimentaires de l’État ne pourront pas être satisfaites de manière simultanée avec les obligations énoncées dans les accords d’investissements internationaux. Ces conflits normatifs interviennent comme des alarmes et renseignent d’une part, sur les déséquilibres du pouvoir de règlementation des États et des droits exclusifs des investisseurs, et d’autre part, sur l’asymétrie des droits des victimes d’insécurité alimentaire et des droits des investisseurs. L’insuffisance de prévention renforce les contrariétés de décisions et maintient l’assujettissement des États à des obligations contradictoires. Une fois analysés les conflits de normes et les risques alimentaires qu’ils génèrent, il s’avère que les tentatives de résolution de ces derniers, par le biais des techniques classiques, demeurent souvent inopérantes, rendant compte des limites du système actuel. Pour leur part, les risques, la norme et la responsabilité alimentaire restent parfois non identifiés et ne sont pas appréhendés dans leur globalité. Ces circonstances complexifient la résolution des conflits de normes. Dès lors, la thèse s’attache à démontrer que ces conflits sont susceptibles parfois d’être évités, ou réduits, puis, envisage un traitement dans la résolution de ces derniers en vue de parvenir à une articulation entre les droits des investisseurs étrangers et la protection de l’intérêt public alimentaire de l’État d’accueil de l’investissement.
Keywords: Aide alimentaire; Aliments; Approvisionnement; Conflits de normes; Food security; Foreign investment; International investments; Investissements internationaux; Investissements étrangers; Investments; Norm conflicts; Sécurité alimentaire

Les IDE en Afrique : les pays africains les plus attractifs et les secteurs les plus prometteurs - Iguergaziz, Wassila; Boulifa, Yamina (University of Eloued, 2019)
L'Afrique reste une destination privilégiée pour les investisseurs d’autres continents. Si le monde entier a le regard tourné vers l'Afrique, c’est en partie pour son taux de croissance de son PIB et de ses échanges internationaux. La part de l’Afrique dans les investissements directs étrangers (IDE) mondiaux est passée de 1,2 % en 2007 à 3,1 % en 2012. L’Afrique est l’une des rares régions à avoir enregistré une hausse des entrées d’IDE en 2011 et 2012 alors que les flux mondiaux baissaient sur la même période. A partir de là, nous dégageons la problématique suivante : quels sont les pays africains les plus attractifs pour les IDE et les secteurs les plus prometteurs ? Abstract: Africa remains a preferred destination for investors from other continents. If the whole world is looking to Africa, it is partly for its rate of growth of its GDP and its international trade. Africa's share in global foreign direct investment (FDI) increased from 1.2% in 2007 to 3.1% in 2012. Africa is one of the few regions to have experienced an increase in inflows of 'FDI in 2011 and 2012 while global flows decreased over the same period. From there, we highlight the following problem: which African countries are the most attractive for FDI and the most promising sectors?
Publisher: University of Eloued جامعة الوادي

Le consentement étatique à la compétence des juridictions internationales - Marquet, Clément (Université de Genève, 2019)
Le consentement étatique à la compétence des juridictions internationales est un élément incontournable du droit international public. Il régit le le fonctionnement de la justice internationale. Cependant, malgré son ubiquité, la notion est mal comprise. Ce travail, à travers la jurisprudence de la CIJ, d'ITLOS, de l'OMC et du CIRDI, redéfinit ce consentement, à la lumière de son histoire, son rôle et ses enjeux. Cette re-contextualisation est accompagnée d'une présentation et d'une analyse des enjeux contemporains entourant la notion.
Keywords: Arbitrage; Arbitragem; Arbitration; CIJ; CIRDI; Compétence; Compétence de la compétence; Consentement; Cour internationale de justice; Droit international public; Forum prorogatum; ICSID; ITLOS; Interprétation; Investissements; Investments; Juridictions; MFN; NPF; OMC; Organisation mondiale du commerce; Recevabilité; TIDM

Le régime juridique du financement islamique Moucharaka en investissement immobilier - Morjane, Hicham (Université Hassan 1er, 2019)
Islamic banking is marked by its use of overly generous terms that are likely to apply to multiple factual situations forming more disputes than the law is supposed to settle, these terms are chosen in the style of Islamic Shariah and are considered as statements of Islamic principles rather than as the enactment of legal rules directly applicable to the facts and therefore able to propose solutions. Wishing to gain a better understanding of this young institution, the Musharakah contract in real estate financing. And as a result of our study and final arguments: this thesis will be a legal theory describing with legal simplicity the complex concept of the Musharakah contract in Islamic real estate financing in comparative law. In addition to the fact that the law must be normative, intelligible, in other words readable, clear and precise. Thus, our thesis is a research of analysis and demonstration, making the Musharakah contract in real estate financing go beyond the purely Islamic context and explicitly position it in a universal legal field as: "a legal regime of a contractual structure combining the company contract and the trust contract".
Keywords: Banque islamique; Financement immobilier; Investissement immobilier; Islamic banking; Moucharaka; Musharakah; Real estate financing; Real estate investments

The Legal Regime of Real Estate Investment Financing by Musharaka Contract - Morjane, Hicham (Université Hassan 1er, 2019)
Islamic banking is marked by its use of overly generous terms that are likely to apply to multiple factual situations forming more disputes than the law is supposed to settle, these terms are chosen in the style of Islamic Shariah and are considered as statements of Islamic principles rather than as the enactment of legal rules directly applicable to the facts and therefore able to propose solutions. Wishing to gain a better understanding of this young institution, the Musharakah contract in real estate financing. And as a result of our study and final arguments: this thesis will be a legal theory describing with legal simplicity the complex concept of the Musharakah contract in Islamic real estate financing in comparative law. In addition to the fact that the law must be normative, intelligible, in other words readable, clear and precise. Thus, our thesis is a research of analysis and demonstration, making the Musharakah contract in real estate financing go beyond the purely Islamic context and explicitly position it in a universal legal field as: "a legal regime of a contractual structure combining the company contract and the trust contract".
Il s'agit de la traduction d'une thèse déjà présente dans référencée sur notre sité
Keywords: Banque islamique; Financement immobilier; Investissement immobilier; Islamic banking; Moucharaka; Musharakah; Real estate financing; Real estate investments

Le cadre juridique des investissements internationaux en République démocratique du Congo - Iririra Nganga, Dan (Aix-Marseille Université, 2019)
L’investissement étranger est considéré aujourd’hui comme un facteur clé voire une valeur ajoutée à même de faciliter le développement de l’État d’accueil. Ainsi, l'État congolais mise sur l’amélioration de son arsenal juridique interne dont l’objectif consiste à attirer de nombreux investisseurs et investissements étrangers sur son territoire. Pour ce faire, des réformes tendant à l’amélioration de principaux textes juridiques applicables directement ou indirectement en matière d’admission et de sécurisation des investissements étrangers afin de se conformer aux standards internationaux deviennent une obsession pour cet État, dont la finalité demeure : la valorisation de ses ressources naturelles notamment le cobalt, le germanium et la colombo-tantalite etc. très souvent inexploitées et utile à même de servir à la production des batteries pour les voitures électriques. Il serait donc nécessaire désormais que le contrôle de l’État souverain sur ses ressources naturelles considérées comme des minerais stratégiques soit davantage renforcé et que le contentieux en matière d’investissement soit confié à des entités qui prennent en compte l’intérêt général au détriment des arbitrages sous l’égide des arbitres privés, défendant les intérêts privés. Ainsi, la création d’un Centre international africain de règlement des différends pourrait être profitable notamment en permettant aux experts africains - tant arbitres qu’avocats - d’être plus présents dans le cadre des procédures impliquant leurs États d’origine. Foreign investment is now considered a key factor or even an added value that can facilitate the development of the host country. Thus, the Congolese State is focusing on improving its domestic legal arsenal, the objective of which is to attract many foreign investors and investments to its territory. To this end, reforms aimed at improving the main legal texts directly or indirectly applicable to the admission and security of foreign investments in order to comply with international standards are becoming an obsession for this State, the purpose of which remains: the development of its natural resources, in particular cobalt, germanium and colombo-tantalite etc., which are very often unexploited and useful for the production of batteries for electric cars. It would therefore now be necessary for the sovereign State to strengthen its control over its natural resources considered as strategic minerals and for investment litigation to be entrusted to entities that take into account the general interest to the detriment of arbitrations under the aegis of private arbitrators, defending private interests. Thus, the creation of an African International Dispute Resolution Centre could be beneficial, in particular by allowing African experts - both arbitrators and lawyers - to be more present in proceedings involving their States of origin.
Keywords: Accords bilatéraux; Admission; Bilateral agreements; Congo (République démocratique); Droit; Eclatement; Expropriation; Fair and equitable treatment; Inadequacy of the law; Inadéquation du droit; Incohérence; Inconsistency; Intérêt national; Investissements étrangers; L’obsolescence des règles; Minerais stratégiques; Nationalisation; Obsolescence of rules; Permanent sovereignty; Ressources naturelles; Securisation; Souveraineté permanente; Splitting; Strategic minerals; Sécurisation; Sécurité juridique; Traitement juste et équitable; Transparence; Transparency

Le refinancement d'entreprises en difficulté : contribution à l'optimisation juridique du concept de capital-retournement - Feydel, Romain (Université de Limoges, 2019)
Le refinancement d’entreprises en difficulté est entouré d’une grande part de mystification. Aux yeux du grand public, il s’agit avant tout d’un moyen efficace de faire fortune pour les investisseurs s’y aventurant. Cette activité, connue également sous le nom de capital-retournement, est pourtant le domaine d’exercice exclusif de hauts techniciens de la finance et du droit. Le vaste droit de l’ingénierie financière encadre le refinancement d’entreprises en difficulté. Plongeant son lecteur au coeur de la haute finance d’entreprise, cette thèse démystifie le capital-retournement tout en voulant améliorer sa pratique. Pour cela, l’aspect juridique de la levée des fonds et de leur investissement fait l’objet d’une profonde analyse. À partir de celle-ci et de l’inspiration du droit étranger, de nouveaux outils dédiés à l’optimisation du refinancement d’entreprises en difficulté sont proposés. Cette thèse démontre le rôle prépondérant du droit de l’ingénierie financière dans le sauvetage d’emplois en France.
Keywords: Banking and financial law; Droit bancaire; Droit de l'investissement; Droit financier; Droit privé; Fiscalité; Ingénierie financière; Investment Law; Taxation

Rapport sur la situation économique en Mauritanie : améliorer le climat des affaires pour favoriser le développement du secteur privé - Banque mondiale (Groupe de la Banque mondiale, 2019)

La transparencia en el arbitraje internacional y en los tratados bilaterales de inversión - Febles Pozo, Nayiber (Universitat de Girona, 2019)
The thesis's main objective is the analysis of transparency in international arbitration. To this purpose, we start from a broad conception of the notion of transparency and its relevance in the current Bilateral Investment Treaties (BITs) and in the main international arbitration regulations: the ICSID, the ICC, UNCITRAL and its Rules on Transparency in Treaty-based Investor-State Arbitration, followed by a study of the most important issues of the arbitration procedure related to transparency, such as public hearings, the participation of third parties in the procedure (third-party funders and amicus curiae), the appointment of arbitrators and the conflict of interests and, finally, the analysis of transparency in the decisions (arbitral awards). The thesis proposes and bases, among other issues, the need to create an ICSID Court of Appeal and, if not, the most suitable mechanism for the implementation of an International Investment Tribunal
Keywords: Advertising; Arbitrage; Arbitragem; Arbitraje internacional; Arbitration; Bilateral Investment Treaties (BITs); Confidencialidad; Confidencialitat; Confidentiality; Ethical principles; International Arbitration; International Investment Tribunal; Investments; Investor-state arbitration; Preciding; Principios éticos; Principis ètics; Publicidad; Publicitat; Transparencia; Transparency; Transparència

The China-OHADA BIT, a step in the right direction : a new model of China-Africa BIT at a regional or sub-regional level - Sun, Sisi (Université de Montréal, 2019)
L’Afrique jouit non seulement de ressources naturelles, mais aussi d’un grand potentiel de marché. Ces dernières années, il y a une injection croissante d'investissements privés en provenance de Chine vers l’Afrique. La Chine souhaite exploiter le potentiel de l’Afrique en tant que marché émergent grâce aux investissements considérables réalisés par des entreprises privées. Parallèlement, les pays africains ont besoin d'investissements chinois dans divers domaines pour stimuler chaque aspect de leurs économies. L'investissement privé axé sur le marché nécessite un environnement d'investissement ouvert, stable, sécurisé et prévisible. Or, les traités bilatéraux d'investissement (TBI) existants entre la Chine et l'Afrique adoptent le modèle post-établissement axé sur la protection. La plupart de ces traités prévoient simplement des obligations générales de protection des investissements, laissant toutes les autres questions à la discrétion de l’État hôte. Les régimes juridiques instaurés par les TBI conclus entre la Chine et les États africains manquent de lisibilité, de prévisibilité et de cohérence. La conclusion de l'accord économique et commercial global entre l'UE et le Canada (AECG) suggère l’idée que la Chine pourrait s’inspirer de ce modèle pour conclure un accord bilatéral autonome avec les pays africains au niveau régional ou sous régional afin d’attirer des investissements chinois vers l’Afrique. Cet accord pourrait intervenir dans le cadre de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) étant donné son niveau d’intégration et son autorité en matière de commerce et d’investissement sur le continent. Ce TBI modèle comportera des normes uniformes en matière d’accès aux marchés et de protection des investissements, ce qui limitera les risques d’interprétation divergente et partant, contribuera à l’instauration d’un climat d'investissement stable, sûr, prévisible et plus ouvert. Africa enjoys not only natural resources, but also market potential. There has been a growing injection of private investment inflows from China to Africa recently. China needs to exploit Africa’s potential as an emerging market for its tremendous investments by private enterprises. Moreover, the African countries need Chinese investments in various areas to boost aspects of their economies. Private, market-oriented investment calls for an open, stable, secure and predicable investment environment. However, existing bilateral investment treaties (BIT) between China and Africa adopt the protection-oriented, post-establishment model. The treaties merely provide for some general obligations of investment protection, leaving all other matters to the policy discretion of the host state. The China-Africa BIT regime is sporadic, uninformed and incoherent. The conclusion of the Comprehensive Economic and Trade Agreement between the EU and Canada (CETA) develops the idea that China might conclude a standalone BIT with the African countries at a regional or sub-regional level to attract Chinese investment inflows into Africa through an open, coherent and uniformed investment scheme. Given the integration of Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) to be one single jurisdiction over trade and investment, the China-OHADA BIT is the one most likely to be expected. This standalone BIT regime inherently calls for an absolute standard for market access and investment protection, and uniformity to limit the discretion of interpretation, and as such, contribute to a more open, stable, secure and predictable investment climate.
Keywords: BIT regime; China-OHADA BIT; Chine-OHADA TBI; Climat d'investissement; Discrétion politique; Investment climate; Investments; Policy discretion; TBI modèle

Les facteurs d’attractivité des Investissements Directs Etrangers par les Pays en Développement et l’effet modérateur de la qualité des institutions - El Jazouli, Moutia (International Review of Economics, Management and Law Research, 2019)
L’attractivité des investissements directs étrangers (IDE) a fait l’objet de plusieurs recherches empiriques. Beaucoup d’auteurs se sont intéressés aux facteurs qui expliquent l’afflux de ces investissements sur les pays d’accueil. L’effet d’un facteur d’attractivité des IDE change en effet d’un pays à l’autre. Cette recherche examinera l’effet modérateur de la qualité des institutions légales et gouvernementales du pays d’accueil des IDE de la relation entre ces investissements et les facteurs de leur attraction. Les principaux résultats montrent que plus les politiques gouvernementales sont efficaces, que plus la corruption est réprimée, que plus les lois protègent les investisseurs, l’attractivité des IDE est assurée par le marché financier et par la stabilité politique que l’ouverture commerciale s’améliore. Il n’en reste pas moins que les pays qui ont des institutions de qualité supérieure se trouve plus pénalisés en termes d’attractivité des IDE lorsque le poids fiscal sur les entreprises qui y opèrent s’alourdit et lorsque leur taux de change devient plus flexible.
Keywords: Attractiveness factors; Attractiveness of FDI; Attractivité des EDI; Données du panel; Dynamic model in first differences; Effet modérateur; Facteurs d’attractivité; Institutional quality; Investments; Moderating effect; Modèle dynamique; Panel data; Premières différences; Qualité institutionnelle

L'internationalisation des investissements en droit africain OHADA - Kouamen Tatkam, Tatiana (Lex4 Magazine, 2019)
L'internationalisation 1 fait intervenir les notions d'interdépendance 2 , de transnationalité 3 et même parfois un effet d'absence de frontières depuis que le monde est si intégré qu'il semble parfois impossible d'assimiler ou de relever l'origine d'un produit, d'un service ou de façon plus globale des échanges. L'internationalisation de façon plus sommaire fait planer sur le haut des hémisphères une sorte d'existence globale, de réussite visuelle et partant d'imposition d'un art de vivre. De nos jours, l'internationalisation est recherchée par toute entité dans l'exploitation de ses activités ; laquelle se matérialise la plupart du temps dans le cadre d'une entreprise ou d'une société. Ce dernier cas est l'objet d'une organisation structurée entre une ou plusieurs associés qui décident de mettre en commun des moyens matériels et financiers dans le but de profiter du bénéfice ou de l'économie qui pourrait en résulter 4. Cette dernière, à savoir la société, facilite évidemment la prolifération desdites activités dans les quatre coins du monde. Selon le théorème de Coase 5 , la firme a cet avantage qu'elle permet de rassembler tous les actes de confections d'un produit ou d'un service de façon intégrée sous le contrôle d'une structure pour limiter les dépenses et ainsi pénétrer le marché sans souci insurmontable. L'internationalisation fait également intervenir le nominatif multinational 6 et la question de la nationalité de l'entreprise 7. Mais au-delà de toutes ces notions, elle amène 11 Du point de vue étymologique, l'internationalisation s'appréhende comme suit : Du latin inter, entre, parmi, avec un sens de réciprocité et de natio, naissance, extraction, dérivant de natus, né. L'internationalisation est l'action d'internationaliser ainsi que le résultat de cette action. Le verbe "internationaliser" signifie rendre international, faire en sorte que plusieurs nations ou toutes les nations soient concernées. Sur le plan économique, pan qui nous intéresse le plus, l'internationalisation est une stratégie de développement d'une entreprise au-delà de son marché national d'origine. Elle peut se manifester par l'implantation d'unités de production dans d'autres pays ou la conquête de plusieurs marchés nationaux. Cf

Le défi de l'Organisation pour l'harmonisation en Afrique du droit des affaires face au développement des marchés financiers africains: Quid de la protection des investisseurs - Sita, Gloria Lubaki (Recht in Afrika, 2019)
By the time the founding fathers of the Organization for the Harmonization of Business Law in Africa (OHADA) signed the Treaty of Port Louis, the financial markets in Western and Central Africa were embryonic. Nowadays the situation has changed and it seems appropriate to reconsider relationship between OHADA law and securities exchange markets. Indeed, OHADA's Community legislation has to deal with the securities markets covered and serve both the proper functioning of the market and the protection of investors. The uniform Act on Commercial Companies and Economic Interest Groupings contains provisions referring to specific financial rules. However, is this sufficient to earn the public trust? Financial market law is a complex discipline. If we supplement this the effort required for investors to find their way between the West African Economic and Monetary Union (WAEMU) or the Economic and Monetary Community of Central Africa (CEMAC) stock exchange law and national constraints throughout OHADA, the following question must be asked: How is the investor's interest protected in this legal jungle? This paper tries to analyse the legal mechanisms of investor protection in the WAEMU Regional Stock Exchange and the Central African Stock Exchange, combining them with the uniform law for commercial companies of OHADA.

Entry of Foreign Investments: Convergence of International Trade and Investment Law? - Lubambo de Melo, Murilo Otávio (University College London, 2018)
The thesis analyses how public international law regulates the entry of foreign investors and investments into states. It explores the various legal concepts and techniques to limit the freedom of states to accept investments and regulate their access, employed in different regimes of international law. These are: international trade law – mainly illustrated by the WTO (World Trade Organisation) agreements, in particular, the General Agreement on Trade in Services (GATS), and preferential trade agreements (PTAs) – and international investment law (IIL) – scattered through a network of bilateral investment treaties (BITs). The thesis concludes that there are signs that the international rules regulating the entry of investments in services are converging in several levels of alignment and treaty making. Convergence means a reduction of non-shared legal and systemic characteristics or an increase in shared characteristics. Several factors support this conclusion: the progressive incorporation in treaties of establishment rights for investors, that is, commitments by states to allow foreign investments under certain conditions; the narrowing-down of investor-state dispute settlement clauses dealing with entry, which makes IIL systemically closer to international trade law regarding dispute settlement; the hidden liberalising power that flows from the broad interaction of the most-favoured-nation (MFN) clauses in the GATS and IIL with entry provisions; and, the incorporation of concepts and techniques from the international trade law world into investment chapters of larger international economic agreements, such as the GATS absolute standard of market access and its system of exceptions and justifications. These converging signs are considered a natural evolution of the rules given that trade and investment sometimes represent complementary market access strategies in the context of global value chains. The thesis suggests that this move towards convergence may bring about more effectiveness to the rules by attaining the goal of investment liberalisation balanced with the safeguard of regulatory space.
Keywords: Domestic investor; Foreign investment; GATS MFN clause; International Economic Law; International Trade; Investment Law; Investments; Remedies; State-State Investment Arbitration; WTO regulation

The defence of illegality in international investment arbitration : a hybrid model to address criminal conduct by the investor, at the crossroads between the culpability standard of criminal law and the separability doctrine of international commercial arbitration - Busco, Paolo (Sant'Anna School of Advanced Studies ; Université Paris 1, 2018)
Cette thèse analyse la question relative au cas où, dans l'arbitrage international en matière d'investissements, dont le but principal est l'application des normes visées à la protection des investisseurs, l’État défendeur soutient que l'investissement pour lequel la protection est demandée a été obtenu au moyen d'une forme de criminalité. Dans ce contexte, la défense de l'illégalité soulevée par les État dans les contentieux d'investissement est de plus en plus courante. Cette défense fonctionne selon le schéma suivant : un État hôte enfreint les dispositions de fond que le droit international accorde aux investissements effectués dans un pays étranger, par exemple en expropriant un investisseur étranger de son investissement sans indemnité. Dans le différend qui s'ensuit devant un tribunal arbitral d'investissement, l'État défendeur invoque l'illégalité commise par l'investisseur lors de la réalisation de l'investissement pour se défendre contre la procédure arbitrale intenté contre lui. Le but principal de cette étude est celui de démontrer que des considérations systématiques de nature strictement juridique, aussi bien que de politique juridique, exigent que la défense d'illégalité dans l'arbitrage d'investissement soit strictement restreinte et qu'un tribunal ne puisse décliner d'exercer sa compétence / juridiction que dans des cas exceptionnels. Cette étude aboutit à la conclusion d'après laquelle les tribunaux d'arbitrage devraient plutôt examiner au cas par cas au stade du fond l'ensemble des circonstances soumises devant lui et procéder à une mise en balance appropriée entre les comportements de l'investisseur et ceux de l'État hôte. This thesis addresses the question as to how an investment Tribunal is to react if, in the context of a case brought before it for breach of standards of protection of an investment, the respondent argues that the investment for which protection is sought has been secured by resorting to some form of criminality. Against this background, a defence by the Host State that has become increasingly common is the so-called Defence of Illegality. It operates on the basis of the following scheme : a Host State breaches the substantive provision that international law accord to investments made in a foreign Country, for instance by means of expropriating without compensation the investor's investment. In the ensuing dispute before an investment Tribunal, the defendant Host State raises the illegality committed by the investor in the making of the investment as defence against the breach of the substantive provisions on the protection of the investment, of which it is accused, to avoid responsibility. This thesis intends to demonstrate that both legal and policy consideration dictate that the Defence of Illegality in investment arbitration should be strictly curtailed and that a Tribunal should only decline to exercise its jurisdiction in exceptional cases. Rather, Tribunals should look at the entire set of circumstances at the merits stage and perform a proper balancing test between the conduct of the investor and the Host State.
Keywords: Admissibility and jurisdiction; Admissibilité; Approche comparée; Arbitrage; Arbitrage commercial; Arbitrage d'investissement; Arbitrage et crime; Arbitrage international; Arbitragem; Arbitration; Arbitration and crime; Clause de légalité; Clean hands doctrine; Commercial Arbitration; Comparative law; Compétence; Compétence juridictionnelle; Corruption; Defence of Illegality; Doctrine des mains propres; Défense d'illégalité; Investment arbitration; Investments

La rentabilité de l'investissement dans la responsabilité sociale d'entreprise "RSE" : pourquoi et comment ? - Espinassouze, Aline-Laure (CY Cergy Paris Université, 2018)
Selon le modèle théorique de la « RSE stratégique », la responsabilité sociale des entreprises, définie comme un investissement dans la qualité des relations avec les parties-prenantes stratégiques de l’entreprise, s’intègre dans la logique économique de l’entreprise. Partant de l’hypothèse d’une corrélation universellement positive entre RSE et FI, la question se pose du processus et du contexte par lesquels cette création de valeur s’effectue : si la RSE est un investissement rentable, peut-on expliquer pourquoi et comment ?La base de données Gaïa-Index mise à disposition par l’agence de notation RSE française EthiFinance permet d’étudier cette question sur une population d’entreprises françaises cotées de taille moyenne (N=230) durant la période 2011-2013. Les résultats sont en cohérence avec le consensus théorique et empirique sur la RSE stratégique et montrent que le « facteur humain » est un élément fondamental du processus de création de valeur permettant d’associer performance RSE et performance financière.
Keywords: CSR; Capital humain; Employee turnover; Human capital; Investissements; Investments; Performance; RSE; Strategy; Stratégie; Turnover

Le développement durable dans les traités régionaux africains d'investissement : cas de la CEDEAO et de la SADC - Koula, Bablésson Mardochée Désiré (Université de Bordeaux, 2018)
L’appréhension du tandem développement durable – traité d’investissement a longtemps été perçue sous l’angle de la contradiction. En effet, bien qu’il existe un consensus sur l’importance des investissements en tant que vecteur du développement durable, les seuls instruments internationaux qui leur sont spécifiquement dédiés [les traités d’investissement] font généralement peu, ou pas, cas de cet objectif ; ceux-ci étant conçus dans le seul but d’assurer une protection élevée des investisseurs et leurs investissements. Toutefois, depuis une décennie, on voit émerger au sein des organisations régionales africaines de nouveaux modèles de traités d’investissement dont l’unique but est de promouvoir les investissements qui soutiennent le développement durable. Ce changement de paradigme, qui prône désormais la compatibilité du régime juridique de l’investissement transnational avec les exigences sociales et environnementales, n’est cependant pas sans soulever des interrogations. Parmi celles-ci se pose la question de savoir comment l’engagement en faveur du développement durable est concrètement traduit dans ces traités régionaux. L’interrogation est capitale, surtout lorsqu’on sait les difficultés qui entourent l’analyse du développement durable, concept et objectif à la fois multidimensionnel et évolutif. À cet égard, l’étude des instruments de la CEDEAO et de la SADC témoigne de la prise en compte du développement durable à un double niveau. D’abord, l’adaptation, à travers l’aménagement des clauses traditionnelles des traités d’investissement (PARTIE I). Ensuite, l’innovation, par l’introduction de dispositions jusque-là inexistantes dans la pratique conventionnelle (PARTIE II). The understanding of the tandem of sustainable development and investment treaty has long been seen in terms of contradiction. Indeed, although there is a consensus on the importance of investments as a vehicle for Sustainable Development, the only international instruments specifically dedicated to them [investment treaties] generally pay little or no attention to this objective; they are designed with the sole aim of ensuring high protection for investors and their investments. Over the past decade, however, new models of investment treaties have emerged in African regional organizations with the sole aim of promoting investments that support sustainable development. However, this paradigm shift, which now advocates the compatibility of the legal regime of transnational investment with social and environmental requirements, raises some questions. Among these is the question of how the commitment to sustainable development is concretely reflected in these regional treaties. The issue is crucial, especially when one considers the difficulties surrounding the analysis of Sustainable Development, a concept and objective that is both multidimensional and evolving. In that regard, the study of ECOWAS and SADC instruments reflected the consideration of Sustainable Development at two levels. First, adaptation, through the amendment of the traditional clauses of investment treaties (Part I). Secondly, innovation, through the introduction of provisions which had not previously existed in Treaty practice (Part II).
Keywords: Africa; Afrique; Communauté économique des États de l'Afrique de l'Ouest; Durable; Développement durable; Investissements; Investments; Regional; Southern African Development Community; Sustainable; Traités; Treaties

La protection juridique des investissements directs étrangers dans les pays en développement : l'exemple de l'Afrique de l'Ouest - Fall, Cheikh Lo (Université de Bordeaux, 2018)
Les IDE sont au cœur de la mondialisation et des rapports Economiques Nord-Sud. La question de leur protection et de leur régulation juridique se pose avec acuité. Devant la rareté des autres sources de financement du développement et d’accès à la technologie, l'IDE constitue une source importante pour combler l'insuffisances des ressources internes. raison pour laquelle, les pays d'Afrique de l'ouest se livrent à une concurrence farouche pour les accueillir. Dans la sous région ouest africaine le droit et la réglementation sont utilisés comme des instruments importants pour mesurer l'attractivité et la sécurité juridiques des pays. Le sujet s'interroge, analyse la dimension sécuritaire(traitement et garantie) a t'elle permise une plus grande promotion et d'accueil des IDE?. Notre sujet tentera d'analyser et situer l'effectivité du régime juridique des investissements étrangers au plan interne( codes des investissements, codes miniers et codes pétroliers). Mais aussi au plan externe( Traité bilatéraux d'investissement TBI,conventions sectoriels de protection arbitrage et garantie). Le dernier axe de ce travail de recherche, est le phénomène de la Communautarisation de la protection avec les tentatives d'harmonisation et d'uniformisation des réglementations nationales en Afrique de l'Ouest. Le dernier aspect, c'est l'institutionnalisation à travers les Organisations Economique Internationales (Banque Mondiale et Banque Africaine de développement BAD) du système juridique de protection en Afrique de l'Ouest. "The protection of foreign direct investment in developing countries: the example of West Africa" FDI is at the heart of globalization and north-south economic relations. The question of their protection and legal regulation is acute. Faced with the scarcity of other sources of development finance (development aid) and the difficulties of access to technology, FDI is an important resource for filling the insufficiency of internal resources. This is why African countries in general, and those in West Africa in particular, are competing vigorously to receive foreign capital by providing them with an attractive, secure and non-discriminatory legal and institutional framework. Indeed, in the West African subregion, the law is used by States, but also by subregional integration organizations such as ECOWAS as an important instrument for demonstrating economic attractiveness. Thus, the analysis and measurement of the legal and institutional framework for FDI in West Africa will be discussed. In other words, has the security dimension of the investment (reception, processing, guarantee and settlement of disputes etc.) allowed for greater promotion and reception of investments from these countries?The interest of the subject is multiple. Indeed, at the legal and academic level, it allows to know, analyze and situate the entire legal regime of foreign investment at the internal level (investment code, mining code, oil code). At the external level, there is a multitude of conventions - such as bilateral BIT investment treaties -, accession to the relevant international investment conventions, and of course the increasingly visible and visible role of Community law in through the "communitisation of the law of foreign direct investment". The study of this subject shows the deep gap that exists between theory and practice in the FDI legislation of the countries of this part of Africa. If, upstream, the texts are more or less similar to those of the advanced countries, downstream, the execution of the texts by the public administrations makes mediocre the environment and the practice of the businesses. This theme on the legal protection of investments raises other questions and issues such as: the intervention of more and more actors and the instruments negotiated within them (World Bank, ADB, WTO, OECD, ECOWAS and UEMOA). etc.). There are also new issues related to environmental issues, corporate social responsibility and heritage issues. Finally, the problems posed by new types of investment, particularly PPP public-private partnerships, will be studied. The current nature of the research is striking, as there are several issues related to investment protection in countries such as West Africa. It is about the transfer of technology in a new context, the industrialization by the natural resources, the contribution on the development of the host country and the creation of jobs especially in an international context where Africa became again attractive.
Keywords: Afrique de l'Ouest; FDI; Foreign investment; Ide; Investissements; Investissements étrangers; Investments; Juridique; Protecting; Protection; West africa

Les émanations de l'État à vocation économique dans l'arbitrage des investissements et dans le contentieux de l'O.M.C - Cortesi, Giulio Alvaro (Université Paris 1 ; Università degli Studi di Padova, 2018)
L'idée de cette thèse sur le droit international des investissements concernant les entreprises d'État trouve son origine dans l'impressionnant développement économique de ces dix dernières années. D'une part, ce dernier donne une pertinence considérable à ce thème compte tenu de son actualité. D'autre part, il existe un intérêt considérable pour les problèmes juridiques laissés en suspens par ces entités. Cette thèse commence par un chapitre préliminaire dans lequel la forme juridique de ces institutions est analysée, à la fois avec une évaluation empirique et du point de vue du droit national et international applicable à ces sujets. L'analyse empirique approfondie qui n'a pas encore été réalisée dans les recueils de contributions examinés s'est révélée fondamentale, car certaines des questions juridiques concernant les entreprises d'État ne pourraient vraiment pas être abordées sans une telle approche. Le corps plus juridique de la thèse, consacré uniquement à l'analyse juridique, est composé de trois parties et présente deux principaux pôles d'intérêt : le premier est lié à la compréhension des implications juridiques de ces entités et le second, plus large, vise à comprendre le traitement qui a été réservé à ces organes dans les différends examinés. Ce traitement peut nous renseigner au niveau systémique sur le droit international des investissements, qui a également nécessité une comparaison ciblée avec l'arbitrage commercial et avec le droit commercial international. The idea of a thesis on state enterprises in international investment law finds its roots in their impressive economic development during the last decade, which, on one hand, gives considerable relevance to this theme given its inherent actuality and, on the other hand, there is a considerable interest in the juridical problems that these entities leave open. The thesis consists of a preliminary chapter, were the legal form of these institutions has been analyzed, from both an empirical assessment and the standpoint of national and international law applicable to these subjects. The empirical, in-depth analysis, not yet reached in the collections of examined contributions, turned up as fundamental, because some of the legal issues concerning state enterprises cannot really be tackled without such an approach. The more juridical body of the thesis, devoted only to legal analysis is composed of three parts and has two main poles of interest: the first linked to the understanding of the legal implications of these entities and a second, and, wider one, aimed at understanding what the treatment of these bodies, occurred in the dispute cases examined, can tell us at a systemic level about international investment law, which has required also a targeted comparison with commercial arbitration and international trade law.
Keywords: Contentieux d'investissement; Contentieux fiscal; Contentieux économique; Economic litigation; Entreprises publiques; Finances publiques; Fond souverain; Investment arbitration; State enterprises

La protection internationale des investissements étrangers en Afrique de l'ouest : espace CEDEAO (Communauté Économique des États de l’Afrique de l’Ouest) - Diop, Papa Abdoulaye (Université Côte d'Azur, 2018)
La protection internationale des investissements étrangers dans la Communauté Économique des Etats de l’Afrique de l’Ouest (CEDEAO) suppose d’établir la compétence de celle-ci à assurer une sécurisation des biens des opérateurs économiques ressortissants d’Etats tiers dans son espace. Ainsi, il a été démontré que, par le biais de ses instruments de réalisation de l’intégration régionale, cette organisation communautaire pourrait être amenée à assurer une sécurisation des investissements étrangers. Mais, quoique fusse grande la volonté de la CEDEAO d’assumer une telle fonction, l’analyse démontre qu’elle présente certaines insuffisances qui sont intrinsèquement liées à la différence de nature entre le droit communautaire et le droit conventionnel des investissements. Face à ce constat, il urgeait de trouver d’autres instruments supplétifs, voire complémentaires dans la protection communautaire des investissements étrangers. Ces dits instruments ont été localisés dans le droit international général, tant à travers ses règles substantielles que ses mécanismes procéduraux. Cependant, si la protection que procure le droit de la CEDEAO sur les biens des investisseurs étrangers a été jugée inefficace, celle du droit international, en revanche, semble excessive au point d’être préjudiciable aux Etats hôtes, si tant qu’elle nécessite un nivellement. À l’examen, l’observateur pourrait avoir la sensation qu’il existe un bras de fer entre le droit international et le droit communautaire dans la sécurisation des biens des opérateurs économiques étrangers. Cet observateur constatera ensuite que le droit de la protection des étrangers entre dans une nouvelle ère. En effet, longtemps limitée dans le cadre bilatéral entre Etat d’origine et Etat d’accueil de l’investissement, la problématique de la sécurisation des investissements étrangers a acquis une telle acuité dans la vie économique des entités étatiques qu’elle tend à devenir une affaire de communauté. Il se rendra, enfin, surtout compte que, si le droit conventionnel des investissements a pour visée la protection des étrangers, il peut, à certains égards, constituer un stimulant à la bonne gouvernance. The international protection of foreign Investments within the Economic Community of West African States (ECOWAS) requires establishing the competence of the latter to ensure the security of the property of economic operators who are nationals of third States in its area. Thus, it has been shown that through its instruments for achieving regional integration, this community organization could be led to ensure the security of foreign investments. But, although ECOWAS’s willingness to assume such a function is great, the analysis shows that it has certain shortcomings which are intrinsically linked to the difference in nature between Community law and the Conventional law of investment. In this view, it was urgent to find other supplementary and even complementary instruments in the community protection of foreign investments within the community. These instruments have been localized in General International Law both through its substantive rules as in its procedural mechanics. However, while the protection afforded by ECOWAS law to the properties of foreign investors has been found to be ineffective, that of the international law, on the other hand, seems excessive to the point of being detrimental to host States, as long as it requires leveling. On examination, the observer might have the feeling that there is a tug of war between International law and Community law in securing the assets of foreign economic operators. This observer will then note that the law of the protection of foreigners enters a new era. Indeed, for a long time limited in the bilateral framework between the State of origin and the host States of the investment, the issue of securing foreign investments has acquired such acuity in the economic life of the State entities that it is tends to become a community affair. Finally, i twill be appreciated that, while the purpose of conventional investment law is the protection of foreigners, it may, in some respects, be a stimulus to good governance.
Keywords: Afrique occidentale; Arbitrage commercial international; Arbitrage d'investissement; Bilateral Investments Treaties; CEDEAO; CIRDI; Communauté économique des États de l'Afrique de l'Ouest; Droit international; Droit international des investissements; ICSID; International Investment Law; Investissements étrangers

Defragmenting Investment disputes: Multilateral Court of Investment Disputes as a Panacea? - Kidane, Brook Bekele (Revue juridique des étudiants de la Sorbonne, 2018)
Never was there a time whereby investment dispute settlement came to the forefront of every possible communication outlet, from academia and mainstream news to civil societies and an outright protest of the public. TTIP and CETA brought ISDS to a broad daylight scrutiny in many parts of Europe getting the attention of law and policy makers at EU and national level. The criticisms and anxiety over ISDS relates to divergent interpretation of similar or identical International Investment Agreements (IIAs) provisions that lead to inconsistency and unpredictability of decisions, lack of transparency in investment disputes, lack of independence and impartiality of arbitrators, the elite group of arbitrators, costs, diversions of public money from public goods and services, ‘chilling effect’ on state regulatory powers and bypassing national judicial systems.; With a view to establish and tackle the problem with a meaningful solution to the legitimate concerns and anxieties, the EU, with its competence to conclude the Investment Agreements, attempted to create two mechanisms. The inclusion of Investment Court System (ICS) in newly concluded IIAs and the creation of a multilateral investment court.; This article will assess the three systems together, i.e. the ISDS, ICS, and the multilateral investment court, in terms the pros and cons and attempt to envisage the policy shortcomings or benefits under any of the systems. Jamais il n'y a eu une époque où le règlement des différends en matière d'investissement a été au premier plan de tous les moyens de communication possibles, qu'il s'agisse d'universitaires, de la presse grand public, de la société civile voire d’actions publiques. La TTIP et la CETA ont permis à l'ISDS de faire l'objet d'un examen minutieux dans de nombreuses parties de l'Europe, attirant l'attention des législateurs et des décideurs politiques au niveau européen et national. Les critiques et l'anxiété à l'égard de l'ISDS ont trait à l'interprétation divergente de dispositions similaires ou identiques des accords internationaux d'investissement (AII) qui conduisent à l'incohérence et à l'imprévisibilité des décisions, au manque de transparence dans les différends en matière d'investissement, au manque d'indépendance et d'impartialité des arbitres, à l'élite des arbitres, aux coûts, aux détournements de fonds publics des biens et services publics, à l'"effet paralysant" sur les pouvoirs réglementaires des États et au contournement des systèmes judiciaires nationaux. En vue d'établir et d'aborder le problème avec une solution significative aux préoccupations et aux inquiétudes légitimes, l'UE, avec sa compétence pour conclure les accords d'investissement, a tenté de créer deux mécanismes. L'inclusion de l'Investment Court System (ICS) dans les AII nouvellement conclus et la création d'un tribunal multilatéral de l'investissement. Cet article évaluera les trois systèmes ensemble, c'est-à-dire le SIPDS, le SCI et le tribunal multilatéral de l'investissement en termes d'avantages et d'inconvénients et tentera d'envisager les lacunes ou les avantages de l'un ou l'autre des systèmes.

Political risk in energy-related investment disputes - Sahin, H. (The World Arbitration and Mediation Review (WAMR), 2018)
The energy industry is a key source of growth stimulation for developing states. This is true not only in terms of economic growth, but also in terms of the transfer of knowledge and skills as well as the provision of employment opportunities. Understandably, developing states are well-disposed towards international investors, and are eager to enter into petroleum investment contracts with the expectation that this will bring the aforementioned benefits to their countries particularly where the host state is less able to act as a provider of such resources autonomously. On a global scale, regardless of their type, all investments face risks. These risks are volatile in nature and reach as the world economy globalises. It is, of course, true that political risk phenomena per se are potentially destructive to all industries. However, it is fair to say that due to its high stakes, the energy industry is more acutely exposed and subject to political risk than most sectors. The purpose of this article is to examine political risk, particularly direct expropriation risk, in long-term energy investment projects. This paper will refer to arbitral decisions with regard to expropriation cases, as well as the valuation techniques applied by the investment arbitration tribunals in unlawful expropriation cases.
Number: 3 https://irep.ntu.ac.uk/id/eprint/41477/

A critical analysis of the security of foreign investments in the Southern African Development Community (SADC) region - Ngobeni, Tinyiko Lawrence (University of South Africa, 2018)
Foreign investments in SADC are regulated by Annex 1 of the SADC Protocol on Finance and Investments (SADC FIP), as well as the laws of SADC Member States. At present, SADC faces the challenge that this regime for the regulation of foreign investments is unstable, unsatisfactory and unpredictable. Furthermore, the state of the rule of law in some SADC Member States is unsatisfactory. This negatively affects the security of foreign investments regulated by this regime. The main reasons for this state of affairs are briefly explained below. The regulatory regime for foreign investments in SADC is unstable, due to recent policy reviews and amendments of key regulatory instruments that have taken place. Major developments in this regard have been the suspension of the SADC Tribunal during 2010, the amendment of the SADC Tribunal Protocol during 2014 to bar natural and legal persons from access to the Tribunal, and the amendment of Annex 1 during 2016 to remove investor access to international investor-state arbitration, better known as investor-state dispute settlement (ISDS). The regulation of foreign investments in SADC has been unsatisfactory, among others because some SADC Member States have failed or neglected to harmonise their investment laws with both the 2006 and the 2016 Annex 1. Furthermore, SADC Member States such as Angola, Democratic Republic of Congo (DRC), Malawi, Mauritius, Seychelles, Eswatini, Tanzania, Zambia, and Zimbabwe have multiple Regional Economic Community (REC) memberships. This places these Member States in a position whereby they have conflicting interests and treaty obligations. Finally, the future of the regime for the regulation of foreign investments in SADC is unpredictable, due to regional integration efforts such as the recent formation of the COMESA-EAC-SADC Tripartite Free Zone (T-FTA) and the African Continental Free Trade Area (AfCFTA). The T-FTA is entitled to have its investment protocol, while the AfCFTA investment protocol will be negotiated from 2018 until 2020. These developments entail that the 2016 Annex 1 will soon be replaced by an investment protocol at either the T-FTA or AfCFTA levels, thereby ushering a new regime for the regulation of foreign investments in SADC. The unknown nature of the future regulations create uncertainty and instability among foreign investors and host states alike. This study analyses the regulation of foreign investments in terms of Annex 1 and selected laws of SADC Member States. In the end, it makes the three findings mentioned above. In order to address these findings, the study makes four recommendations. The first is that foreign investments in SADC must be regulated at African Union (AU) level, by means of an AfCFTA investment protocol (which incidentally is now the case). Secondly, investor-state disputes must be referred to the courts of a host state, optional ISDS, the African Court of Justice and Human Rights (ACJ&HR) or other agreed forum. Thirdly, an African Justice Scoreboard (AJS) must be established. The AJS will act as a gateway to determine whether an investor-state dispute shall be referred to the courts of a host state, ISDS, the ACJ&HR or other forums. Fourthly, the office of an African Investment Ombud (AIO) must be created. The AIO shall facilitate the early resolution of investor-state disputes, so as to reduce the number of disputes that may end-up in litigation or arbitration.
Keywords: ACH&PR; AfCFTA; African Continental Free Trade Area; African Court for People and Human Rights; African Court of Justice and Human and Peoples' Rights; African Court on Human and Peoples' Rights; African Justice Scoreboard; African Union; COMESA; Commercial treaties; Customs unions; Dispute resolution; EAC; Expropriation; Foreign economic relations; Foreign investment; Free Trade Agreement; ICSID Arbitration Rules; International commercial arbitration; Investments; Investor-State Dispute Settlement; SADC; SADC Protocol; Southern African Development Community; State Responsibility; UNCITRAL Arbitration Rules

Contrats internationaux en Algérie : applicabilité des conventions fiscales au service de l'investissement - Kaloune, Salah (Aix-Marseille, 2018)
L'Algérie a engagé une politique de libéralisation de son économie et cherche à intégrer l’économie mondiale pour sortir de sa dépendance des hydrocarbures et diversifier son économie. Une politique incitative est mise en place pour accueillir les investissements direct étrangers qui constituent un enjeu majeur pour l’accroissement des échanges, le transfert de technologie, la mise à niveau des sociétés locales et la création d’emploi. D’un autre côté la mise en place d’une économie de marché exige un environnement juridique efficace et stable qui définit clairement les droits et obligations des opérateurs économiques notamment en matière de conclusion de contrats. Le cadre théorique que nous retenons pour répondre à cette question est l’analyse de la place des conventions fiscales dans l’ordre fiscal algérien et sa corrélation avec la politique de promotion des investissements. Les conventions fiscales sont telles réellement au service de l’investissement ? Pour ce faire nous avons mis en exergue tout au long de nos développements l’examen des conventions fiscales à l’épreuve des contrats internationaux permettant d’améliorer la lisibilité et la transparence de la norme fiscale afin de favoriser l’attractivité du territoire
Keywords: Algérie; Attractivity; Attractivité; Attractivité (géographie); Contrats internationaux; Conventions fiscales; Double imposition (traités); FDI; Foreign direct investment; International contracts; Investissement direct étranger; Investissements étrangers; Investments; Permanent establishment; Tax treaties; Établissement stable

A critical analysis of the legal environment in respect of the private equity industry in South Africa - Oaker, Wentzel (Stellenbosch University, 2018)
This dissertation aims to answer a fundamental question relating to the South African legal and economic framework in which private equity operates. This being: To what extent does the law address/regulate the structure of private equity funds and the relationships between the various parties related to a fund, that is: investors, the fund manager and underlying portfolio investments? This thesis also discussed how the law could better regulate the private equity industry. The dissertation consists of five chapters. Chapter one raises such fundamental questions as ‘what is the nature of private equity?’ by looking at the parties involved, the private equity cycle, returns, liquidity, the risk, and the private equity market. In addition, it assesses whether private equity satisfies the criteria to be regarded as a separate asset class. Chapter two provides an analysis of the key features of private equity fund formation in South Africa. The choice of the most appropriate legal structure of a private equity fund starts with the choice of the most effective and suitable legal vehicle. Chapter two includes a discussion of the general private equity fund structure, the regulatory requirements of private equity firms, and certain regulatory considerations relevant in operating a private equity fund in South Africa. The discussion at certain instances reference private equity fund formation in foreign jurisdictions such the US, UK, Australia, and Canada. Chapter three introduces an analysis of corporate governance as it pertains to private equity funds. Firstly, it discusses the role of corporate governance regulation in stimulating investment. Secondly, it discusses the importance and benefits of corporate governance from the perspective of private equity managers; and seeks to explain the link between the private equity business model and corporate governance that is based on the assertion that there are two levels of corporate governance involved in private equity investing. The first level of governance relates to the private equity fund’s underlying portfolio investee companies and this includes inter alia, a discussion on the duties of the fund manager, particularly in their capacity as serving as directors on the boards of such companies. The second level of governance relates to the private equity fund itself which focuses on the relationship between the private equity firm and the investors that invest in the private equity fund. Chapter four examines two key impediments namely tax legislation and exit alternatives; and show how legislation could effectively address the former and how the lack of exit routes is an impediment to the growth of the local private equity industry. Chapter five states that, the development of the above mentioned regulatory framework will only be successful if the private equity industry participants themselves acknowledge and actively address the disadvantages and real risks posed by the private equity industry on the South African financial system.
URI: http://hdl.handle.net/10019.1/103466
Keywords: Investments; Private equity; Private equity funds; South Africa; Taxation

Les efforts de la CNUDCI pour accroitre le niveau de transparence dans l’arbitrage d’investissement - Belhadj, Miriana (Revue de l'ERSUMA, 2018)
Récemment, la Commission des Nations Unies pour le Droit commercial international (CNUDCI) a adopté deux instruments sur la transparence dans l’arbitrage entre investisseurs et États fondé sur des traités. Un Règlement adopté en 2013, prévoit des règles spécifiques pour compléter tout règlement d’arbitrage choisi pour régir un arbitrage conduit sur la base d’un traité d’investissement. Ces règles prévoient notamment, et sous certaines conditions, la publication d’informations et de documents relatifs à l’affaire. Elles permettent aussi que des observations soient présentées par les tiers ou par une partie au traité non partie au litige. Une Convention adoptée en 2014 met en place un mécanisme efficace permettant aux États de prévoir l’application du Règlement sur la transparence à leurs traités d’investissement antérieurs à l’entrée en vigueur du Règlement. À la date de cet article, la Convention compte cinq États parties, dont deux États africains (18 autres États, dont 3 États africains, l’ont signée) et est entrée en vigueur le 18 octobre 2017. Ces efforts de promotion de la transparence dans l’arbitrage d’investissement ont été suivis de discussions au sein de la CNUDCI aboutissant à ce qu’un nouveau groupe de travail au sein de la CNUDCI soit chargé de réfléchir à une possible réforme du système de règlement des différends entre investisseurs et États (RDIE). Dans le cadre de ces réflexions politiques et techniques de haut niveau, la question de la place de la transparence – autre que la transparence procédurale – est récurrente à plusieurs égards et inévitablement au cœur des débats.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; CNUDCI; Investissements; Investments; Transparence; Transparency

L’arbitrage comme mode de règlement des différends dans les codes d’investissements des Etats membres de l’UEMOA - Djigle, Doundongue (Revue de Recherches en Economie et en Management Africain, 2018)
Dans le but d’attirer les investissements directs étrangers, les Etats membres de l’UEMOA ont adopté des codes d’investissements destinés à régir les relations entre investisseurs et Etats. Ces codes privilégient l’arbitrage comme mode de règlement des différends. Mais le fondement de cet arbitrage n’est pas le même dans chacun des codes. Certains codes comportent directement dans leur corpus la clause d’arbitrage que l’investisseur peut activer en cas de survenance d’un litige, tandis que d’autres renvoient à des sources extérieures, tel un contrat d’investissement ou un traité bilatéral d’investissement liant l’Etat d’accueil avec l’Etat d’origine de l’investisseur. En outre, dans leur pratique, les Etats de l’UEMOA donnent souvent le choix aux investisseurs entre différentes instances arbitrales. Pourtant, peu de procédures d’arbitrage sont engagées contre ces Etats sur le fondement des codes nationaux d’investissement.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Code des investissements; Etats membres.; Investissements; Investments; Offre d’arbitrage; UEMOA

Factors Influencing Indian Firms Decision Making In Foreign Direct Investment In Africa - Kukreja, Mukta; Joshi, Mahesh Chandra (International Journal of Applied Business and International Management, 2018)
India's economic progress and relations with other developing regions have received much attention, particularly the way in which Indo-African relations have evolved since 2000. This paper aims to put Indian FDI in Africa into perspective and provide some answers on the nature and possible impact of these flows to the continent. The study utilized the International typology offered by Dunning OLI paradigm to identify the important of Location Specific Advantages and how these advantages leads to selection of location for investment purposes by investors The study findings demonstrated that potential market growth, market opportunities and consumer base are the important indicated Indian firms targets Africa to seek new and unexplored markets of Africa. Competitiveness climate is important determinant along with economies of scale, investment incentives and availability of natural resources.
Keywords: African nations; Developing countries; FDI; India; Indo-Afro relations; Investments; Multinational companies; OLI eclectic paradigm

Shareholders' claims for reflective loss in international investment arbitration - the rule and its demystification - Vanhonnaeker, Lukas (McGill University, 2018)
In recent years, investor-State tribunals have often permitted shareholders' claims for reflective loss despite the well-established principle of no reflective loss applied consistently in domestic regimes and in other fields of international law. Investment tribunals have justified their decisions by relying on definitions of "investment" in investment agreements that often include "shares", while the no-reflective-loss principle is generally justified on the basis of policy considerations pertaining to the preservation of the efficiency of the adjudicatory process and to the protection of other stakeholders, such as creditors. Although these policy considerations militating for the prohibition of shareholders' claims for reflective loss also apply in investor-State arbitration, they are curable in that context and must be balanced with policy considerations specific to the field of international investment law that weigh in favor of such claims: the protection of foreign investors in order to promote trade and investment liberalization.
https://escholarship.mcgill.ca/concern/theses/s1784p10r
Keywords: Arbitrage; Arbitragem; Arbitration; International Arbitration; International Investment Arbitration; Investments; Reflective loss; Shareholder claims

الاطار القانوني للاستثمار العربي في الجزائر - عبد الصدوق, حفيظة (Université d'Oran 2 Mohamed Ben Ahmed, 2018)
للاستثمار العربي في الج ا زئر أهمية خاصة لسببين: أحدهما يتعلق بأهمية الاستثمار في حد ذاته لما يلعبه من دور لا يستهان به في التنمية الاقتصادية للدولة، مؤث ا ر على كل جوانب الحياة في المجتمع بما يوفره من تطور اقتصادي وازدهار واستق ا رر، وثانيهما يرتبط باتخاذه وسيلة لتجسيد التعاون العربي المشترك وتحقيق التكامل المنشود منذ عقود، والذي تأكد عدم تحققه الا بالاعتماد على المدخل الإنتاجي من خلال توظيف رؤوس الأموال العربية في الدول العربية. بدافع هذين العاملين وجذبا لرؤوس الأموال العربية وضعت الج ا زئر اطا ا ر قانونيا ا زخ ا ر بالضمانات والامتيا ا زت بعد تحديد مفهوم الاستثمار العربي، هذا الإطار يتألف من الاحكام الاتفاقية السامية على التشريع الوطني الواردة في الاتفاقيات المبرمة بين الج ا زئر والدول العربية بعد المصادقة عليها، ومن احكام التشريع الوطني الذي يعد آلية قانونية تنفذ بها الدولة است ا رتيجياتها. ت ا زمن ذلك مع تهيئة مناخ الاستثمار بصفة عامة من خلال الإصلاحات التي طالت مختلف التشريعات المتعلقة بإقامة الاعمال اولاستثمار في الج ا زئر. جاءت هذه الد ا رسة لتبين معالم هذا الإطار القانوني، مكوناته ومدى تأثيره في رفع مست وى الاستثمار العربي في الج ا زئر كما ونوعا، ضمن مشاريع التكتل الإقليمي والجهوي او المبادلات الثنائية مع الدول العربية.
Keywords: Accords bilatéraux; Algeria; Arab Nationality; Arbitrage; Arbitration; Bilateral Agreements; Blocage; Blocking; Business Establishment; Compensation; Création d'entreprise; Encouragement; Garanties; Guarantees; Investissements; Investment Protection; Investments; Nationalité arabe; Privileges; Privilèges; Protection des investissements

Les obligations internationales de l’Etat d’accueil d’un investissement étranger et leur sanction dans l’ordre juridique international - Edouard, Régis (Université Paris 10, 2017)
L’encadrement, par le droit international, du comportement de l’État hôte d’un investissement étranger n’est concevable que dans la mesure où sa souveraineté est limitée, l’enjeu étant la sanction de l’inobservation, par cet État, de ses obligations. Ces dernières sont issues de la pratique conventionnelle, surtout bilatérale, regroupant des traités qui disposent au fond. L’«internationalisation» du régime juridique de l’investissement n’est pas exclue comme mode de formation d’obligations mais ne se produit qu’à la faveur de dispositions dotées d’un tel effet. La pratique conventionnelle, assez uniforme, a comme principale caractéristique l’articulation de règles limitant le besoin d’interprétation autour de standards qui l’amplifient. Ceci, de même que les interprétations arbitrales, autorise à soupçonner une volonté de « remembrement » du standard minimum international. Si l’attribution d’un comportement à l’État d’accueil ne pose pas de difficulté inédite, l’établissement d’une violation, par cet État, de « ce qui est requis de lui » révèle des singularités de ce domaine. La qualification des circonstances excluant l’illicéité en situation d’urgence peut s’avérer problématique, le risque étant omniprésent d’une méconnaissance, de la part des arbitres, de la logique du droit de la responsabilité. En dehors de ces situations, on peut imaginer des hypothèses dans lesquelles l’illicéité est exclue suite au consentement de l’État d’origine ou de l’investisseur. Le préjudice subi par ce dernier, objet de la réparation intégrale due par l’État responsable, constitue le « préjudice causé par le fait internationalement illicite ». Il est immédiat et direct. L’investisseur, titulaire du droit d’invocation de la responsabilité de l’État hôte, a accès à une réclamation internationale qui éclipse celle de son État de nationalité. La perspective d’un endossement, par ce dernier, de la réclamation de son national accroît l’efficacité des traités d’investissement. For the conduct of a foreign investment’s host State to be governed by international law is only conceivable insofar as its sovereignty is limited, since the issue is the sanction of the failure of that State to fulfill its obligations. The latter results from a mostly bilateral treaty practice embodying treaties which contain material provisions. The “internationalization” of the legal regime of an investment is not excluded as a means to create obligations, but only occurs through provisions with such an effect. The main characteristic to this fairly uniform treaty practice is the development of rules limiting the need for interpretation around a core set of standards amplifying it. This, as well as the arbitral interpretations, may reflect a desire to “consolidate” the international minimum standard. If the attribution of conduct to the host State does not raise any unprecedented issue, the establishment of a violation by that State of “what is required of it” reveals singularities in this field. The characterization of circumstances precluding wrongfulness in an emergency situation may prove problematic, as the risk that arbitrators may ignore the logic of the law of responsibility is omnipresent. Apart from these situations, it is possible to imagine hypotheses in which wrongfulness is precluded due to the consent of the State of origin or the investor. The injury sustained by the latter, which is the subject of full reparation due by the responsible State, constitutes “injury caused by the internationally wrongful act.” It is immediate and direct. The investor, entitled to invoke the responsibility of the host State, has access to an international claim which eclipses that of his State of nationality. The prospect of an espousal by the latter of its national’s claim increases the effectiveness of the investment treaties.
Keywords: Arbitrage transnational; Foreign investment; International responsibility; Investissement étranger; Investissements étrangers (droit international); Investment treaty; Investments; Obligation primaire; Obligations internationales; Primary obligation; Responsabilité internationale; Souveraineté; Sovereignty; Traité d’investissement; Transnational arbitration; État (responsabilité)

Recherche sur la notion d'investisseur protégé par le droit international - Atanasov, Ognyan (Université Paris 1, 2017)
A la différence d'autres catégories de personnes privées, comme par exemple celle des commerçants qui, s'ils peuvent tirer profit des règles internationales mises en place par les États relatives au libre exercice du commerce, n'ont généralement pas la capacité de se prévaloir à titre individuel des droits leur conférant ces règles dans l'ordre international, l'investisseur est devenu aujourd'hui destinataire direct d'un nombre important d'instruments conventionnels, et dispose grâce aux mécanismes de règlement des différends prévus par ces derniers d'un droit d'action individuel à l'encontre des États étrangers. Par le terme « investisseur», les conventions de protection des investissements étrangers désignent aussi bien les individus que les personnes morales. Traditionnellement, en contentieux interétatique, un État ne peut exercer sa protection diplomatique qu'en faveur de ses nationaux, à condition cependant que l'individu ne possède pas en outre la nationalité de l’État destinataire d'une telle réclamation. Le droit conventionnel des investissements a apporté une certaine évolution en la matière. D'une part, de plus en plus de traités étendent leur application non seulement aux nationaux des États contractants, mais également aux individus ayant établi leur résidence sur le territoire de ces derniers. D'autre part, certaines conventions prévoient expressément que lorsqu'un individu-investisseur dispose à la fois de la nationalité de l'un des États contractants d'un traité et de celle d'un autre État contractant, contre lequel il entend adresser une réclamation, c'est la nationalité la plus effective de la personne physique qui doit conditionner la recevabilité de sa demande au niveau international. Concernant le régime de protection des personnes morales, en contentieux de la protection diplomatique la Cour internationale de Justice accorde uniquement à l’État où est constituée la société, le titre pour agir en sa faveur à l'encontre d'un autre État. Cette règle a été très critiquée au motif que souvent l’État d'incorporation d'une société, contrôlée par des ressortissants d'un autre État, n'a pas toujours un intérêt suffisant pour défendre les droits de celle-ci vis-à-vis d'un troisième État auteur d'une mesure préjudiciable pour cette société. L’État réellement intéressé par un recours serait plutôt celui de nationalité des associés de la personne morale lésée. En tenant compte de ce dernier constat, le droit conventionnel des investissements a conféré la capacité aux associés d'une société lésée pour agir en protection des actifs de cette dernière, sans pour autant remettre en cause la qualité à agir de la société pour la protection de ces mêmes biens et avoirs. Lorsque le titulaire d'un investissement est une personne morale, celle-ci n'est alors plus perçue comme un seul investisseur, mais comme une pluralité d'investisseurs potentiels. La société peut être traitée soit comme une personne juridique unique, soit comme une addition des personnalités de tous ses associés, détenant directement ou indirectement son capital, et disposant le cas échéant de nationalités différentes, et donc de titres juridiques multiples leur permettant d'agir à l'encontre de l’État ayant porté atteinte à l'investissement réalisé par une telle personne morale.
Keywords: Clause de déni des bénéfices; Corporate law; Droit des sociétés; Droits des associés; International law; Intérêt social; Investissements étrangers (droit international); Investisseur; Investments; Investors; Nationality; Nationalité; Rights of the associates; Résidence; Société

Contractual renegotiations and International investment arbitration : a relational contract theory interpretation of investment treaties - Florou, Aikaterini (Institut d'études politiques, 2017)
The relationship between international investment treaties and the underlying contracts remains a highly disputed matter in international investment law. This thesis explored the contract-treaty interaction by using the renegotiation of regulatory contracts in the sector of energy infrastructure as a natural experiment, with a particular emphasis on the arbitral disputes that arose from the Argentine crisis. It deployed to this end an original analytical framework drawing from transaction cost economics and relational contract theory. The result of the novel combination of these two analytical frameworks is the construction of an interpretative methodology that takes an integrated approach to the two instruments – the contract and the overarching treaty – in a way that achieves a more sustainable balance between the competing public and private interests. In particular, the thesis rests on three arguments: the first is the relational-contract nature of dynamic treaty standards, which require the long-term cooperation of the parties. The second is the status of these vague standards as default rules complemented by the provisions of the underlying contracts, which are also relational, and act as gap-fillers. The last, normative argument is that the relationship between these (default) treaty rules and the (gap-filling) contractual provisions should be determined by transaction cost economics, and specifically the goal of economizing on the transaction costs of bounded rationality and opportunism when and interpreting relational treaty standards. La relation entre les traites internationaux d’investissement et les contrats sous-jacents reste un sujet très contentieux dans le domaine du droit international de l’investissement. Cette thèse explore l’interaction entre le contrat et le traité en utilisant la renégociation des contrats règlementaires dans le secteur de l’infrastructure énergétique comme un exemple d’ « expérience naturelle », en se focalisant en particulier sur les litiges arbitraux découlant de la crise économique en Argentine. A cette fin, un cadre analytique original, s’inspirant de l’économie des coûts de transaction et la théorie du contrat relationnel. Le résultat de la combinaison originelle de ces deux cadres analytiques est la construction d’une méthodologie interprétative proposant une approche d’intégration entre les deux instruments – le contrat et le traité – d’une manière apportant plus d’équilibre entre les intérêts publics et privés souvent opposés. La thèse est fondée en particulier sur trois arguments : le premier est la nature des standards dynamiques des traités comme contrats relationnels exigeant la coopération des parties à long terme. Le deuxième est le statut de ces standards vagues comme règles par défaut, complémentés par les provisions des contrats sous-jacents, qui sont aussi relationnels et fonctionnent comme « gap fillers ». Le dernier argument, normatif, est que la relation entre ces règles (par défaut) des traites et les provisions contractuels doit être déterminée par l’économie des coûts de transaction, et en particulier le but d’économiser les coûts de transaction découlant de la rationalité limitée et l’opportunisme durant l’interprétation des standards relationnels des traités.
Keywords: Arbitrage commercial international; Contrats internationaux; Economie des coûts de transaction; Interprétation des traités; Relational contract theory; Théorie du contrat relationnel; Transaction cost economics; Treaty interpretation

Le règlement par voie d'arbitrage des litiges relatif aux investissements dans l'espace OHADA - Kenfack Douajni, Gaston (Revue juridique de l'Océan Indien, 2017)
Keywords: Arbitrage; Arbitragem; Arbitration; Clause compromissoire; Commission des Nations Unies pour le droit commercial international (CNUDCI); Contrat; Convention d'arbitrage; Exequatur; Investissements; Investments; Jurisprudence arbitrale; Loi nationale; Organisation pour l'harmonisation en Afrique du droit des affaires (OHADA); Règlement des litiges; Sentence arbitrale; Traité de protection des investissements

Conflict of treaty-norms in investment arbitration - Atanasova, Dafina (Université de Genève, 2017)
The study analyses the process through which investment arbitral tribunals identify and resolve conflicts between investment standards of protection and norms from other international regimes relevant for the merits of the dispute. It questions the validity behind the current approach that tribunals adopt, under which arguments based on extraneous norms are overwhelmingly unsuccessful and proposes its' transformation in three respects. First, rather than being a mere means of interpretation, as in current practice, a broader pool of international norms must be applied to the substance of investment disputes. Second, the concept of normative conflict must be broadened if one is to address the actual challenges that inter-regime conflicts pose for international law. Third, fleshing out the modalities under which one could use private international law as a source of inspiration in public international law context, the study offers best practices for approaching the types of conflict commonly found in investment disputes.
Keywords: Arbitrage; Arbitrage d'investissements; Arbitragem; Arbitration; Diversification; Droit international; Droit international privé; Fragmentation; International courts and tribunals; International law; Investissements; Investment arbitration; Investments; Private international law

Foreign Direct Investment and Economic Development in Africa - Adegboye, F. B.; Ojo, Joshua A. T.; Olokoyo, F. O. (Journal of Internet Banking and Commerce, 2017)
Africa unlike other developing regions of the world has experienced declining flows of foreign direct investment (FDI).The flow of FDI is expected to result into gradual reduction in reliance on external borrowed capital and acceleration of economic development. The study examined the declining flow of FDI to the African regions as well as the impact that it has had on economic development of the region, using the proxies of Income per capita, Life expectancy and Education indices. The study made use of pooled data from thirty nine African countries within the period 1993 and 2012.The method of analysis utilized for the study was the fixed effect least-square dummy variable model, employed to estimate the impact of foreign direct investment on economic development for the selected host African countries. The study finds that foreign direct investment is statistically significant in relation to economic development for host African countries. It is therefore recommended that the governments of host countries should consider closely the sectors that FDI flows into, encourage investment domestically in such sectors such that dependence on external financial flows could be reduced, resulting in sustained increases in income, literacy level and hence improved life expectancy which are expected to result into sustained economic development.
Number: 1 http://www.icommercecentral.com
Keywords: Economic Development; Foreign direct investment; Host African Countries; Income Per Capital; Investments; Life Expectancy

Comportement des entreprises en matière d’investissements immatériels : état des lieux et déterminants en contexte camerounais - Gonne, Jérôme; Feudjo, Jules Roger (La Revue Gestion et Organisation, 2017)
Résumé Les facteurs de compétitivité des entreprises dans la nouvelle économie ont changé de nature, passant des éléments physiques aux éléments immatériels. L’objectif de cette communication est donc d’analyser les spécificités des entreprises au Cameroun en matière d’investissements immatériels. Les données de l’étude ont été collectées auprès d’un échantillon de 78 entreprises opérant dans divers secteurs d’activité au Cameroun. Les résultats obtenus soulignent que les investissements immatériels font désormais partie intégrante des habitudes des entreprises camerounaises. Quelques actifs issus de ces investissements y trouvent un marché florissant. Cependant, on peut déplorer dans la majorité de ces entreprises un faible niveau d’investissements immatériels et une déficience de la qualité de l’information comptable et financière relative à ce type d’investissements. Nous relevons par ailleurs que, contrairement à l’intensité immatérielle, la qualité de l’information sur les immatériels semble dépendre de certains facteurs caractéristiques de l’entreprise. The factors of competitiveness of companies in the new economy have changed in nature from physical elements to intangible elements. The purpose of this communication is therefore to analyze the specificities of companies in Cameroon relating to intangible investments. The study's data was collected from a sample of 78 companies operating in various industries in Cameroon. The results emphasize that intangible investments are now part of the habits of Cameroonian companies. Some assets from these investments find in Cameroonian context a flourishing market. However, it is regrettable that the majority of these companies have a low level of intangible investment and impairment of quality of accounting and financial information for this type of investment. We further note that, contrary to the intangible intensity, the quality of information on intangibles seems to depend on some characteristic factors of the company.
Keywords: Accounting information; Cameroon; Cameroun; Companies; Entreprises; Information comptable; Intangible investments; Investissements; Investissements immatériels

Intégration régionale et investissements directs étrangers en Afrique - Mama, Hamimida (Revue Interventions économiques, 2017)
Le continent africain, un grand importateur de denrées alimentaires, connait des épisodes de crises alimentaires. En même temps et paradoxalement, les accords étrangers de leasing de terres sont en hausse depuis 2001. Les avantages que les investissements directs étrangers (IDE) procurent ne sont pas automatiques et ne profitent pas de manière égale aux pays d’origine et aux pays d’accueil. Souvent pour ces derniers, quand il s’agit de pays en développement ou des pays les moins avancés, la c...

Investissements d’accord, mais financement d’abord - Zogning Nguimeya, Felix (Revue Interventions économiques, 2017)
Les banques en Afrique subsaharienne ne possèdent toujours pas de système d’informations leur permettant d’accéder au dossier de crédit des opérateurs économiques qui sollicitent un financement. Si les experts, observateurs et investisseurs s’accordent sur le fait que l’heure est résolument à l’Afrique, que son immense potentiel augure des investissements prometteurs, il reste que le continent n’a toujours pas trouvé le véhicule de financement idéal pour soutenir, voire accélérer sa croissanc...

Financial Development, Integration and Access to Finance in Africa - Essien, Grace Etim (University of Leeds, 2017)
This thesis is made up of three empirical studies that fall under the general classification of international and financial economics, particularly the study focuses on the financial system of selected African countries. The first empirical study presented in Chapter 2 examines the role of financial development in improving the effect of FDI on the economic growth of some African countries. Investigations were conducted to pinpoint which financial structure could provide the best improvement by applying the bank-based vs. market-based debate. Results from the regression analysis conducted show that the effect of FDI on economic growth becomes significant only when financial development measures were factored in. Analysis of results indicate that development of the overall financial system of African countries would be more beneficial in comparison to developing either the banks or financial markets alone. Chapter 3 empirically measures the level of financial integration in Africa’s Regional Economic Communities (RECs) using beta and sigma convergence to measure the speed and degree of financial integration in four RECs. These chapter also theoretically examines how regional financial integration contributes to financial development and economic growth in Africa. Analysis of the results show that Africa’s RECs are integrating at a relatively slow and diverse rate. Therefore, policy makers in Africa would need to focus on reform strategies that would strengthen financial integration in their regions. A fully financially integrated system would contribute immensely to financial development and promote sustainable economic growth. The fourth chapter investigates the effect of access to finance on firms’ productivity. Using cross-sectional firm-level data to estimate the effect of access to finance on labor productivity, total factor productivity (TFP), and the stochastic frontier trans-log model. This study estimates an instrumental variable (GMM) model to address potential endogeneity bias between access to credit and firms’ productivity. The results obtained show that the lack of access to finance negatively affects the productivity of firms in Africa. This study suggests that the development of a balanced financial system should be of topmost priority to policy makers. This ensures that more finance is channelled towards those firms whose productivity depends heavily on the availability of finance irrespective of their characteristics. This would result in firms increasing their investments in productivity-enhancing activities, which would benefit long-term economic growth

China's legal obligations in the field of foreign investment : how trade agreements influence the formation of investment agreements? - Hua, Yuting (European University Institute, 2017)
Since deeper 'open-door' domestic reform in 1992, China has consistently maintained its position as the largest foreign direct investment (FDI) recipient among developing countries. In recent years China is going global as well. Accompanied with a large amount of outbound FDI, the level of debt is also increasing. Thus it is necessary for China to adopt a sustainable development policy and behave based on rules. China needs to work with the world to promote a rules-based investment climate. At a multilateral level, China joined the World Trade Organization (WTO) in 2001 and promised general and specific obligations on market entry and non-discrimination principles. Bilaterally, only after 2001, China has started negotiating preferential trade agreements (PTAs). The first part of the thesis analyses China’s legal obligations in investment agreements in pre- and post-WTO entry phases. Chapter 1 introduces China’s investment policy before 2001. Chapter 2 clarifies China’s commitments on non-discrimination principles under the WTO agreements, especially China’s Protocol of Accession. Chapter 3 compares Chinese BITs and PTAs with regard to investment principles. The second part of the thesis concerns interpretation on substantive and procedural provisions. Chapter 4 tries to answer the question of whether and how do tribunals consider jurisprudential concepts developed in the case law of the trade regime when resolving investment cases. Chapter 5 examines different remedies in trade and investment agreements. It is important for China to keep compliance with its commitments in international agreements, otherwise, it would face countermeasures which are highly costly. Also, China can implement competition rules in its domestic market for improving firms’ efficiency. Meanwhile, a balancing approach which emphasizes corporate social responsibility is equally important for China’s companies going global.
Keywords: Foreign investment; Foreign trade regulation; WTO; World Trade Organization

L'Etat dans l'arbitrage d'investissement - Ranjeva, Hery Frédéric (Revue juridique de l'Océan Indien, 2017)

The responsibility of private actors in the internal market : private actors taking over? - Trommer, Jan (European University Institute, 2017)
The picture presented and often referred to in EU internal market law and legal scholarship is clear. Within the internal market private actors are the recipients of rights and public authorities are constrained in their (regulatory) powers. The notion of this new individualism is bound up with capacities, powers, and resources that empower private actors to engage in the internal market and cross-border situations; ultimately serving the objectives the internal market seeks to attain. Yet, within thinew individualism a conceptually different class of private actors has emerged that is constrained in economic freedoms, i.e. through obligations, rather than being empowered in the context of the internal market. This thesis will enquire the reasons that led to the development of this counter-culture. Why did it emerge? To what extent does this phenomenon affect the roles of private actors in the internal market? I will demonstrate that under the counter-culture private actors are responsibilized and transformed into ‘competent authorities’, i.e. alternative forms of regulatory authority, in the internal market. Private actors are placed into systems of shared responsibilities the relationships of which are coordinated by EU internal market law. In this regard, the concept of responsibility will serve as a tool to bridge the gap between the new positions EU internal market law allocates to private actors and the emerging legal consequences, i.e. allocation of obligations or tasks. The legal contexts of EU free movement law, EU discrimination law, EU food safety law and EU data protection law will serve as case studies against which the construed conceptual framework will be tested. Under the counter-culture the new individualism is no longer only about the exercise of self-interests. Rather, this form of the new individualism comes with a requirement to give account to the interests of other actors within the internal market.
Keywords: Commercial law; European Union countries; Free Trade; Trade regulation

Le droit des investissements internationaux vu par la CIJ et le CIRDI - Tanon, Abédjinan M. Sandrine (Université de Bordeaux, 2016)
Le droit des investissements internationaux est largement présenté au travers de la jurisprudence arbitrale, notamment celle du CIRDI. Une telle approche a paru insuffisante. En effet, dans l'examen des questions touchant le droit des investissements internationaux, la jurisprudence de la CIJ et de sa devancière semble être un passage obligé à certains égards. S'agissant de règles primaires, c’est dans la jurisprudence de la Cour qu’ont émergé et pris forme certaines règles substantielles relatives aux investissements internationaux, et dont la désuétude est loin d'être établie par l'avènement du CIRDI. Par ailleurs, le rôle général de la Cour dans le fonctionnement de l'ordre juridique international à travers les règles juridictionnelles, procédurales, d’interprétation ou encore de responsabilité internationale, est indéniable. Or, certaines de ces règles se présentent comme des chapitres incontournables du droit des investissements internationaux. Ce sont là autant de raisons qui ont conduit à entreprendre une étude sur Le droit des investissements internationaux vu par la CIJ et le CIRDI en l’abordant au travers de la question de savoir si les tribunaux CIRDI puisent dans l’héritage de la Cour sur les problématiques juridiques relatives aux investissements internationaux ou s’en départissent. La confrontation des jurisprudences de la Cour et des tribunaux CIRDI a permis de conclure que le droit des investissements internationaux vu par la CIJ n’est que partiellement le droit des investissements internationaux vu par les tribunaux CIRDI. Globalement, sur une problématique donnée, en même temps que certaines solutions retenues par la jurisprudence des tribunaux CIRDI dénotent un emprunt aux règles et principes posés par la Cour, d’autres s’en départissent, qu'il s'agisse des règles primaires en la matière, ou bien des règles secondaires du droit international dans leur déclinaison dans le cadre du droit des investissements internationaux. Parce qu’elle livre, entre autres, une vue d’ensemble de la jurisprudence de la Cour de la Haye en matière d’investissements internationaux – démarche inédite –, la thèse se présente comme une piste pour les arbitres sur le chemin de l’émergence d’une jurisprudence arbitrale cohérente en droit des investissements internationaux.
Keywords: Applicable law; CIJ; CIRDI; Centre international pour le réglement des différends relatifs aux investissements; Consentement; Contrats d'état; Cour internationale de justice; Coutume; Custom; Droit applicable; Droit des investissements internationaux; Equitable treatment; Expropriation; Fair treatment; Foreign investment; Full protection; Full security; ICJ; ICSID; International Investment Law; International responsability; Investissements étrangers; Investments; Minimum standard of treatment; Most favoured nation treatment; National treatment; Pleine protection et sécurité; Protection des actionnaires; Responsabilité internationale; Shareholder protection; Standard minimum de traitement; State contracts; Traitement de la nation la plus favorisée; Traitement juste et équitable; Traitement national

Le cadre fiscal de l'investissement français en Tunisie - Amor, Mehdi (Université Toulouse 1 Capitole, 2016)
Le cadre fiscal de l’investissement français en Tunisie tend à assurer la liberté d’investissement et renforcer l’ouverture de l’économie tunisienne à l’étranger en assurant un traitement non discriminatoire envers les investissements français en Tunisie. Il contient notamment des règles d’incitations fiscales qui couvrent la majorité des secteurs. Toutefois, ce cadre fiscal n’est pas suffisant pour promouvoir l’investissement français en Tunisie.
Keywords: Conditions économiques; Droit fiscal; Investissements; Investissements français; Investissements étrangers; Investments; Tunisie

La protection internationale des investissements en République démocratique du Congo à l’aune de l’affaire Patrick Mitchell devant le Centre International pour le Règlement des Différends relatifs aux Investissements (CIRDI) - Djuma Bilali, Lokema Guy-Prosper (KAS African Law Study Library, 2016)

Effets des institutions sur les investissements directs étrangers dans les pays de l'UEMOA : une approche par le méthode de panel ARDL - Bagaga, Mamoudou (Université Cheikh Anta Diop, 2016)
Dans un monde globalisé et fortement concurrentiel, les économies sont à la recherche permanente de capitaux en vue de renforcer leur tissu industriel, gage d'une croissance soutenue au service du développement et de l'emploi. Dans ce sens, une frange importante de chercheurs et de praticiens s'accordent sur l'importance du cadre institutionnel. Or les pays de l'Union économique et monétaire ouest africain (UEMOA) disposent d'un cadre institutionnel peu performant. Et à cela s'ajoute la faiblesse des flux de capitaux directs étrangers qu'ils enregistrent. Ces capitaux seraient d'ailleurs concentrés dans des secteurs peu productifs. C'est pourquoi, cette thèse se propose d'analyser l'influence de la qualité des institutions dans l'attractivité et l'efficacité des investissements directs étrangers (IDE) des pays de l'UEMOA. A cet effet, nous avons développé un modèle théorique inspiré de Feng & Chen (1997) pour analyser les mécanismes en jeu. Ainsi, dans le but de réduire d'une part, les problèmes d'endogénéité des variables explicatives notamment des variables institutionnelles, et d'autre part, de se conformer aux caractéristiques de notre échantillon et de capter les dynamiques de court terme et de long terme, la méthodologie utilisée pour les estimations des modèles empiriques est celle des modèles de panel Autorégressifs à Retards Echelonnés (ARDL). Avec une prédominance des relations de long terme entre les différentes variables, trois principaux résultats émergent de cette thèse. D'abord, une amélioration de la qualité des institutions (corruption, crises socio-politiques, démocratie, respect de la loi et de l'ordre) a permis d'attirer davantage d'investisseurs privés étrangers. Ensuite, le faible développement des institutions s'est accompagné d'un comportement de recherche de rente accru des dirigeants provoquant une éviction de certains investisseurs locaux par ceux étrangers. Enfin, ces insuffisances institutionnelles dans les pays de l'UEMOA ont atténué les effets d'entraînement sur la croissance économique qu'auraient pu avoir les IDE. Face à ces conclusions, il urge pour chaque pays de l'Union de se pencher sérieusement sur des politiques de réformes de leurs institutions notamment à travers la promotion de la démocratie, tant au niveau national qu'au niveau communautaire. Ces politiques devraient favoriser non seulement l'attractivité des IDE, mais aussi la complémentarité de ces derniers avec les investissements privés locaux.
Keywords: ARDL panel; Croissance économique; Domestic private investment; Economic growth; Foreign direct investment; Investissement direct étranger; Investissement domestique privé; Investments; Modèle de panel ARDL; UEMOA; WEMU

Commerce international et investissements directs étrangers : complémentarité ou substituabilité ? - Tayara, Saeed (Université de Poitiers, 2016)
Ce travail étudie, théoriquement et empiriquement, l'interaction entre le commerce international et l'investissement direct étranger (IDE), interaction qui a été un des principaux canaux de la mondialisation économique et de l'essor des chaînes de valeur mondiales dans la segmentation des activités de production. Les modèles théoriques montrent que le commerce international et les IDE peuvent se développer dans une relation de substituabilité ou de complémentarité. La nature de cette relation peut être la conséquence de facteurs exogènes, déterminants de la spécialisation des pays, ou le résultat de la stratégie endogène des firmes dans l'organisation de leurs activités à l'international. La validation empirique s'appuie sur une adaptation du modèle de gravité, en appliquant les techniques économétrique sur données de panel sur des données bilatérales pour la France au cours de la période de 1993 à 2012. Les estimations mettent en évidence une relation de complémentarité entre le commerce et l'IDE au niveau le plus agrégé. Cependant, une analyse comparative à un niveau plus désagrégé permet de trouver des indices de substituabilité et de complémentarité selon les groupes de pays partenaires.
Keywords: Commerce extérieur; Commerce international; Complementarity; Complémentarité; Données de panel; Entreprise multinationale; Entreprises multinationales; Foreign direct investment; Gravity model.; International Trade; Investissement étranger direct; Investissements étrangers; Modèle de gravité; Modèles économétriques; Multinational firm; Panel data; Substituabilité; Substitutability

A rights-based approach to foreign agro-investment governance in Cameroon, Uganda and South Africa - Ashukem, Jean-Claude Nkwanyuo (North-West University, 2016)
The practice of foreign agro-investment (FAI) for the production of food crops and biofuel crops has been a recent phenomenon in sub-Saharan Africa and other developing countries. In fact, the present era of climate change has caused foreign countries to acquire vast tracts of land - often through multinational corporations - in order to propagate biofuel or expand their home industries abroad. Practices of FAI have resulted in a form of land grabbing, as local communities are often evicted from their land without their consent. FAI activities are reported to have considerable impact on people in areas where they occur, which range from environmental to social and economic impacts. There is compelling evidence that FAI land deals are not transparent and inclusive, which raises pertinent concerns with respect to participatory rights, access to information, the compatibility of property rights, environmental protection and the protection of the rights and interests of local communities generally, among other issues. The lack of respect for and protection of local communities’ rights and interests during FAI land deals and activities form the crux of this study. In this light, the overall aim of this thesis is to investigate and ascertain how the procedural aspects of a rights-based approach (RBA) could be used to provide adequate protection to local communities’ rights and interests during FAI activities in Cameroon, Uganda and South Africa. The study is premised on the notion of a RBA to FAI governance and captures the procedural aspects of the right to access to information, public participation and the right to access to justice in international, regional, sub-regional and national human rights legal regimes. It is argued that because these rights have the potential to significantly contribute towards the protection of the rights and interests of people that are adversely affected by development activities, their incorporation remains useful and relevant in the FAI context. It is further claimed that the implementation of the procedural RBA in FAI land deals could strengthen the ability and capacity of the state to increase opportunities for more meaningful dialogue with local communities, while concomitantly helping the state to fulfil its international and national obligations as a duty-bearer to respect, protect and fulfil the rights and interests of its people. In addition, procedural rights encompass elements of good governance and democracy and could be used as a necessary and vital tool to prevent a government’s exercise of arbitrary power generally and in the context of development activities. This is predicated on the belief that procedural rights serve inter alia to strengthen democratic structures and processes and to curb corruption and the mismanagement of national resources, and ultimately to promote sustainable development. In this study, it is argued that a RBA generally and its procedural aspects specifically could play an important role in setting the standards and defining the processes that are appropriate to repudiate the unacceptable impacts of FAI and simultaneously address distributive concerns with the hope of promoting and ensuring more responsible and sustainable FAI. Conversely, the absence of such a normative baseline suggests that large-scale land transfer under the guise of FAI practices would endlessly levy an unacceptable toll on the fundamental rights of the vulnerable host population. The first step in this thesis is to analysis the theoretical concepts of governance and good governance in order to establish the eventual objective of what FAI governance and good FAI governance should entail. A further component of the theoretical analysis includes an analysis of a RBA and a RBA to FAI governance. These components are investigated in order to determine a possible solution to the impacts of FAI activities from a rights-based perspective. Second, the thesis investigates and analyses the procedural aspects of a RBA espoused in international, regional and sub-regional legal regimes. It distils generic characteristics and minimum requirements of the RBA for good FAI governance to be used as benchmarks in the context of project development-related activities, including FAI. As benchmarks, the international, regional and sub-regional legal regimes provide minimum criteria to which the legal frameworks of countries must adhere to and conform with. This part also examines the procedural RBA frameworks in Cameroon, Uganda and South Africa and critically evaluates the legal frameworks in these countries against the distilled generic characteristics and minimum requirements of the RBA in terms of good FAI governance. Third, the thesis concludes with a set of recommendations on the procedural RBA frameworks in Cameroon, Uganda and South Africa. These recommendations are meant to address the current lacunae in these domestic procedural RBA frameworks, and to propose measures designed to enable a situation where the rights and interests of local communities are better protected in the event that FAI land deals are concluded.
Keywords: ACCESS TO INFORMATION; ACCESS TO JUSTICE; Foreign agro-investment; Good governance; Land grabbing; Procedural rights; Public participation; Rights-based approach

Foreign Direct Investments and Economic Growth of African Regions: A Comparative Study - Igbinosa, Sunday O.; Ikponmwosa, Noruwa Abu (UNILAG Journal of Humanities, 2016)
The paper examines the impact of Foreign Direct Investments (FDIs)on economic growth in the five regions of Africa, as well as identifies their respective drivers of growth. It employs the Ordinary Least Squares (OLS) multiple regression analysis to examine the relative impact of Foreign Direct Investments, balance of payments, trade openness, technology and quality of labour force on economic growth in each of the five regions between 1980 and 2012. The study finds that foreign Direct Investments (FDIs) have no significant impact on economic growth in the five regions of Africa. The impact of FDI on growth is positive in Eastern, Middle and Western Africa but negative in Northern and Southern Africa. Similarly, there are differentials in the drivers of growth in the five regions. While trade openness is a negative driver of growth in all regions of Africa except in Northern Africa, both balance of payments and quality of labour force have mixed impacts on economic growth in Africa. In addition, technological progress impacted growth in Middle, Southern Africa and Western Africa but it appears that lack of it retarded growth in Eastern and Northern Africa. The study calls for policy reform frameworks that encourage and boost foreign Direct Investment flows to all regions of Africa, particularly Direct Investments in critical sectors of the economies, as well as check the negative effects of foreign Direct Investments. Furthermore, it recommends that regional economic blocks in Africa should be resuscitated and supported to develop and promote intra-Africa trade and Investments.
Keywords: African regions; Drivers of growth; Economic growth; FDI; Foreign direct investment; Investments

Attractivité économique des investissements directs étrangers en zone CEMAC : harmonisation des instruments juridiques aux règles internationales - Memphil Ndi, Evelyne Patience (Université de Nice Sophia-Antipolis, 2015)
Les courants de la mondialisation des marchés, marqués par la libre circulation des capitaux et le phénomène du libre-échange ont favorisé la mise en œuvre de politiques communautaires de relance économique et d’attractivité des territoires. C’est dans cette lancée que des regroupements géographiques à visée économique comme la Communauté Économique et Monétaire de l’Afrique Centrale (CEMAC) sont apparus. Six pays de l’Afrique Centrale dont le Cameroun, le Congo, le Gabon, la Guinée Equatoriale, la République Centrafricaine et le Tchad en sont membres et font l’objet de notre analyse sur l’attractivité économique de l’investissement Direct étranger (IDE) dans cette sous-région. L’IDE est devenu un acteur incontournable du processus de développement, et la zone CEMAC une destination privilégiée pour les investisseurs. Il apparait néanmoins une ambiguïté dans les rapports entre le flux d’IDE, la croissance économique et le développement des pays membres de la CEMAC : le taux sans cesse croissant des flux d’IDE entrants dans la sous-région, n’est malheureusement pas toujours synonyme de croissance économique. Pour comprendre ce paradoxe, l’on procède à une analyse des instruments encadrement de l’IDE dans la sous-région CEMAC. Il en ressort que, pour un rendement optimal de ces dispositifs et la garantie d’une croissance économique à long terme dans ces États, il est nécessaire d’associer les politiques actuelles d’attractivité économique des IDE, à une diversification des domaines économiques exploitables , mais aussi adapter les standards internationaux aux spécificités socioculturelles mais aussi économiques de la sous-région CEMAC. The currents of the globalization of the markets, marked by the free movement of capital and the phenomenon of free trade supported the implementation of Community policies of economic revival and attractivity of the territories. It is in this impetus that geographical regroupings with economic aiming like the Economic community and Monetarist of Central Africa (CEMAC) appeared. Six countries of Central Africa of which Cameroon, Congo, Gabon, Equatorial Guinea, the Central African Republic and Chad are members and are for it, the object our analysis on the economic attractivity of direct foreign investment (FDI) in this under-area. The FDI became an inevitable actor of the development process, and CEMAC zones, a privileged destination for the investors. It appears nevertheless an ambiguity in the relationship between the flow of FDI, the economic growth and the development of the member countries of the CEMAC : the rate unceasingly crescent of flows of FDI entering the under-area, is unfortunately not always synonymous with economic growth. To understand this paradox, one carries out an analysis of the instruments framing of the IDE under-area CEMAC. This reveals that, for an optimal output of these devices and the warranty of one long-term economic growth in these States, it is necessary to associate the current policies of economic attractivity of the FDI, with a diversification of the exploitable economic domains, but also to adapt the international standards to sociocultural but so economic specificities of under-area CEMAC. The case of the countries of the BRICS can in this respect, being used as illustration for an “other way” of thinking the development.
Keywords: Afrique centrale; Attractivité économique; Communauté Economique et Monétaire de l'Afrique Centrale; Conditions économiques; Economic attractivity; Foreign direct investment; Harmonisation; Harmonization; Investissements directs étrangers; Investissements étrangers

Determinants and Growth Impact of Foreign Direct Investment in West African Economic and Monetary Union (1980-2010) - Laleye, Abimbola Nicaise (University of Lagos, 2015)
This study’s aim is to assess the trends and the macroeconomic determinants of FDI and to estimate its impact on economic growth, using West African Economic and Monetary Union (WAEMU) and its member countries (Benin, Burkina Faso, Cote d’Ivoire, Guinea Bissau, Mali, Niger, Senegal and Togo) as a case study. In order to achieve the objectives of the current study, the panel cointegration method is employed for the period that expands from 1980 to 2010. This method is constituted of three steps: first, running the panel unit root tests; secondly, run the panel cointegration tests to establish a long-run relationship between the included variables; and thirdly, to run the two models of this study. All this is supplemented by Granger causality test in order to determine the direction of causality between the two variables of FDI and economic growth in WAEMU and its member countries. The findings show that: (i) the variables market size, trade openness, human capital, infrastructure development, financial development, macroeconomic stability, exchange rate and political stability are significant determinants of FDI in WAEMU and in its member countries; (ii) not all the variables affect the same way FDI inflows in WAEMU and in each one of the WAEMU member countries; (iii) there is a positive relationship between FDI and economic growth which implies that FDI stimulates economic growth in WAEMU and its member countries; (iv) this study finds a causality relationship between FDI and economic growth, which runs from FDI to economic growth not from economic growth to FDI: meaning there is a unidirectional linkage between FDI and economic growth in WAEMU; (v) the study also finds that at cross-sectional level, FDI only causes economic growth, not the opposite: this implies that there is also a unidirectional linkage between FDI and economic growth in each WAEMU member country and its runs from FDI to economic growth. Therefore, it is important that the enabling environment should always be provided not only in WAEMU but also in its member countries in order to attract more foreign direct investment and further to stimulate the xiv country’s economic growth. Thus, this study recommends the followings, at the local or country level: first, improvement of the image of WAEMU countries. Rapid economic growth could result in an increase in foreign direct investment inflows, not only in WAEMU but in each one of the WAEMU member countries. But, this has to be done with more attention given to conditions (i.e. key variables) such as fair trade policy with abroad, development of infrastructure and financial system, availability of human capital through a sound human training and formation. At regional or WAEMU level, governments should set up policy that guaranties macroeconomic stability and political stability.
https://ir.unilag.edu.ng/handle/123456789/4079
Keywords: Co-integration; Determinants of FDI; FDI; Foreign direct investment; WAEMU; West African Economic and Monetary Union

Policy Options for Promoting Foreign Direct Investment in the Least Developed Countries - Sauvant, Karl P.; Mallampally, Padma (Transnational Corporations Review, 2015)
Foreign direct investment (FDI) plays an important role in the world economy and has the potential to contribute towards accelerating the process of economic growth and sustainable development in the least developed countries (LDCs). The paper provides a brief overview of recent trends and patterns in FDI flows to the LDCs, and then takes stock of the policies, programmes and measures pursued by host and home countries and by international organizations to stimulate FDI flows to LDCs and increase their benefits for these countries. It then lays out a number of policy proposals on how flows to LDCs, and the benefits associated with them, can be enhanced. Finally, it outlines some options for international action to strengthen such efforts – proposals and options that are also relevant to other developing countries.
Keywords: Development; Foreign direct investment; Least Developed Countries; policy options

Arguments in favour of reconceptualising the fair and equitable treatment (FET) standard in international investment arbitration : developing countries in context - Islam, Rumana (University of Warwick, 2015)
The Fair and Equitable Treatment (FET) standard is the most important and, because of its flexible nature and its status as a ‘catch-all’ provision, most controversial investment protection standard in international investment treaties. The standard imposes the most far-reaching obligation of any aspect of such treaties. This thesis’ core contention is that the current investment tribunals’ interpretation of the FET standard prioritises the interests of foreign investors and neglects the perspectives of host developing countries. Therefore there is a pressing need to reconceptualise the interpretation of the FET standard. In service to depicting the perspectives of host developing countries, this thesis advances an understanding of classifications such as ‘developing’ and ‘developed’ that reflects the issues and challenges that these countries face in the investment dispute context, such as their lack of resources, administrative capacity, technology, and infrastructure, as much as the economic and social level of development international organisations generally emphasise in their classifications. It addresses socio-political circumstances such as political instability, social unrest, conflict and its aftermath, social and political transition, and economic crises and their impact on host developing countries in the investment dispute context. Through a detailed study of the approaches they have taken to such issues in their interpretation of the breach of FET standard in disputes involving host developing countries, it shows that current investment tribunals have taken inconsistent and inadequate approaches to the issues host developing countries face. It argues that a reconceptualised interpretation of the FET standard which acknowledges the developmental issues and challenges this thesis has identified would accommodate the needs of the host developing countries while continuing to give reasonable protections to foreign investors and therefore serve the needs of the system as a whole.
URI: http://webcat.warwick.ac.uk/record=b2766071~S1
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Developing countries; Dispute resolution (Law); Equity; Foreign investment; Free trade agreemtment; International business enterprises; Investments; Unfair competition

Convergence of international trade and investment law in practice : how should investor-state arbitral tribunals engage with trade norms? - Chevry, Jonathan (European University Institute, 2015)
This thesis aims to provide an analytical framework to which investor-State arbitral tribunals can refer in cases where international trade law is invoked. The starting point of the present study is the trend in commentary on international trade and investment law, which makes the argument that international trade and investment law should be reconciled due to the clear "convergence" between (some of) their constitutive elements. This convergence argument is not misguided: there are similarities between the underlying principles of global trade and investment and, as such, a better coordination of these principles would be helpful for several reasons. Such reasons include legal certainty, reduction of transaction costs, better coherence in the operation of international agreements that now combine both trade and investment provisions, to name a few. However, no matter how reconcilable or converging the two disciplines may be, their enforcement mechanisms are structurally different and are likely to remain so even if the reforms towards a modernization of the investment dispute settlement (currently discussed at the EU policy level) are eventually implemented in the near future. In light of this last point, it is possible to claim that integration between trade law and investment law will only have limited or even negative effects if the trade and investment adjudicators continue to exercise their functions in an isolated manner, without taking cognizance of (i) the norms contained in the other discipline and (ii) the other adjudicator's scope of authority. Effective convergence of trade and investment entails a two-way process pursuant to which one adjudicator can use (i.e. take into account, refer to, apply, interpret and enforce) the law of the other and vice-versa. The thesis envisages one of the two dimensions of this process, namely the use of trade law by the investment adjudicator. Looking into the details of the convergence argument, the role of investment dispute settlement mechanism and the use of trade norms over the past two decades by litigants and arbitrators, the present study identifies both the legal techniques and obstacles these actors shall apply or go beyond in order to use trade norms in the most appropriate way and, more importantly, benefit from this use.
Accepted: 2015-12-09T14:30:56Z
Keywords: Arbitrage; Arbitragem; Arbitration; Foreign investment; Foreign trade regulation; International commercial arbitration

The Investment Treaty Regime and Public Interest Regulation in Ghana: Perspectives in Constitutionalism and General International Law - Dagbanja, Dominic (University of Auckland, 2015)
There is extensive literature on conflict of legal norms and interests in international investment law. The dominant discourse is on the implications of treaty-based investment protection for sovereign regulatory autonomy. Mainstream scholarship critical of the scope and effect of investment treaties has taken the legal status of these treaties for granted. Little systematic attention has been paid to the capacity of states to make investment treaties and the obligations states can or cannot agree to under those treaties in light of their public interest obligations. Yet, this issue is of fundamental importance for three reasons. First, the case for states’ regulatory autonomy arises out of their primary duty to regulate in the public interest. This duty has its legal justification in national constitutions and international law. Second, treaty obligations are founded on the existence of legal norms necessary for the treaty to come into existence and which define the juridical consequences attached to the conclusion of the treaty. These matters are also determined by national constitutions and international law. Third, the limitations inherent in state-specific defences in international investment disputes settlement compel a proactive rethink of the conclusion of investment treaties and how they are interpreted. The question this thesis assesses with reference to Ghana then is: does a state that is legally required to act both under the terms of its constitution and international law in the public interest have the capacity to conclude investment treaties that expressly prevent or abridge the exercise of its public interest regulatory powers, and how should treaties adopted in breach of these obligations be interpreted? To address this question, three areas of public interest regulation that have featured prominently in investment arbitration serve as case studies: the jurisdiction of municipal courts, environmental protection and development policy. Based on the impact and potential limitations of standards of investment protection on these areas, the thesis argues that some treaties are incompatible with the public interest regulation obligations of Ghana under the Constitution and international law. The core proposition of the thesis is that the legal source and public purpose of the State’s powers prevent it from concluding agreements that directly prohibit public interest regulation or indirectly achieve that effect. Accordingly, the thesis proposes that the express and implied limitations on the duty to regulate in the public interest placed on investment treaty making powers of the State must inform the making of investment treaties and their interpretation. By its approach, this thesis establishes a principled basis for reflection on the limits to the State’s capacity to conclude investment treaties and on how they should be interpreted.
http://hdl.handle.net/2292/28285
Keywords: Ghana; Investment treaty; Investments; Public interest

Harmonising investment laws in the OHADA space - Mugangu, Marie Providence Ntagulwa (University of Cape Town, 2015)
The Organisation for the Harmonisation of Business Law in Africa (OHADA) was established for the purpose of restoring legal and judicial security in the region to attract more investment. The OHADA Treaty included certain areas of business law within its ambit but omitted investment law. There are several laws on investment in the region at the national, regional and sub-regional level that regulate the treatment of foreign investments such as CEMAC and UEMOA investment charters. Moreover OHADA states sign BITs to protect foreign investments. The relationship between the different sub regional laws on investment and OHADA is not yet clear but case law suggests that CEMAC and UEMOA courts recognise the supremacy of OHADA law and their lack of competence to hear matters regulated under OHADA. The standards of protection granted by OHADA states in BITs are very high thus taxing on them. This thesis suggests that OHADA states should either qualify these standards of protection or replace them with more specific provisions. The OHADA system of arbitration cannot effectively settle investment disputes arising out of a BIT leaving international arbitration systems such as ICSID as the best alternative to resolve investment disputes arising out of BITs.
Keywords: International Trade; International Trade Law; Investments

آليات تهيئة مناخ الإسثمار الأجنبي المباشر في الجزائر - بن طراد, أسماء (Ibn Khaldun University of Tiaret, 2015)
تهدف هذه الدراسة إلى استعراض تجربة الجزائر في مجال جذب الاستثمار الأجنبي المباشر من خلال الإشارة إلى جهودها المبذولة في سبيل تهيئة المناخ الاستثمار لامتلاكها مجموعة من مؤهلات واتخاذها العديد من مزايا التي تأهلها على استقطابه ، إلا أنها مازالت رغم ذلك تصنف ضمن المراتب الأخيرة من طرف الهيئات الدولية نظرا لوجود عدة عوامل تحد في مجملها من تدفق الاستثمارات الأجنبية إليها، لهذا خلصت هذه الدراسة إلى محاولة استعراض مجموعة من الآليات الكفيلة بتهيئة مناخ الاستثمار في الجزائر وجعله يتمتع بالاستقرار والجاذبية على جميع المستويات، وبناء تصور متكامل لعوامل جذب الاستثمار الاجنبي في الجزائر للفترة 1980-2012 ، لمعرفة أثرها على تدفقات الاستثمار الأجنبي المباشر واقتراح معالجات مناسبة لها بما ينعكس بالإيجاب عليها مستقبلا.
Keywords: Algérie; Climat d'investissement; Environnement des affaires; FDI; Foreign direct investment; Investissement direct étranger; Investments

An Analysis of Delay in Enforcement of Contractual Judgments as Impediment to Foreign Direct Investments (FDI) in Nigeria - Rabiu, Ahmed (Ahmadu Bello University, 2014)
Foreign Direct Investment (FDI) is about economic prosperity and wealth creation of developing economies, (FDI) brings with it capital, technology, it provides a platform for the creation of jobs and links to the world economy which brings development. The New Partnership for Africa’s Development [NEPAD] asserts that to meet its developmental challenges, Africa will have to rely more on foreign direct investment [FDI] than aid. Given the fact, the aid flows to Africa have significantly declined over the years and that the continent has now to compete with other countries for the same resources needed for development. Therefore, [NEPAD] places greater emphases on the importance of foreign direct investment [FDI] as Africa’s new engine of economic growth, particularly in the manufacturing and agricultural sector, as opposed to the oil and gas and other natural resources. However, the contribution firms, and foreign direct investment [FDI] make to the society is determined principally by the investment climate. There are many features of a good investment climate, aside of legal framework, provision of security and maintaining infrastructure, which provide the opportunities and incentives for the investment to flow and flourish and create confidence in the mind of the investors, to invest productively, and they include strong and vibrant contract enforcement. Delays or uncertainties in the enforcement of contractual rights erode the value of property rights and diminish the opportunities and incentives to invest. Therefore, the process of seeking redress through the normal court system is too protracted and unsatisfactory to continue to serve as primary recourse option of executives and potential investors, and this also explain the slow of improvement in FDI in the manufacturing and agricultural sector inflow to Nigeria. There are additional reasons for all these difficulties and hurdles that constitute a clog to an efficient contractual enforcement. The legal system that made judges of regular courts to also handle election petitions and other ad-hoc assignments to the detriment of the regular pending commercial cases before the courts. Secondly, there currently distinct rules for each state of the Federation and there number of civil procedure rules required to be complied with to move cases through the system from filing to judgment enforcement. This has created additional and unnecessary procedures that elongate the process of contract enforcement. Thirdly, despite these enormous powers of the Sheriff and bailiffs in the process of trials and enforcement of contractual judgments, in Nigeria majority of the bailiffs in all our courts including the courts of records are either retired police or military officers with no formal training on their powers and obligations in accordance with the provision of the law.The dissertation mainly recommended the creation of Commercial courts or Commercial divisions throughout the federation to handle contractual and commercial cases; secondly, Secondly, it is recommended for the unification and adoption of a single the civil procedure rules throughout the country. Lastly to institutionalize the training and retraining of sheriffs and court bailiffs on the provisions of the rules as it relates their functions of giving effect to court orders and judgment.These would go a long way in providing an effective and speedy movement of civil cases through the system of trial and subsequent enforcement in our courts, which may further create confidence and improve the investment climate for the inflow of the Foreign Direct Investment (FDI) in to Nigeria.
Keywords: Contract; Enforcement; FDI; Foreign direct investment; Impediment; Investments; Judgments; Nigeria

L'investissement : étude juridique - Grundeler, Guillaume (Aix-Marseille Université, 2014)
L'investissement est une notion récente dans la sphère juridique. Voici quelques années, elle n'était encore employée que dans la règlementation relative au contrôle des investissements étrangers. C'est que, si le droit n'ignorait pas l'investissement, il le saisissait presque uniquement à travers d'autres notions, tels l'apport en société ou le mouvement de capital. Depuis lors, le mot a été très largement juridicisé. Pour s'en tenir à deux exemples, on peut ainsi relever que, dans notre ordre interne, l'existence d'un investissement permet une durée contractuelle longue et que, dans l'ordre international, la qualification d'investissement est aujourd'hui une condition de la compétence des tribunaux arbitraux statuant sous l'égide du Cirdi.Cet accès spontané de l'investissement à la juridicité s'est malheureusement accompagné de certaines incohérences. Ainsi, le mot est parfois employé de manière excessivement large, comme en droit des marchés financiers, où il désigne toute opération relative à un instrument financier. De même, en droit des régimes matrimoniaux, ce que la Cour de cassation nomme les « dépenses d'investissement » recouvre en réalité l'ensemble des dépenses immobilières. Parfois, à l'inverse, certaines opérations dont la qualification d'investissement ne fait aucun doute continuent d'être envisagées à travers des notions qui en sont le simple reflet. L'objet de la thèse est donc de rétablir une certaine cohérence dans l'emploi du mot investissement en proposant une définition juridique de la notion et en esquissant certains éléments du régime qui s'y attache.
Keywords: Apport; Arbitrage d'investissement; CIRDI; Capital contribution; Centre international pour le réglement des différends relatifs aux investissements; Civil liability; Contrôle des investissements étrangers; Droits sui generis du producteur de bases de données; Duration of the contract; Durée contractuelle; Foreign investment regulation; Foreign investments; France; Free-Riding; ICSID; Investissements; Investissements étrangers; Investisseur; Investment arbitration; Investments; Investor; Parasitisme; Responsabilité civile; Return on capital; Rémunération; Sui generis right of the producer of a database

Rapport sur l'amélioration du climat des affaires en Afrique Centrale - Commission Économique Pour l'Afrique (Bureau Sous Régional pour l'Afrique Centrale, 2014)

The effects of the South African anti-dumping and competition measures upon foreign direct investment - Sibanda, Omphemetse S. (Journal of Business and Retail Management Research, 2014)
Since the dawn of democracy South Africa has embarked in a process of dismantling protectionist business and trade policies, and made the country’s stream of commerce one of the preferred globally. The country’s sound competition and trade policies, natural resource endowments, market size and regional influence, attracted foreign businesss and foreign direct invetsment (FDI). Equally the country has been under pressure to protect the domestic industries from injurious competition and business, through sector specific laws, anti-dumping and countervailing duties laws, investment and competition regime. The concern has been the likilelihood of the introduction of trade and competition barriers, and the allienation of FDI. This paper critically examines the impact the country’s antidumping and competition law and practice upon foreign direct investment. Domestic industries have never been shy to file anti-dumping and anti-competition suits against foreign companies, sometimes even when there might be a public outcry. Relevant examples of these suits include the famous Wal-Mart anti-competition case, and recently the Brazilian frozen fowl meat anti-dumping case.
Keywords: Anti-Dumping; Competition; Consumers; Divestment; Domestic Industry; Investments; Protection; Tariffs

Les produits structurés et la protection de l'investisseur - Gomez Richa, Lucia (Université de Genève, 2014)
La présente étude propose une analyse juridique des produits structurés (art. 5 LPCC), qui la conduit à une réflexion plus large quant à la protection de l'investisseur en droit suisse, de lege lata mais également au regard de l'avant-projet de loi sur les services financiers. L'étude met tout d'abord en lumière les incohérences et les insuffisances du système juridique actuel. Elle propose une définition nouvelle des produits structurés assurant une cohérence au système. Avec comme fil conducteur et illustration la complexité des produits structurés, la thèse explique et critique le retard de la réglementation suisse en matière de protection des investisseurs, tant s'agissant de la conception juridique de l'investisseur que de la concrétisation des règles de conduite par l'émetteur et les distributeurs. Elle expose et discute les règles et pratiques existantes visant à répondre à certains des enjeux posés. Enfin, la thèse énonce des propositions d'amélioration à ces règles, en grande partie relayées par l'avant-projet de loi sur les services financiers.
Keywords: Anlage (Investition); Anlagefonds; Derivative Finanzinstrumente; Instruments dérivés (finances); Investisseurs directs; Produits structurés; Produits structurés (finances); Protection; Protection de l'investisseur; Risque financier; Réglementation des marchés financiers; Schweiz; Sociétés d'investissement; Suisse

Venture capital: valor da informação, riscos e instrumentos para sua mitigação - Silva, Fernando César Nimer Moreira da (Universidade de São Paulo, 2014)
Venture capital é espécie de empreendimento que vincula dois agentes econômicos, empreendedor e investidor, visando ao desenvolvimento de uma ideia inovadora para posterior comercialização no mercado. O empreendedor é detentor de conhecimento sobre a ideia e o investidor possui os recursos para desenvolver o projeto. O negócio se diferencia dos demais pelo alto grau de incerteza e risco do empreendimento e requer o uso de tipos contratuais adequados para sua limitação. O projeto se inicia com a etapa de contratação, na qual as partes negociam a divisão de riscos e retorno do negócio, seguindo-se a etapa de monitoramento do desenvolvimento das atividades. Ao final ocorre o desinvestimento, com a saída do investidor e venda do negócio. Do ponto de vista da Economia, utilizamos a Teoria dos Jogos e apresentamos os problemas informacionais, riscos e incertezas do negócio, e os incentivos para organizar a cooperação entre as partes. Do ponto de vista de Finanças, debatemos a decisão de financiamento do negócio e as alternativas para diversificação dos riscos do investimento, isto é, a possibilidade de limitação dos riscos pela adoção de estratégias de contenção, que aumentam o interesse em contratar o negócio. Do ponto de vista do Direito, avaliamos qual a estrutura contratual ideal para organizar esse tipo de empreendimento. Analisamos as principais formas usadas para organização do negócio, em especial as sociedades limitadas e as sociedades anônimas fechadas. Avaliamos o suporte normativo aplicável, com destaque para a possibilidade de limitação dos riscos do projeto pela aplicação das normas de Direito Societário a esses empreendimentos. Os principais riscos aplicáveis são os riscos de contratação do negócio, os riscos de alocação do poder de decisão entre os sócios e os riscos de interrupção prematura do projeto. Devido à natureza e características do negócio de venture capital, concluímos que esse tipo de projeto é mais bem organizado como um contrato plurilateral e que não há tipo contratual ideal para alinhar os interesses. Dos tipos existentes, a sociedade anônima fechada é o mais adequado, mas incapaz de limitar todos os riscos do negócio. A conclusão é confirmada, parcialmente, pelas evidências empíricas apresentadas. Venture capital is a business that links two economic agents, entrepreneur and investor, aiming to develop an innovative idea for future sale on the market. The entrepreneur holds knowledge about the idea and the investor has the resources to develop the project. It is distinguished from others by the high degree of uncertainty and risk of the project and requires the use of appropriate contract types for its restriction. The project begins with the contracting stage, in which the parties negotiate the division of risks and return business, followed by the monitoring of the development of the business activities. At the end occurs the divestment, in which the finished business is sold by the investor. From the point of view of Economics, we use Game Theory to present the informational problems, business risks and uncertainties, and the incentives to organize the cooperation between the parties. From the standpoint of Finance, we discuss the decision to finance the business, and alternatives for risk diversification, that is, the possibility of limiting the risks by adopting containment strategies that may increase the interest in contracting. From the point of view of Law, we evaluate the ideal contractual structure for organizing this kind of project. We analyze the main existing contract types, in particular, the limited liability companies and the closed corporations. We present our concerns about the normative support applicable to that type of business, emphasizing the Corporate Law problems. We evaluate the normative support applicable, emphasizing the possibility of limiting the project risks by applying the Corporate Law rules to such ventures. The main risks are the risks applicable to the contracting phase, the risk of incorrect allocation of decision rights between the partners and the risk of premature termination of the project. Due to the nature and characteristics of the venture capital business, we conclude that this type of design is best organized as a plurilateral agreement and that there is no contract type that can be considered ideal to align the interests. Considering all the existing types, the private corporation contract is the most appropriate form, but also unable to limit all the business risks. The conclusion is partially supported by the empirical evidence presented.
Keywords: Capital de risco; Capital-risque; Closed company; Closed corporation; Contract; Corporate finance; Direito comercial; Game theory; Instruments; Investimentos; Investment fund; Law and economics; Limited liability company; Mercado de capitais; Risk; Risque; Uncertainty; Venture capital

Reconciling international investment law and sustainable development with respect to host state's right to regulate : the legal impact of sustainable development objective on indirect expropriation standard and its legitimate expectations sub-element - Dubava, Ilze (European University Institute, 2014)
This thesis seeks to determine whether the evolution of international law has allowed for the concept of cultural genocide to be addressed in spite of its non-codification. It firstly provides an assessment of the evolution of the concept of cultural genocide, from a technique to a process of genocide, also known as 'ethnocide'. Acknowledging that the codification of the concept is unlikely in the future, it therefore undertakes a study of the evolution of international law with regard to the main components of the concept, namely genocide, culture and group. The evolution of the legal concept of 'genocide' raises the question of the interpretation of the international definition of genocide, which is enshrined in the 1948 Convention on the Prevention and Punishment of the Crime of Genocide, so as to encompass instances of cultural destruction. The state of international and domestic judicial practice illustrates the limits of an evolutionary interpretation. In contrast, international law has evolved considerably in relation to the protection of some groups and their culture, so that customary international law, and especially international human rights law, may be deemed to prohibit group cultural destruction and consequently entail State responsibility. The thesis argues that this evolution could ground the articulation of an international law-based approach to the concept of cultural genocide both by allowing for its criminalisation through the crime against humanity of persecution and by providing tools for a stronger framework of State responsibility, especially in the context of genocide prevention. Furthermore, this approach would give rise to the possibility of further conceptualising reparation for the intended cultural damage. Against this background, the thesis firstly draws conclusions as to the irrelevance of enclosing the debate exclusively at the level of the genocide legal framework and, secondly, as to the relevance of cultural genocide as a 'paralegal concept', an understanding which would drive the interpretation of international legal norms, especially in cases involving indigenous peoples' cultural harm.
Accepted: 2014-07-14T15:02:04Z
Keywords: Economic aspects; Economic development; Foreign investment; International Law; Investments

Investment Protection in the Framework of the Treaty of Harmonizing Business Law in Africa (OHADA) - Houanye, Paulin; Shen, Sibao (Beijing Law Review, 2013)
A few years ago, African contribution of the world trade was only around 2%. The investors, except those who are exploiting natural resources, never want to dare dispensing their fund in Africa. The reason of this situation was very simple. The majority of investors denounce the juridical insecurity and also the political preponderance across the African continent. With human and natural resources abundant, Africa is regarded as a continent equipped with a great potential of development. The years of independences in Africa saw being born in many States, of the organizations trying to solve these difficulties and to reinforce their capacities by the constitution of international organizations acting in all the fields. But it is only in the year 1990; some organizations appeared in the continent and knew of real rise thanks to the liberal and democratic economic policies. This article wishes to present an assessment of seventeen years implementation of the African Harmonization of Business Law Treaty of 1993. Firstly, it will describe the system from an institutional point of view and hence from a normative point of view. Secondly, during the course of this essay, there will be a focus on analysis of OHADA’s laws, its system and its potential impact. In addition, the article will concentrate on OHADA’s appropriateness in the business sector and necessary guarantees it must offer for a successful investment partnership with foreign investment.
Keywords: African Development; Harmonization; Harmonization Business Law; Investment Law; Investments; Regional integration; Rule of Law

Applicable law in investor-state arbitration: the interplay between national and international law - Elisabeth Kjos, Hege (Oxford University Press, 2013)
This book examines the law, national and/or international, that arbitral tribunals apply on the merits to settle disputes between foreign investors and host states. In light of the freedom that the disputing parties and the arbitrators have when designating the applicable law, and because of the hybrid nature of legal relationship between investors and states, there is significant interplay between the national and the international legal order in investor-state arbitration. The book contains a comprehensive analysis of the relevant jurisprudence, legal instruments, and scholarship surrounding arbitral practice with respect to the application of national law and international law. It investigates the awards in which tribunals referred to consistency between the legal orders, and suggests alternatives to the traditional doctrines of monism and dualism to explain the relationship between the national and the international legal order. The book also addresses the territorialized or internationalized nature of the tribunals; relevant choice-of-law rules and methodologies; and the scope of the arbitration agreement, including the possibility of host states presenting counterclaims in investment treaty arbitration. Ultimately, it argues that in investor–state arbitration, national and international law do not only coexist but may be applied simultaneously; they are also interdependent, each complementing and informing the other both indirectly and directly for a larger common good: enforcement of rights and obligations regardless of their national or international origin.
https://ora.ox.ac.uk/objects/uuid:a52424f2-4c14-4cc1-a452-6d926a0a02fe https://library.oapen.org/bitstream/handle/20.500.12657/33860/453473.pdf
Keywords: Arbitral tribunals; Choice-of-law rules; Foreign investors; Host states; International law; Investor-state arbitration; National law; OAPEN

L'émergence du droit international des investissements : contribution des traités bilatéraux d’investissement et de la jurisprudence du CIRDI - Danic, Olivia (Université Paris 10, 2012)
La relation dialectique qui unit les traités bilatéraux d’investissement et la jurisprudence du Centre International de Règlement des Différends relatifs aux Investissements (CIRDI) a fait émerger un droit international des investissements. La rencontre de ces deux dynamiques a permis de dépasser leur caractère a priori isolé et fragmenté, pour aboutir à un véritable système juridique international, doté d’une structure, d’une logique et de principes propres. En effet, rien ne pouvait laisser envisager une telle évolution, le régime de l’investissement international se fondant sur une multitude de traités bilatéraux et sur une instance arbitrale ne faisant qu’héberger des tribunaux éphémères. Les mouvements de va-et-vient qui unissaient ces deux phénomènes ont permis de lui donner des normes quasi-universelles, mais aussi un véritable juge à la compétence extensive et surtout de lui insuffler l’unité, l’efficacité, la cohérence et la complétude, faisant de plus en plus ressembler le droit international des investissements à un véritable ordre juridique qui, même s’il relève du droit international, lui permet également d’évoluer. The relashionship between bilateral investment treaties and the case-law of the International Centre for Settlement of Investment Disputes (ICSID) has led to the emergence of international investment law. It seems surprising, at first, that these two distinct phenomena, being isolated and fragmented, would reach a certain degree of unity so that a real international legal order could appear, with its own structure, reasoning and principles. No one could foresee such an evolution, the regime of international investment being founded on a large number of bilateral treaties and on an international institution which only provides facilities for arbitration of international investment disputes. The unity of the system has been discovered through the back and forth movements between treaties and arbitration which gave rise to international investment law. This system has now almost universal norms, an international judge and satisfies the criteria of unity, efficiency, consistency and completeness, producing a real legal order functioning in accordance with its own logic. There is no doubt that this evolution will influence the course of international law.
Keywords: Arbitrage; Arbitrage (droit); Arbitration; Bilateral Investment Treaties (BITs); CIRDI; Centre international pour le réglement des différends relatifs aux investissements; Droit international; ICSID; International law; Investissements; Investissements étrangers (droit international); Investment; Investments; Jurisprudence; Legal order; Ordre juridique; Traité bilatéral d’investissement

Full protection and security in International Law - Magnusson, Finnur (Universität Wien, 2012)
The thesis covers one of the investment standards of international investment law, namely the full protection and security standard. In Part I, the study is introduced in terms of structure and substance. Chapter 1 provides a description of the scope of the research topic and a definition of its terms and structure. Chapter 2 covers the historical development of the full protection and security standard. Part II deals with three fundamental issues concerning the standard: sources, interpretation and content. Chapter 3 contains a discussion dealing with the various sources of the standard. Each source will be studied independently. Chapter 4 will address general issues with regard to interpretation, such as to what extent the Vienna Convention on the Law of Treaties influences the process of interpretation. Chapter 5 deals with the content of the standard of full protection and security, including conceptual issues relating to the substantive elements of which the standard consists. Moreover, the chapter will ask questions as to which underlying issues are needed to explore when a due diligence assessment is made in order to determine whether a state has fulfilled its obligations to provide protection and security. Part III deals with issues relating to the violations of the standard. In Chapter 6, the violations of the standard and their many manifestations will be analyzed. The chapter will address whether certain fact-based scenarios can be established in which the standard is most commonly violated. Finally, Chapter 7 contains a summary of findings.
Keywords: Arbitral Awards; Bilateral Investment Treaties (BITs); Due diligence; Full protection standard; Full security standard; ICSID; International Investment Law; International law; Investment standards; Investments

Les problèmes juridiques relatifs à la communautarisation du droit des investissements dans l’espace UEMOA - Ouedraogo, Séni Mahamadou (Annuaire Français de Droit International, 2012)
Le développement du droit communautaire en Afrique de l’Ouest couvre aujourd’hui un large champ qui s’étend aux investissements demeurés au lendemain des indépendances des États africains dans le périmètre de leur souveraineté. Les enjeux actuels du droit international des investissements, en raison des exigences de la mondialisation des économies, ont contraint les États de l’espace CEDEAO et UEMOA, importateurs de capitaux, à faire converger leur réglementation des investissements afin de favoriser leur attractivité et d’en tirer le meilleur parti. La difficulté d’un tel objectif réside dans la nécessité d’arriver à concilier leurs intérêts avec ceux des investisseurs, qui ne sont pas toujours convergents. The development of community law in West Africa nowadays covers a wide field extending to investments which, in the aftermath of independence, remained within the scope of sovereignty of African states. The current challenges of international investment law, because of the requirements of economic globalisation, have compelled ECOWAS and WAEMU countries, as importers of capital, to ensure convergence of their investment regulations so as to make them more attractive and to get the most out of them. The difficulty of such an objective lies in the need to successfully reconcile their interests with those of investors, which do not always converge.

Public assets financing in Nigeria : the imperatives for legal reforms to unlock domestic financial resources and foreign capital for infrastructure development - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2012)
Infrastructure is one of the main parameters of economic growth and a country‘s competitiveness depends on the provision and maintenance of efficient and productive infrastructure assets. However, Nigeria, like most countries in Sub-Saharan Africa has the lowest quantity and poorest quality of stocks of infrastructure assets in the world and this phenomenally poor infrastructure has remained an impediment to development in the country. Decades of sub-optimal investment, poor maintenance culture and the fact that the required infrastructure investments could not be accommodated within the available fiscal space as a result of budgetary constraints have all contributed to the Nigeria‘s infrastructure deficit. The immediate outcome of this however is that the available infrastructure assets across the Nigerian landscape are in decrepit state and absurdly inadequate. Besides, the present demand for basic infrastructure services has grown astronomically out-stripping the supply capacity of the existing ones. Closing the infrastructure financing gap will however require increased investment by private investors through creative financing in an enabling legal and financial environment. Outside the budgetary constraints, the absence of efficient maintenance and management of infrastructure assets and quality service delivery by the public sector are some of the reasons why procurement of public infrastructure stocks by government through the traditional approach is no longer plausible and hence, the general appeal of the public-private partnership framework. However, despite all the potentials, the public private partnership technique in Nigeria has not made an appreciable impact in closing the infrastructure gaps due to lack of access to long-term financing. It is against this back-drop that this study has sought to investigate how reforms of the legal and financial infrastructure could widen access to financing through innovative financial resource mobilization in scaling-up infrastructure development and service delivery to the teeming Nigeria population. Therefore, the central thesis of this study is that the inadequacy of appropriate laws and inefficient financial system are partly responsible for the huge financing gaps in the Nigeria‘s infrastructure market and with the legal and financial reforms, an enabling legal and financial environment that would open up space for resource mobilization through innovative financing techniques and sources will be created thereby widening access to long-term financing and increasing the appetite for private investment in the nation‘s public infrastructure assets and services. So, the overarching objective of this thesis is to explore how legal and financial system reforms can facilitate the development of financial models and instruments that can help mobilize financial resources to fund infrastructure and bridge the huge infrastructure financing gaps in Nigeria in a sustainable fashion. Given the infrastructure poverty that constrains economic growth and development in Nigeria, the outcomes of this proposed study would help inform the need for the legal and financial system reforms to unlock resources in addressing the problems of financing gaps in infrastructure projects development in Nigeria. Besides, such outcomes based on the Nigerian experience in infrastructure financing and development may be turned into valuable knowledge for policy –making and further research in Nigeria. Copyright
https://repository.up.ac.za/handle/2263/24525
Keywords: Foreign capital; Infrastructure; Legal reform; Nigeria; Public assets

Common good and the concept of expropriation in international law on foreign investment: Determinacy of substance in legitimacy of structure - Falsafi, Alireza (McGill University, 2011)
This thesis, exploring the rule of law for international rules, offers a human bond of common good between determinacy of substance and legitimacy of structure of rules in order to evaluate international obligations of States in international law on foreign investment. In an in-depth exposition of the theoretical underpinnings and practices underlying the normative structure of rules in international law, the thesis critically questions the legal reasoning embedded in—and the authority of rules borrowed from—principles and precedents or moral and political evaluations by arbitrators in interpretation of States' contractual, customary, and treaty obligations in investment arbitrations. With crucial moral, political, social and economic ramifications for the constitutional functions of States and concomitant interests of their human members implicated in the concept of expropriation in international law, the thesis provides a framework of legitimacy in a common good approach with structural criteria of recognition and coherence for the interpretation of States' obligations in investment arbitration. Coherence brings to the fore conflicting demands of justice requiring fresh evaluation divesting a general rule of its authoritative force, and recognition brings to the fore the validation of the power to engage in moral and political evaluation. Together, these structural criteria offer a common good approach of legitimacy to test the authority of States' obligations and the power of arbitrators in hard cases. By virtue of these criteria, the thesis characterizes the nature of substantive property rights of corporations and corresponding obligations of States in foreign investment as contingent and consensual in contrast with the absolute and constitutional rights of human beings in human rights. Through coherence and recognition, the thesis also portrays a supreme status for customary international law for the normative structure and substance of States' contractual or treaty obligations in the interpretation of hard cases in international law on foreign investment. The thesis espouses a new horizon for legal reasoning in foreign investment arbitration that eschews the lex lata veneer for lex ferenda propositions manufactured from precedents and principles, on the one hand, and the sheen of law for the conception of justice of investor-State arbitrators, on the other, in cases of hard confrontation between the demands of justice.
https://escholarship.mcgill.ca/concern/theses/dv13zz300
Keywords: Expropriation; Foreign investment; International law

La qualification d'investissement étranger : contribution à la notion juridique d'investissement et à la définition de l'extranéité - Onguene Onana, Dieudonné Edouard; Prujiner, Alain (Université Laval, 2011)
La compétence d'un arbitre chargé d'appliquer le droit international des investissements exige l'existence préalable d'un investissement étranger. Cette étude vise à identifier ce qui constitue un investissement parmi l'ensemble des opérations économiques et financières et à déterminer les conditions auxquelles il doit répondre pour être considéré comme étranger. L'importance de la Convention de Washington explique l'attention particulière portée au Centre international pour le règlement des différends relatifs aux investissements (CIRDI). La diversité des traités bilatéraux et des autres sources normatives dans ce domaine a conduit à proposer une approche fondée sur une dissociation du contrôle sur la base des sources normatives de la compétence arbitrale. Après un exposé introductif sur l'évolution des modes de règlement des différends relatifs à la propriété étrangère et son aboutissement à l'arbitrage international actuel, la première partie de l'étude est consacrée à la définition de la notion juridique d'investissement dans une perspective de qualification par l'arbitre. La seconde partie analyse la seconde exigence pour établir la compétence de l'arbitre, celle d'extranéité de l'investissement, et elle expose les conditions liées à la nationalité de l'investisseur.
Keywords: Arbitrage; Arbitrage international; Arbitragem; Arbitration; Investissements; Investissements étrangers; Investments; Sociétés

Revisiting the Depoliticization of Investment Disputes - Schneiderman, David (Yearbook on International Investment Law and Policy, 2011)
The chapter challenges claims about depoliticization in two different aspects. The first examined claim is that home states are disenfranchised from pursuing investment claims once they are lodged with ICSID. Is it the case that home states simply stay home? This chapter examines instances where home states may have played a role in investment disputes between contracting states. What the record generally reveals, however, is that home states involve themselves in disputes where ICSID hearings are imminent but not yet in play. The second, broader, reading of depoliticization maintains that disputes now are resolved without recourse to lowly politics but to ‘higher’ law. This more extravagant claim is vulnerable to the critique that investor-state dispute resolution is not emptied of political content but, instead, spills over with politics. As the regime implicates the capacity of public authority to act in a wide variety of regulatory contexts, the separation of law from politics is hard to credibly maintain. Not only are investor-state disputes embedded within regimes of political discourse and political power, the ambit of investment arbitrator discretion is so capacious that it can be said of arbitrators, as it has been said of the U.S. Supreme Court, that they can sensibly be regarded as political actors.
Accepted: 2024-06-14T19:55:42Z

Essays on policy reforms in trade, investment and taxation - Wagle, Swarnim (Australian National University, 2011)
This thesis consists of three essays on trade, investment, and taxation that are unified by their policy relevance to developing countries. Following an introductory chapter on policy reform, the first essay revisits the institutional determinants of foreign direct investment (FDI) using a comprehensive new data set covering more than 80 countries. It exploits the presence of confirmed zero investment flows between countries to estimate productivity cut-offs of firms that invest abroad profitably. This approach corrects likely biases arising from firm heterogeneity and country selection in a theoretically derived gravity-type model. The analysis finds inward FDI to be highly responsive to cross-country variation in specific institutional provisions, such as arbitration of disputes and legal procedures to establish foreign subsidiaries. The importance of FDI-specific regulations stands out even after controlling for the general quality of institutions. Statutory openness to FDI, however, has no association with actual inflow of investment. The second essay examines cross-national differences in the survival of exports through the lenses of product, industry, and country characteristics. The estimates are derived from a new application of discrete-time models instead of the continuous-time (Cox) models that are standard in trade duration analysis. The examination of exports originating in more than 100 developing countries covering 4000 products over 12 years shows that export flows are much more fragile than suggested by trade theory. Using new measures of product sophistication and export diversification, the paper finds evidence of information and network externalities that aid export survival. Exports concentrated in a few industries or in a narrow range of destination markets exhibit higher rates of death, whereas export concentration within some industries is positively associated with survival, suggesting a synergistic network effect. The probability of export death decreases with proximity from the capital content of products to the national factor endowment, competitive real exchange rate, and bilateral trade preferences. Further, death rates for dynamic subsets of exports like manufactured components and processed food differ from other products, belying the notion that short durations are necessarily a result of poor exporter capabilities. The third essay assesses the revenue implications of coordinated tariff and tax reforms. It is shown for a sample of low-income countries over 25 years that they have had a mixed record of offsetting reductions in trade tax revenue, and that Value-Added Tax (VAT) has, at best, played a limited role. The paper then analyzes the specific case of Nepal, using a unique data set compiled from unpublished customs records of imports, tariffs, and all other taxes levied at the border. It estimates changes to revenue and domestic production associated with two sets of reforms: i) proportional tariff cuts coordinated with a strictly enforced VAT; and ii) proposed tariff cuts under a regional free trade agreement. It is shown that a revenue-neutral tax reform is conditional on the effectiveness with which domestic taxes are enforced. Furthermore, loss of revenue as a result of intra-regional free trade can be minimized through judicious use of Sensitive Lists that still cover "substantially all the trade" as required by Article XXIV of the General Agreement on Tariffs and Trade (GATT).
Keywords: Commercial policy; Fiscal policy; Free Trade; Investments; Taxation

Différends entre investisseurs et État : Prévention et modes de règlement autres que l’arbitrage - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Nations Unies, 2010)
Keywords: Différends; Etat; Investisseurs; Modes de règlement; Prevention

Bilateral Investment Treaty between Spain and Guinea: Legal Framework - Vives, Pascual; José, Francisco (2009)
Keywords: Dispute settlement; Equitable treatment; Expropriation; Fair treatment; Guinea foreign investment; ICSID; Investment; Investor; Investor-State Dispute Settlement; National treatment; Spanish BITs

The development of performance requirements in international law and their effect on BITs and FTAs as well as on the agreeing parties - Bless, Christopher Josef Manfred (Universität Wien, 2008)
Performance requirements are part of a system of policy measures implemented by states to advance their economic, social and political objectives. A universally agreed upon definition of performance requirements is not available. Rather they are defined by the applicable legal norms and their assessment is dependent upon their effect on the parties of each individual case. The scope of legal protection these regulations provide must be measured separately for each norm within the scope of the specific legal framework. This dissertation has two objectives: First, the implementation and legal effect of performance requirements in international investment and trade law are investigated. Secondly, a legal test will be developed, that allows for an assessment of performance requirements. In a first step, the legal treatment of performance requirements will be analyzed from a theoretical perspective. Subsequently, the legal practices relating performance requirements and the relevant provisions in international investment and trade law will be identified. The developed legal test does not only do justice to the economic, social and political framework within which each performance requirement must be looked at but is also adaptable in a way that it can be applied to a variety of situations and legal traditions. It satisfies both the demands of legal certainty and clarity as well as facilitating the finding of justice on an individual basis. Understanding the advantages of foreign direct investment, the analysis performed aims promote the usage of performance requirements in a way that foreign direct investment will push the global economy forward.
https://phaidra.univie.ac.at/detail/o:1258202
Keywords: FIRA; Foreign direct investment; Free trade agreements; International Trade; International investment; Investment treaties; NAFTA; Performance requirements

L'évolution du droit international en matière d'investissements directs étrangers - Zorila, Carmen Rodica (Université d'Auvergne Clermont-Ferrand 1, 2007)
Cette thèse présente le parcours difficile du droit en matière d’investissements directs à l’étranger vers son internationalisation. La difficulté d’intégration dans le droit international des normes juridiques régissant l’investissement étranger a été due aux changements intervenus dans les relations internationales, à la suite de confrontations politiques, idéologiques et surtout économiques entre les pays. Les mécanismes conventionnels, les traités bilatéraux et la multiplication des arrangements régionaux ont contribué à une juridicisation nouvelle de la société mondiale. Cependant, ce n’est qu'un instrument multilatéral global, généralement accepté et qui échapperait de ce fait aux rapports de pouvoir au niveau mondial qui pourrait consacrer l’avènement d’un droit international en matière d’investissements directs étrangers. Assurant la stabilité du système multilatéral, il serait l’outil juridique qui permettrait de régir différemment la mondialisation économique.
Keywords: Droit international; FDI; Foreign direct investment; Investissements étrangers; Mondialisation

La participation des collectivités territoriales au capital de sociétés - Peltier, Marc (Université Paris 1, 2005)
La législation française se fonde traditionnellement sur un conflit entre l'intérêt général, le but lucratif et le risque d'entreprise. La participation des collectivités territoriales au capital de sociétés est alors en principe interdite. De nombreux textes autorisent cependant des collectivités territoriales à participer au capital de sociétés spécifiques. La protection de l'intérêt général et l'accueil des collectivités territoriales se font dans des groupements qui dérogent au droit commun des sociétés. Ces régimes sont porteurs de risques tant pour la société elle-même que pour les collectivités territoriales. Une autre approche de la participation des collectivités territoriales au capital de sociétés devrait être envisagée. Le droit communautaire pourrait servir de référence en s'inspirant du critère de l'investisseur privé en économie de marché. La transposition en droit interne de ce critère permettrait de faire évoluer le régime de ces sociétés vers le droit commun.
Keywords: Administration locale; Capital social; Droit commercial; France; Investissements de capitaux; Sociétés d'économie mixte

Un meilleur climat de l’investissement pour tous (Éditions De Boeck Université, 2005)

Le régime des investissements directs dans les zones franches d'exportation - Ravaloson, Johary (Université de La Réunion, 2002)
Adopté souverainement par l'État afin d'aménager l'attractivité de son territoire sur le marché des investissements directs, ce régime soustrait cependant les rapports d'investissements à l'ordre juridique national. Primo, négocié avec les investisseurs dans son élaboration comme dans son application, mis en concurrence face à des régimes équivalents d'autres États : le régime est marchandisé. Secundo, le lien spécifique entre le traitement privilégié des investissements et l'affectation obligée de leurs produits vers l'exportation subvertit le principe de territorialité qui fonde le régime : il est soumis aux préférences des États importateurs et est saisi par le droit de l'OMC : d'abord, l'Accord MIC limite la marge de manoeuvre de l'État dans sa définition des obligations des investisseurs ; ensuite, parce que les avantages fiscaux forment des subventions "spécifiques" au regard de l'Accord SMC et donc susceptibles de mesures compensatoires de la part des États importateurs.
Keywords: Compétitivité (économie politique); Droit international; Déréglementation; Investissements étrangers; Investments; Territoires internationalisés; Zones franches industrielles d'exportation